Surfactin suppresses postharvest gray mold in Actinidia arguta fruit via direct antifungal activity and induced host resistance - Feiyang Wang; Sen Dong; Hang Che; Baodong Wei; Dazhi Zhang; Bingxue Li; He Gao; Shunchang Cheng (Food Control, 2027)

How pyruvate postpones postharvest physiological deterioration of cassava - Yannian Che; Chen Shen; Xiaohua Lu; Zhongping Ding; Yaxingqiao Zhou; Qin Zhou; Jiao Liu; Yajie Wang; Jianchun Guo; Yuan Yao; Alisdair R. Fernie; Ruimei Li (Postharvest Biology and Technology, 2026)

Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Alginate-derived oligosaccharides obtained from enzymatic hydrolysis of Laminaria improve temperature adaptability and increase bioactive compound yield in Phaeodactylum tricornutum - Xingkai Che; Dingning Fan; Ruirui Ding; Litao Zhang; Benwei Zhu; Yongfu Li (Bioresource Technology, 2026)

Melatonin inhibits malignant biological behaviors in carboplatin-resistant ovarian cancer cells: elucidating the potential molecular mechanisms - Xiaoying Li; Xiaoyu Che; Yanhong Bi (Molecular Biology Reports, 2026)

Tidal air exposure thresholds in seagrass survival: photodamage-antioxidant imbalance and anthocyanin accumulation associated with Enhalus acoroides zonation limits - Hu Li; Shuju Guo; Mengjie Zhang; Tie Zhang; Litao Zhang; Xingkai Che; Wenjie Yu; Jianguo Liu (Marine Pollution Bulletin, 2026)

Fruit allergens and their allergenicity reduction: characteristics, technologies, and prospects - Tanying Zhang; Jinshen Chu; Yuntong Ying; Haochen Ye; Mengxian Li; Yiran Xie; Haozhe Yi; Jing Che; Bowen Li; Binjia Zhang; Xiaowen Pi (Trends in Food Science & Technology, 2026)

Synergetic chemical passivation and energy level alignment via multifunctional polyurethane for high-efficiency Sb2S3 solar cells - Yifan Sun; Jiawang Che; Xiaochen Feng; Yanqing Wang; Xiang Li; Zhiping Fang; Min Fan; Dongchen Guo; Hui Dai; Chengwu Shi (Chemical Engineering Journal, 2026)

Arginine and putrescine ameliorate heat stress-induced testicular inflammation and apoptosis via inhibiting endoplasmic reticulum stress in mice - Kun Wu; Chenglong Yu; Guangmang Liu; Yong Zhuo; Bin Feng; Lianqiang Che; Shengyu Xu; Lun Hua; Jian Li; Zhengfeng Fang; De Wu; Yan Lin (Theriogenology, 2026)

Mechanism of glyoxalase MeGLYI-13 in regulating postharvest physiological deterioration of cassava - Chen Shen; Yannian Che; Zhongping Ding; Qin Zhou; Yaxingqiao Zhou; Alisdair R. Fernie; Jiao Liu; Yajie Wang; Xiaohua Lu; Jianchun Guo; Yuan Yao; Ruimei Li (Postharvest Biology and Technology, 2026)

Mine water as a multidimensional resource: A critical process engineering review of water-energy‑carbon nexus technologies, maturity assessment and scale-up challenges - Che Lulu; Li Bo; Yang Ya; Yang Yu; Luo Ye; Li Tao (Journal of Water Process Engineering, 2026)

Engineering Co-N4 active sites in heptazine-porphyrin organic polymer to boost non-radical singlet oxygen generation in peroxymonosulfate activation - Xiang Li; Yu Tian; Yalong Xu; Bo Liu; Shi Zhou; Wei Jiang; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Integrated biochar-iron amendment mitigates rice cadmium uptake via soil immobilization, iron plaque barriers, and microbial community restructuring - Meiling Xu; Tianyi Hu; Fangge Xu; Jing Che; Guobing Wang; Yepu Li; Qiao Xu; Xiaozhi Wang (Journal of Environmental Chemical Engineering, 2026)

Optimization of zeotropic series cycle for improved temperature matching and energy efficiency in compact household refrigerators - Bingqi Li; Yanjun Du; Xudong Ma; Yuting Wu; Che Wang; Jie Lin; Haiqing Guan; Lubing Wang (International Journal of Refrigeration, 2026)

Synergistic effects of lipid degradation and the Maillard reaction: Decoding the flavor formation of charcoal-grilled lamb skewers based on flavoromics, sensomics, metabolomics, and lipidomics - Che Shen; Xinyu Jiang; Jiajin Sun; Meiyi Li; Ran Wang; Yunhui Zhang; Jing Tian; Lizhang Wu; Xiongfeng He; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Immunomodulatory effects of sea buckthorn leaf green tea in cyclophosphamide-induced immunosuppressed mice - Xuhui Kan; Yingjia Yao; Zengshan Chen; Haihong Wang; Chao Che; Quanjin Rong; Fengfeng Du; Jixiang Liu; Xixi Li; Xiaojing Liu; Dongrui Yao (Food Research International, 2026)

Microbiome-metabolomics revealed the mitigative effect of Laminaria japonica fucoidan on high-fat diet induced colonic mucus layer injury - Wanshuang Cai; Dezhao Yang; Huiru Li; Chuqiao Zhang; Hongxia Che; Hongyan Li (Food Bioscience, 2026)

Lattice distortion driving dielectric relaxation frequency and absorbing behavior via electron localization in high-entropy borides - Lili Li; Pingan Chen; Yingli Zhu; Fu Chen; Mengke Qiao; Xiangcheng Li; Renchao Che (Chemical Engineering Journal, 2026)

Synergistic bulk–interfacial regulation for wide-temperature aqueous zinc batteries - Yuanhang Wang; Hui Zhi; Yiming Zhang; Chenglin Miao; Yicheng Tan; Junzhi Li; Jiacheng Zhou; Che Yuan; Mengjie Lu; Wei Han (Chemical Engineering Journal, 2026)

Ventilation and air conditioning design for interconnected large-space underground pumped storage power stations and prediction method for spatial temperature distribution - Lianhua Deng; Jigang Che; Angui Li; Shaofeng Niu; Jing Xiong; Ying Zhang (Building and Environment, 2026)

Deciphering the long-term performance and underlying mechanisms of an engineering-scale anaerobic-anoxic-oxic-anaerobic-vibrating MBR process - Shujuan Che; Weichen Lin; Haojie Ding; Congcong Zhang; Xiangyu Li; Kaichang Yu; Huanhuan Guan; Jie Shi; Yun Yang; Xia Huang (ENGINEERING Environment, 2026)

Geometrically consistent ordinal mixture-of-experts for weight estimation of sows from multi-view point clouds - Qiang Zhai; Longhu Ma; Han Jiang; Li Wan; Yunhan Liu; Yiran Liao; Yifeng Yang; Changmeng Peng; Jinglan Lei; Yong Zhuo; Lianqiang Che; De Wu (Computers and Electronics in Agriculture, 2026)

Interfacial stress mitigation in fusion-bonded reinforced composite pipe joints for offshore energy transportation using functionally graded adhesives - Jingwen Ren; Hanxiang Wang; Feixue Ren; Yanxin Liu; Jiaqi Che; Xin Zhang; Qiang Li; Yongqiang Chen (Ocean Engineering, 2026)

Isolation and functional characterization of goose-derived lactic acid bacteria with growth-promoting and gut health benefits in Sanhua geese - Changsheng Jiang; Wenli Shi; Ji Chen; Weitao Wang; Dandan Fang; Wanji Zhan; Wei Zuo; Chuanyan Che; Ahmed H. Ghonaim; Mengmeng Jin; Qianqian Hu; Keli Yang; et al. (Food Chemistry, 2026)

Functional probiotic Ligilactobacillus agilis Z22 enhances gut–lung immune defense in chickens through TLR2/IL-10–JAK1/STAT3 signaling - Qiao Guo; Yingjie Wang; Jiahui Wu; Zhenghao Che; Shan Lv; Wenqing Zhao; Shiying Li; Jin Liu; Xiuli Peng (Food Bioscience, 2026)

Dynamically structured bubbles enhance energy release performance in solar-driven carbonation reaction - Chao Song; Qiang Guo; Yinshi Li; Jinbo Che; Jiabin Fang; Qiang Xu; Tao Fan; Rui Wang (Chemical Engineering Journal, 2026)

Diurnal variations of organic molecules in atmospheric PM2.5 in urban areas of the Yangtze River Basin, China characterized by UHPLC–Orbitrap MS - Xin Ou; Lijuan Li; Xin Qi; Jiawei Zhou; Hanxiong Che; Zhier Bao; Yiliang Liu; Lingshuo Meng; Xin Long; Xiaojiang Yao; Shumin Zhang; Yang Chen (Atmospheric Environment, 2026)

Depth heterogeneity within surface soils substantially affects microbial abundance, diversity, and co-occurrence patterns - Guanyu Chai; Yuan Du; Zelin Wang; Kaifang Liu; Yuan Chi; Yi Duan; Shuo Ma; Xin Hu; Rongxiao Che; Jianxing Li; Wenjun Liu; Dong Liu (Journal of Soils and Sediments, 2026)

Retraction notice to “Cable-car measurements of vertical aerosol profiles impacted by mountain-valley breezes in Lushan Mountain, East China” [Sci. Total Environ. 768 (2021) 144198] - Jing Duan; Yong Chen; Wenling Wang; Jun Li; Xiaopeng Zhang; Guangxian Lu; Yunfei Che; Shujun Zhong; Shupo Ma; Peng Li; Junling An; Pingqing Fu (Science of The Total Environment, 2026)

Cavitation control by a spanwise obstacle placed near the trailing edge of a pitching hydrofoil - Lu Wang; Xukang Li; Bangxiang Che; Pengzhong Wang; Bin Huang; Dazhuan Wu (Ocean Engineering, 2026)

Quantifying the effects of near-fault fling-step ground motions on seismic performance of offshore wind turbines - Wei Che; Guowei Qin; Yajun Li; Chao Long (Ocean Engineering, 2026)

A dual-stream LSTM–XGBoost framework for mine water inflow forecasting: a case study of the Longfeng coal mine - Wang Hao; Li Bo; Zeng Yi Fan; Liu Pu; Chen Wei; Wang Ze Hui; Che Lu Lu (Journal of Hydrology, 2026)

Dredging changes the controls, pathways and environmental sensitivity of N2O emissions in shallow lakes - Rongwei Xiong; Yong Li; Ming Chen; Zhiyang Zhou; Zhengliang Jiang; Xichen Che (Journal of Environmental Management, 2026)

Global electric vehicle network: Structural patterns and news sentiment - Ling Li; Miaomiao Tao; Suai Che; Stephen Poletti (Journal of Environmental Management, 2026)

Steam-assisted dry reforming of methane over a Ce-doped Ni/calcium aluminate catalyst enabling stable syngas production - Ding Wang; Jiming Liu; Yuchen Che; Hao Yang; Bohao Li; Tong Su; Jinhong Zhang (Fuel, 2026)

Exposure to O3, NO2 and their oxidative potential in relation to decreased fecundability: The potential contribution of inflammatory hematological markers - Bingxue Wu; Zigao Zhao; Yan Zhang; Cai Kong; Yuyan Li; Yishi Jiang; Zhengyuan Xie; Xiangjing Song; Tao Wang; Yan Che (Environmental Research, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

CRISPR/Cas9 mediated knockout of MeSSI enhances resistant starch content without compromising yield in cassava - Xiaohua Lu; Yajie Wang; Yannian Che; Yuheng Li; Baochang Nong; Yujian Ge; Xiangwen Wang; Yuxuan Guo; Ruimei Li; Jiao Liu; Jianchun Guo; Yuan Yao; et al. (Carbohydrate Polymers, 2026)

Continuous Diurnal–Nocturnal Observation of Atmospheric Aerosols: Mechanisms, Challenges, and the Prospects of AI Empowerment - Huizheng Che; Yu Zheng; Lei Li; Ke Gui; Hengheng Zhao; Junli Jin; Xiaochun Zhang; Xiang’ao Xia; Yupeng Wang; Zhiwei Xia; Yucong Miao; Yaqiang Wang; et al. (Journal of Meteorological Research, 2026)

Reduced irrigation and phosphorus redistribution optimizes common vetch–mediated soil metabolic and microbial shifts suppress potato late blight - Ting Che; Shan Sun; Yilei Zhou; Chenxi Wu; Tingting Sun; Kangji Gao; Feng Hu; Huixin Li; Huijuan Zhang; Peiyi Zhao; Li Xu (Agriculture, Ecosystems & Environment, 2026)

When defence mechanisms fail: Multi-omics evidence of antioxidant system collapse in Thymallus grubii liver under acute temperature stress - Xinchi Shang; Xinghua Che; Kai Ma; Huaifa Chen; Lanlan Zhang; Huizhi Sun; Yanjun Li; Meiqi Xing; Wei Xu; Wenhua Wu; Yongquan Zhang (Marine Pollution Bulletin, 2026)

Constructing of astaxanthin-loaded microalgal motor and its effect on ameliorating chronic colitis involving in oxidative stress, gut microbiota, and intestinal barrier - Hongyan Li; Xinwei Gong; Huiru Li; Chuqiao Zhang; Lu Yang; Hongxia Che; Yuchao Gu (Marine Life Science & Technology, 2026)

From spatial expansion to institutional coherence: governance pathways of marine protected areas in island blue economies - Chun-Yi Li; Siou-wun Ji; Yi-Che Shih (Frontiers in Marine Science, 2026)
Island jurisdictions are simultaneously advancing marine conservation and expanding blue economy activities under intensifying climate stress. Although Marine Protected Areas (MPAs) have expanded rapidly in response to global biodiversity commitments, spatial designation alone has not consistently translated into effective governance, policy coordination, or climate resilience. In island settings—where fisheries, maritime industries, and ecological vulnerability intersect— MPAs must operate as integrated governance mechanisms rather than stand-alone conservation zones. This study comparatively examines the governance arrangements of Fiji, Palau, and the Taiwan marine governance system to assess how different institutional arrangements shape the practical implementation of MPAs within broader ocean policy systems. Drawing on spatial MPA datasets (WDPA), biodiversity occurrence records (OBIS), and qualitative analysis of legal frameworks, enforcement structures, and monitoring systems, the research evaluates how institutional coordination, policy integration, and management capacity influence the operational performance of MPAs. The analysis focuses on governance alignment rather than causal ecological attribution, emphasizing how policy design conditions implementation effectiveness. Three governance models emerge: (1) coverage-driven sovereign protection, characterized by large-scale designation with centralized authority; (2) community-nested governance, grounded in local stewardship but limited national coordination; and (3) institutionally integrated governance, where MPAs are embedded within marine spatial planning, regulatory systems, and sectoral marine policies. The comparison demonstrates that institutional coherence—horizontal alignment across marine sectors and vertical coordination across governance levels—plays a more decisive role in policy effectiveness than protected area extent alone. For island blue economies, strengthening MPA performance requires sequencing spatial expansion with investments in enforcement, monitoring, and inter-agency coordination; embedding MPAs within marine spatial planning frameworks; and establishing adaptive policy cycles that connect ecological monitoring to regulatory adjustment. These findings provide transferable policy insights for strengthening governance coherence, enhancing MPA effectiveness, and supporting climate-resilient ocean development in island blue economies.

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Bidirectional interactions among ecosystem services under the Grain for Green Program: Insights from simultaneous equation models - Hailun Che; Zihan Xu; Hualin Li; Ye Liu; Shouhong Zhang; Fan Zhang (Journal of Environmental Management, 2026)

Two-phase thin film flow in the compressor’s clearance considering gaseous cavitation of refrigerant/oil based on a novel CFD approach - Jiachen Li; Hui Zhang; Yongxiang Guo; Tian Zhang; Zibo Zhao; Che Wang; Jianhua Wu (International Journal of Refrigeration, 2026)

Decoding the dynamic formation of bolus: A multimodal fusion and simulation framework for texture perception-regulated oral processing - Che Shen; Xinyu Jiang; Lizhang Wu; Zidong Chen; Zihao Li; Ran Wang; Wenxi Qi; Yi Zhang; Xinying Zhou; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Integrated transcriptomic and metabolomic analyses elucidate the molecular mechanisms underlying quality formation during Rosa acicularis fruit ripening - Wuhua Zhang; Yuli Zhou; Yuexi Du; Man Su; Ziqing Xie; Shuai Li; Jie Dong; Naiyu Zhang; Jiani Duan; DaiDi Che; Aimin Zhou; Jinzhu Zhang; et al. (Food Research International, 2026)

Commentary on “Thermophysical and rheological properties of sorbitol + ([mmim] (MeO)2PO2) ionic liquid solutions: Solubility, density and viscosity” - Kui Wu; Yujiang Ke; Xiaofang Li; Chaohui Che (Food Chemistry, 2026)

Research progress on the characteristics of milk allergens and the effect of Maillard reaction and its assistance treatment on allergenicity - Xiaowen Pi; Tanying Zhang; Jia Cao; Zeyu Peng; Bowen Li; Haozhe Yi; Wanxiang Guo; Jing Che; Chen Wang; Jinshen Chu (Food Chemistry, 2026)

Biosynthesis, extraction, identification, biological activities, and biomedical applications of cephalopod ink melanin - Chunsen Xia; Baolian Jing; Jiaxin Duan; Miaomiao Zhou; Xiaoran Li; Hongyan Li; Hongxia Che (Food Bioscience, 2026)

Long-term protective efficacy and distinct immune responses of live and inactivated vaccines against cryptocaryoniasis in orange-spotted grouper (Epinephelus coioides) - Hai Zhang; Huicheng Wu; Shunli Che; Yuhao Hong; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2026)

Bioconcentration kinetics and underlying mechanisms of tire additives and their transformation products in the fry stage of rainbow trout (Oncorhynchus mykiss) - Mengdi Wang; Hongliang Jia; Jingjing Sun; Danli Luo; Xiaofang Che; Song Cui; Zhaowei Wang; Yi-Fan Li (Environmental Pollution, 2026)

Assessment of quasi-global surface ozone simulations with WRF-chem using multi-dataset evaluation - Lingxia Wu; Lei Li; Lei Zhang; Yadong Lei; Shuhui Liu; Haoling Zhang; Ke Gui; Yu Zheng; Huizheng Che (Environmental Pollution, 2026)

Structure-dependent inhibition of human carboxylesterase 1 by organophosphate esters: integrated in vitro profiling and 3D-QSAR interpretation - Zhuohua Cao; Siyu Men; Zhenhua Li; Gang Liu; Qingying Su; Xinran Chen; Xianhua Che; Hanyong Jin (Chemico-Biological Interactions, 2026)

Vaginal Probiotic Potential of the Nomadic Species Limosilactobacacillus fermentum Under Dysbiotic Vaginal Conditions: Population Genomic Insights and Anti-Pathogenic Efficacy of a Vaginal Isolate VL9 - Yanqing Che; Yixin Mao; Mengjie Li; Xiao Liu; Hongzhou Li; Guodong Yan; He Gao; Xuemei Bai; Zhiwen Sun; Xiaoning Liu; Duochun Wang (Probiotics and Antimicrobial Proteins, 2026)

Elevation‐Dependence of Different Precipitation Phases Concentrations in the Asian Water Tower: Differences in Rainfall and Snowfall Concentration Changes - Yuanlong Tang; Xuemei Li; Tao Che; Dongyang Zhang; Guigang Wang; Huane Duan; Yue Zhang; Chen Yao; Xiaoxiao Jiang; Guojin Pang (International Journal of Climatology, 2026)
Precipitation concentration is a key indicator for characterising spatio‐temporal heterogeneity of precipitation and assessing hydrological responses to climate change. Nevertheless, most existing studies have concentrated on total precipitation, neglecting how different precipitation phases (rainfall and snowfall) exhibit distinct concentration patterns and sensitivities to climatic forcing. This omission has limited understanding of hydro‐climatic processes in high‐altitude regions, where shift of precipitation from solid to liquid (SPSL) strongly modulates water resources and extreme events. Addressing this gap is challenging in the Asian Water Tower (AWT), given extreme topographic complexity, sparse observations, and strong influence of multiple circulation systems. Using ERA5‐Land reanalysis data at approximately 10 km (0.1°) spatial resolution (1980–2023), combined with a validated precipitation phase discrimination method, we investigate phase‐specific precipitation concentration indicators across the AWT. This study provides one of the first region‐wide, phase‐resolved assessments of precipitation concentration in the AWT by jointly quantifying rainfall and snowfall. It further examines their contrasting elevation‐dependent behaviours, extending previous work that focused solely on total precipitation concentration. Rainfall was strongly clustered in summer and exhibited relatively stable trends, whereas snowfall peaked in late winter–spring. Notably, snowfall concentration diverged by elevation, with increasing concentration at lower elevations but decreasing concentration at higher elevations, highlighting phase‐specific sensitivity to warming. Modulation of precipitation concentration by large‐scale circulations was evident. Indices such as ENSO and Indian Summer Monsoon Index (ISMI) significantly influenced seasonal concentration. El Niño conditions were associated with more temporally dispersed rainfall, whereas La Niña conditions enhanced clustering in southern AWT. In contrast, snowfall concentration index (SCI) was positively influenced by cold‐air outbreaks linked to Siberian High and mid‐latitude westerlies. By explicitly contrasting rainfall and snowfall concentration, this study advances beyond previous total‐precipitation analyses and demonstrates a new pathway to identify hydrological instability in alpine regions. Findings advance understanding of precipitation phase dynamics in high‐altitude regions and offer implications for disaster early warning, seasonal water allocation, and climate‐resilient reservoir management in snow‐dominated basins.

Enhanced deep nitrogen removal from low C/N wastewater via manganese-catalyzed iron-carbon micro-electrolysis coupled biological system: performance, mechanism, and microbial adaptability - Hengyuan Liu; Kai Wang; Feng Sha; Haibing Che; Rui Sun; Xiuhua Li (World Journal of Microbiology and Biotechnology, 2026)

Unraveling the multi-scale drivers of the urban thermal environment through interpretable machine learning models - Mingqian Li; Yajing Liu; Shengquan Che; Chunxiao Wang (Urban Climate, 2026)

Urinary Fibroblast Growth Factor-23 and Soluble Alpha-Klotho in Cats with Chronic Kidney Disease - Wei-Che Chen; Wei-Li Hsu; Chao-Chin Chang; Pei-Shiue Jason Tsai; Vin-Cent Wu; Ya-Jane Lee (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Global disparities in 3D urban morphology shaped by building height and distributions - Yangzi Che; Xuecao Li; Ying Wu; Yucong Sun; Bingjie Li; Xiaoping Liu (Science Bulletin, 2026)

Annual global land cover mapping at 30 m resolution from 1985 to 2022 with high temporal consistency - Bingjie Li; Xiaocong Xu; Haoming Zhuang; Honghui Zhang; Yangzi Che; Yue Zheng; Yiling Cai; Xiaoping Liu; Xia Li (Science Bulletin, 2026)

Data-driven optimization of a composite ducted propeller based on a bi-directional FSI method - Xiaoyi An; Chengshan Li; Peng Wang; Huachao Dong; Che Liu; Youjiang Wang (Ocean Engineering, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

An oil shale ash-based Fe3O4@NaY magnetic zeolite with rapid and high removal efficiency for crystal violet - Yu Duan; Qitao Liu; Qian Wang; Yuanjun Che; Hongchen Liu; Fei Li (Journal of Environmental Chemical Engineering, 2026)

Resonant effects of seismicity on substance migration in rock fractures - Zhi-Jie Che; Jia-Qing Zhou; Li-Guo Guo; Fu-Shuo Gan; Hong-Bin Liu; Changdong Li; Yi-Feng Chen (International Journal of Rock Mechanics and Mining Sciences, 2026)

Corrigendum to ‘Coupled effects of glyphosate on soil carbon cycling regulated by dose, time, and environment: A global meta-analysis’ [Environ. Res. 299 (2026), Article 124281] - Yu Chu; Tianhao Che; Xinran Gao; Panxing He; Yang Li; Yu Ma (Environmental Research, 2026)

Coupled effects of glyphosate on soil carbon cycling regulated by dose, time, and environment: A global meta-analysis - Yu Chu; Tianhao Che; Xinran Gao; Panxing He; Yang Li; Yu Ma (Environmental Research, 2026)

A novel artificial air life support system based on liquid oxygen and liquid nitrogen in underground refuge chamber - Haolin Lu; Angui Li; Jigang Che; Yuanqing Ma; Lianhua Deng; Jing Xiong; Changqing Yang; Dingmeng Wu (Energy and Buildings, 2026)

Assessing earthquake-induced displacements of large-scale landslide by in-situ monitoring and discrete element analysis - Meng-Chia Weng; Wei-An Chao; Che-Ming Yang; Tee-Ann Teo; Kuo-Wei Li; Yu-Ting Hsiao (Engineering Geology, 2026)

Multiscale magnetic-dielectric coupling in nano-micro-macro Fe/Fe3O4@C aerogels via confinement strategy for broadband electromagnetic wave absorption - Xianlin Zhan; Mengqiu Huang; Bicheng Li; Ge Ma; Wenbin You; Yun Tang; Lei Wang; Renchao Che (Chemical Engineering Journal, 2026)

Global radiative forcing assessment of brown carbon versus black carbon: Source-specific constraints from compiled observations - Shuhui Liu; Lei Li; Xindan Zhang; Yadong Lei; Haoling Zhang; Yu Zheng; Ke Gui; Hengheng Zhao; Jingrui Ma; Zhili Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2026)

Genome streamlining and functional adaptation of drought-enriched bacteria regulate soil heterotrophic respiration in alpine peatland - Yichang Gao; Yong Li; Zhongqing Yan; Kerou Zhang; Rongxiao Che; Lizhen Cui; Huan Wang; Yuechuan Niu; Enze Kang; Weirong Zhuang; Wenru Zhao; Miaomiao An; et al. (Plant and Soil, 2026)

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Antioxidant Enzyme Activities and Metabolic Responses of the Posterior Gills of Mud Crab (Scylla paramamosain) Under Long-Term Stress in Coastal Chloride-Dominated Low-Salt Saline-Alkali Water - Ziwei Fan; Kangxiang Qin; Fei Wang; Chenxi Che; Yuntao Li; Wenjun Li; Shan Gao; Chunlin Wang; Changkao Mu; Huan Wang (Journal of Ocean University of China, 2026)

Fungal co-cultivation reshapes salt stress adaptation in the cyanobacterium Synechococcus elongatus PCC 7942 - Ting Wang; Yuexuan Wang; Shujuan Wang; Yan Che; Tuanjie Che; Jie Feng; Tingting Li (Algal Research, 2026)

Tetrabromobisphenol A and Cadmium Chloride Induced Hepatic Oxidative Stress and Autophagy Inhibition in Rats - Rongjing Sun; Jing Tian; Li Che; Tianyang Liu; Huibin Jin; Haonan Zhao; Jin Chen; Nianping Zhang; Xi Kang; Luqing Pan; Piaoye Wu; Bei Liu; et al. (Biological Trace Element Research, 2026)

Caffeic acid restores neurogenesis and synaptic integrity under glucolipotoxic stress by suppressing inflammation and pyroptosis - I-Ning Tsai; Xiang-Ning Xie; Ping-En Ko; Yung-Che Tsai; Ching-Chun Chen; Li-Sung Hsu; Chau-Jong Wang (Metabolic Brain Disease, 2026)

NOTCH3 signal activation by its extracellular domain accumulation in an iPSC line newly established from a CADASIL patient - Ruihua Sun; Zhenxiang Zhao; Ningning Che; Ning Liu; Xiaoyi Ji; Anqi Li; Fengyu Wang; Junkui Shang; Jiewen Zhang (Human Cell, 2026)

Physics-informed βVAE-transformer reduced order surrogate model for fast and accurate prediction of offshore natural gas leakage concentration fields - Houjia Xu; Bingcai Sun; Qi Jing; Qianfan Che; Yuntao Li; Yang Cao; Junyao Wu (Ocean Engineering, 2026)

Non–equilibrium K isotope fractionation during alunite precipitation from hydrothermal fluids and the implications - Yuqi Li; Yang Zhang; Xudong Che; Zhimin Tang; Weiqiang Li (Geochimica et Cosmochimica Acta, 2026)

Luteolin-stabilized pickering emulsion for encapsulating Enterococcus hirae: preparation, characterization, and synergistic effects on hyperuricemia - Chengtao Han; Songhao Che; Hui-Min Li; Yan-Yu Chi; Jun-Yan Xiang; Qiuhong Xie; Hongyu Xiang (Food Research International, 2026)

Rapid degradation of sulfamethoxazole with high mineralization rate and energy-efficiency via C@Co/NF anode-activated peroxymonosulfate - Chuangchuang Li; Xiaoxuan Fan; Gengyuan Zhang; Runren Jiang; Chuncheng Chen; Guangbo Che; Wei Jiang; Chunbo Liu (Chemical Engineering Journal, 2026)

Partially etched Ti2AlN/Ti2N/TiN ternary composite as a synergistic catalyst for enhanced hydrogen storage kinetics and cycling stability of NaAlH4 - Chen Jin; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

China's underestimated, characteristic herpetofauna pet trade highlights the importance of global efforts in conservation - Kai Wang; Chenqi Lu; Shuo Qi; Pipeng Li; Robert W. Murphy; Cameron D. Siler; Jing Che (Biological Conservation, 2026)

La-mediated green rust for synergistic nitrogen–phosphorus removal and targeted N2 formation regulated by built-in electric field and spin state - Yibo Zhang; Jun Nan; Chen Liang; Zhencheng Ge; Han Deng; Yanhan Che; Yunhao Pan; Meng Li; Bohan Liu (Water Research, 2026)

Hydrogeology of reservoirs for deep geological storage of saline coal mine drainage in groundwater Basin - Song Du; Zhan Yang; Xiao Zhang; Sheng Tao; Xiang Li; Qiaohui Che; Yinglin Fan; Yan Ding; Zhe Jiang; Yanxin Wang (Journal of Hydrology, 2026)

Built-in electric field constructed by asymmetric electron cloud distribution for facilitating photocatalytic H2O2 production in covalent organic frameworks - Chuanxue You; Yue Zhou; Meiting Yang; Jingyang Li; Bo Hu; Yunchao Ma; Linlin Liu; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

Electrochemical degradation of PFAS treated with synergetic oxidation system reveals structure- and dose-dependence - Yinhui Li; Naiju Che; Minggu Zhang; Chengliang Li (Journal of Environmental Chemical Engineering, 2026)

Valorization of fly ash into hydrophobic mesoporous SiO₂ as a highly efficient and durable antifoaming agent for wet flue gas desulfurization - Fei Wang; Xiaoyan Yan; Xiaoke Li; Jiangtao Meng; Yu Che; Jing Wang; Yuanyuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Influence of free surface on microwave-induced rock fracturing: An experimental and numerical study - Yanlong Zheng; Ziqiang Su; Gaofeng Zhao; Ping Che; Jianchun Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

A new pair of lunar gabbroic meteorites record magma recharge at ∼ 3.0 Ga - Peiyi Li; Yun Jiang; Kai Zhao; Shiyong Liao; Xiaochao Che; Xinru Zhang (Geochimica et Cosmochimica Acta, 2026)

Enrichment mechanism and clean utilization of sodium-iron in high alkali and high iron coal in Beishan coal Mine, Xinjiang - Jiaxin Li; Hongyang Bai; Wenfeng Wang; Hengyan Liu; Kexin Che; Peng Wang; Qingfeng Lu (Fuel, 2026)

Research progress on performance regulation strategies for copper-based nitrate reduction catalysts for ammonia synthesis - Yuru Song; Tan Zhang; Zhikai Che; Jinping Li; Guang Liu (Chemical Engineering Journal, 2026)

In-Depth Water Quality Analysis in Fengle Reservoir, China - Ran Chen; Jiamin Chai; Zhixu Kang; Yan Li; Lili Dong; Liping Qian; Yurong Wei; Xintong Li; Qidi Liu; Yixin Ma; Jun Cui; Shunli Wan; et al. (Water Conservation Science and Engineering, 2026)

The enhanced nitrous oxide emissions are driven by prokaryotic ammonia oxidizers and nirK-denitrifiers under various combinations of nitrogen and rice straw in a paddy soil - Chunyan Wu; Yinxiu Liu; Xu Tang; Tao Sun; Che Tan; Yu Zeng; Yan Li; Chang Yin; Yongchao Liang (Soil Ecology Letters, 2026)

Effects of water table depth and fluctuations on Sphagnum palustre growth and plant community succession in subtropical mountainous Sphagnum peatlands: insights from a microcosm experiment - Ting-Ting Li; Man-Jing Tian; Jie Xu; Lun-Che Wang; Bin-Luo Li; Hui-Hui Sun; Wen-Yi Yang; Zheng-Xiang Wang (Aquatic Sciences, 2026)

Role of NOX4 and GSH in Cadmium-Induced Renal Redox Homeostatic Dysregulation of Rats and APO Intervention Effect Study - Zhaofan Long; Langqiu Wei; Che Wang; Ningxi Wang; Li Song; Qiling Liu; Chuandao Shi (Biological Trace Element Research, 2026)

Phosphorus Enrichment Rewires Viral-Mediated Phosphorus Cycling in Freshwater Ecosystems via Auxiliary Metabolic Genes - Raoqiong Che; Shiying Zhang; Hao Yi; Jun Li; Kaixin Diao; Xiaolong Cui; Hongchen Jiang; Wei Xiao (Journal of Earth Science, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Quantifying the influencing factors on the spatiotemporal patterns of dune activity in the Tengger Desert, Northwestern China - Xuehua Che; Zhuolun Li; Shipei Dong; Jie Luo; Yingyibing Shen; Xue Peng (Geomorphology, 2026)

Quality enhancement of frozen dough steamed bread by Sanxan: A study on multi-stage regulation of gluten-starch matrix - Haojia Zhu; Heqiao Qian; Jie Li; Hanzhang Hao; Ying Huang; Shenying Zhang; Yingxue Che; Mei Liu; Ying Liang; Xueling Zheng; Chong Liu; Limin Li (Food Hydrocolloids, 2026)

Quantitative evaluation of the effects of initial soil salinity, water quality and nitrogen application rate on cotton growth under drip irrigation in arid regions - Chao Ma; Jun Wang; Zheng Che; Jiusheng Li (Field Crops Research, 2026)

Hydraulic characteristics of short-distance fishway and their influence on fish upstream migration behavior - Wei Yang; Liwei Tan; Xianbin Zhang; Xuan Che; Ziyue Zhu; Geng Li (Ecological Engineering, 2026)

Mechanistic insights into Ti3CN MXene-modified NaAlH4: Boosting hydrogen storage kinetics and cyclability - Chen Jin; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; Mi Yan (Chemical Engineering Journal, 2026)

Synergistic CeH2.51/graphene nanointerface engineering for enhanced kinetics and cycling stability of Mg(NH2)2–2LiH - Chen Jin; Haoyuan Zheng; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Magneto-dielectric synergistic engineering in hierarchical Co/CoO@C@RGO microspheres: Asymmetric core-shell design enables ultra-broadband microwave absorption - Haowen Yang; Lei Wang; Qingqing Li; Renchao Che (Chemical Engineering Journal, 2026)

Naringin-loaded metal-organic framework biomimetic hydrogel system mitigates wear particle-induced periprosthetic osteolysis by suppressing aseptic inflammation and osteoblast apoptosis - Chenhao Qiu; Zhenjia Che; Hao Cheng; Huabin Liu; Yuhao Zhang; Jingtao Wu; Chen Li; Jianyou Li; Xiongfeng Li; Xiao Sheng; Hongliang Gao (Chemical Engineering Journal, 2026)

A novel fructan from Atractylodes macrocephala ameliorates ulcerative colitis through gut microbiota-mediated PI3K/Akt signaling - Jiangping Wu; Qiangbao Xu; Yiping Yang; Zhu Yang; Zihan Li; Lingzhi Chen; Yujia Song; Hui Che; Guodong Wang; Qiuyue Lv; Jun Han (Carbohydrate Polymers, 2026)

Low-temperature photothermal catalytic reforming: a promising approach for deep removal of biomass tar towards green fuels synthesis - Tianxiao Yu; Beibei Yan; Jian Li; Yuechi Che; Xiaopeng Jia; Guanyi Chen (Biomass and Bioenergy, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

High-light resistance of the diatom Phaeodactylum tricornutum is enhanced by the addition of alginate-derived oligosaccharides (ADOs) - Xingkai Che; Yongfu Li; Zhendong Li; Benwei Zhu (Journal of Oceanology and Limnology, 2026)

Soil phosphorus dynamics during cropland reforestation - Wenchao Wu; Rongxiao Che; Song Zhang; Yunlong He; Benjamin L. Turner; Dong Liu; Fang Wang; Ting Li; Anquan Xia; Zejin Zhang; Tong Li; Guangbing Xu; et al. (Agriculture, Ecosystems & Environment, 2026)

Reply to Wang, L.; Fan, B. Golden Pompano in China Is Trachinotus anak, Not T. ovatus. Comment on “Li et al. DNA Barcode and Correct Scientific Name of Golden Pompano, an Important Marine Aquaculture Fish Species in China. Fishes 2025, 10, 129” - Ang Li; Changting An; Huan Wang; Shuai Che; Shufang Liu; Zhimeng Zhuang (Fishes, 2026)
In a recent study [...]

A hybrid assembly mechanism employs nonreducing polyketide synthase-like logic for partially reduced polyketide formation - Xianyan Zhang; Chuanteng Ma; Ziguang Deng; Xingtao Ren; Kaijin Zhang; Wenxue Wang; Luning Zhou; Yongchun Zhu; Guojian Zhang; Qian Che; Tianjiao Zhu; Hongan Long; et al. (Marine Life Science & Technology, 2026)
Fungal iterative type I polyketide synthases (iPKSs) are commonly classified into nonreducing (NR-), partially reducing (PR-), and highly reducing (HR-) polyketide synthases based on their assembly mechanisms and domain structures. These iPKSs have been considered functionally and evolutionarily distinct, characterized by clear boundaries. However, emerging genomic analyses suggest that the diversity of iPKSs in fungi is far from fully understood. Here, we describe the discovery and characterization of PbPKS1 from a marine-derived fungus Penicillium brocae HDN12-143, which exhibits an atypical domain organization arranged as KR-KS-AT-PT-ACP 1 -ACP 2 -CMeT-TE. Heterologous expression of PbPKS1 resulted in the production of two monohydroxybenzoic acids and two pyrones. In vivo and in vitro characterizations demonstrated that PbPKS1 has the capability to synthesize Cα-methylated partially reducing polyketides, yet involved a NR-PKS-like assembly mechanism, featuring a product template (PT) domain for aldol cyclization and a C-terminal thioesterase (TE) domain for product release. Phylogenetic analysis suggests that PbPKS1 belongs to a non-canonical PR-PKS (nPR-PKS) family, which is a minor grouping across the fungal kingdom, and possibly evolved from an NR-PKS through gene recombination. The discovery of nPR-PKS not only expands the diversity of iPKSs but also provides new insights into the evolutionary development of fungal iPKSs.

Effects of high-pH saline-alkaline water on tissue structure, osmoregulation, antioxidant capacity, and metabolic activity in mud crab Scylla paramamosain Estampador, 1950 - Yuntao Li; Cunhong Chen; Zihui Li; Jingli Yang; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; et al. (Aquaculture, 2026)

Transcriptomics reveals that curcumin alleviates alkalinity stress-induced brain damage and neurotoxicity - Xinchi Shang; Zhaoqi He; Xinghua Che; Meiqi Xing; Longwu Geng; Lu Xing; Lanlan Zhang; Xiaohua teng; Wei Xu; Jianhong Li (Aquaculture, 2026)

Shionone ameliorates pulmonary fibrosis by activating mitophagy via PINK1-Parkin pathway - Yijia Su; Qiang Fu; Xilin Wu; Xianhua Che; Zhe Jiang; Xuezheng Li (Toxicology and Applied Pharmacology, 2026)

Efficient removal of bisphenol A from complex environments by Fe-Mn oxides loaded biochar: An innovative perspective of utilizing co-existing Cr(Ⅵ) - Naiju Che; Yinhui Li; Minggu Zhang; Longlin Wang; Chengliang Li (Journal of Environmental Management, 2026)

Mechanistic insights into product distribution and bromine fixation during co-pyrolysis of cattle manure with organic components of printed circuit boards - Wenqi Guan; Dong Liang; Che Zhao; Danni Li; Shuxiao Wang; Rui Shan; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2026)

Reprocessing of lunar crust at ∼4.3 Ga inferred from in situ U-Pb isotopic and trace element investigation of Northwest Africa 11479 - Jingyou Chen; Shaolin Li; Shiyong Liao; Jian Chen; Alexander Nemchin; Katherine H. Joy; Xiaochao Che; Weibiao Hsu; Menghua Zhu (Geochimica et Cosmochimica Acta, 2026)

Multifactorial impacts on ash behaviors during oxy-fuel co-combustion of semi-coke and biomass - Jinping Zhang; Wenwen Wei; Haichen Zhao; Siyuan Li; Jingchun Shen; Defu Che; Lei Chen (Fuel, 2026)

Comparative study on microwave and conventional pyrolysis characteristics of Tar-Rich coal - Xiaole Huang; Xing Ning; Jingwen Mao; Peiqi Li; Jiyun Ren; Qidong Yang; Lei Deng; Defu Che (Fuel, 2026)

Sepia pharaonis ink derived melanin ameliorated high-fat diet induced lipid dysmetabolism: Insights from microbiome and hepatic transcription - Miaomiao Zhou; Chunsen Xia; Baolian Jing; Jiaxin Duan; Hongyan Li; Hongxia Che (Food Research International, 2026)

Effects of recombinant carrot antifreeze protein concentrations on frozen dough and bread: Insights into dynamic changes of water and ice crystals - Ying Huang; Shenying Zhang; Haojia Zhu; Caiyun Liu; Zichen Huang; Hanzhang Hao; Yingxue Che; Mei Liu; Ying Liang; Xueling Zheng; Chong Liu; Limin Li (Food Chemistry, 2026)

Micronutrient uptake, partitioning and accumulation in cotton under drip irrigation with mulch in response to phosphorus application in root morphology changes - Yue Ma; Zupeng Ye; Wei Li; Juanhong Wang; Qingxuan Che; Qinghui Wang; Bolang Chen; Gu Feng (Field Crops Research, 2026)

Organic substitution for synthetic fertilizer mitigates the negative effects of warming on soil quality, greenhouse gas emissions, and soybean yields - Xiaoyu Wang; Jiangsen Chu; Mengyou Zhang; Mingjun Hou; Ke Zheng; Leili Lin; Zhengjun Yan; Xiaoxiao Li; Zhao Che; He Song; Gong Wu (Field Crops Research, 2026)

Built-in electric field-governed ion sieving in interlayer-engineered TiN–MXene heterostructure anodes for dominant aqueous zinc-ion storage - Inaam Ullah; Ayesha Irfan; Mai Li; Chenxi Li; Samira Saddique; Salamat Ali; Waqar ul Hasan; Muhammad Irfan; Caiyuan Xiong; Jinbo Ming; Qinglin Deng; Chunrui Wang; et al. (Chemical Engineering Journal, 2026)

Long-term retrieval and analysis of aerosol components and optical properties in Tianjin, China: Insights from GRASP/component approach and sun-photometer observations (2014–2024) - Xindan Zhang; Lei Li; Yu Zheng; Jibiao Zhu; Tiantao Cheng; Ke Gui; Yuanxin Liang; Shuhui Liu; Haoling Zhang; Jingrui Ma; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2026)

Discovery and optimization of AAK1 inhibitors based on 1H-indazole scaffold for the potential treatment of SARS-CoV-2 infection - Zi Hui; Haowen Deng; Yueying Xu; Yuan Gao; Chenfeng Zhai; Nian-Dong Mao; Hao Che; Zhen Li; Yuting Zhang; Hang Zhang; Tian Xie; Xiang-Yang Ye (Molecular Diversity, 2026)

Functional Roles and Regulatory Factors of Histidine-Related Compounds in Skeletal Muscle Metabolism of Teleosts with Distinct Swimming Strategies - Huan Wang; Jiefeng Li; Ang Li; Changting An; Shuai Che; Shengcong Liu; Shufang Liu; Zhimeng Zhuang (Marine Biotechnology, 2026)

Numerical prediction of progressive failure in earthquake-damaged slopes under rainfall using MPM - Chao Su; Ailan Che; Ganglie Yuan; Hanxu Zhou; Xiaowei Li (Landslides, 2026)

Adaptive filtering suppression method of substation environmental noise based on fast transversal least mean square algorithm - Y. Gong; H. Fan; X. Wei; K. Liu; X. Xu; K. Che; D. Li (International Journal of Environmental Science and Technology, 2026)

Potential role of oocyte-intrinsic fatty acid synthesis in ovarian development of the bigfin reef squid Sepioteuthis lessoniana - Hau-Wen Li; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2026)
In most animals, excess dietary energy is stored as lipids in specialized tissues, such as the liver in vertebrates or the hepatopancreas and fat body in invertebrates, which function as energy reservoirs for reproduction. In cephalopods, however, dietary energy is rapidly mobilized from the digestive gland for growth rather than stored for reproduction. How excess energy is allocated for reproduction activity in cephalopods remains largely unclear. Lipogenesis is initiated by acetyl-CoA carboxylase (ACC), which converts acetyl-CoA derived from dietary carbon sources into malonyl-CoA; subsequent synthesis of saturated fatty acids is catalyzed by fatty acid synthase (FAS). Using the bigfin reef squid as a model, we investigate the role of fas in female development. fas mRNA was highly expressed in ovaries but weak in other tissues, including the lipid-rich digestive gland. fas showed female-biased expression in gonads, with level highest in juvenile ovaries and progressively decreasing to their lowest in mature ovaries. Expression was also high in primary and multiple follicular oocytes but declined in later stages. In situ hybridization and immunohistochemistry confirmed fas mRNA and protein localization in oocytes, particularly in primary and multiple follicular oocytes. In vitro ovarian culture further showed that inhibiting FAS activity enhanced somatic cell proliferation. Together, these findings suggest that squid ovary is a primary site of fatty acid synthesis, supporting early oocyte growth and membrane biogenesis in the absence of dedicated lipid storage tissues. The decline of FAS activity during oogenesis, and the associated reproduction in fatty acid synthesis, may act as a regulatory signal to promote somatic cell proliferation.

SALL4-targeted therapeutic peptide PEN-FFW suppresses PD-L1 and enhances CD8⁺ T cell cytotoxicity via regulating PI3K/AKT signaling in breast cancer - Renyuan Xu; Haomiao Lan; Li Zhang; Hongying Che (Immunologic Research, 2026)

First report of marine leech Limnotrachelobdella okae infestation in miiuy croaker (Miichthys miiuy): An emerging threat to Chinese mariculture - Shunli Che; Zequan Mo; Hai Zhang; Haoran Tang; Xueming Dan; Yanwei Li (Veterinary Parasitology, 2026)

(E)-2-((E)-oct-2-en-1-ylidene)-hydrazine-1-carbothioamide inhibited the growth of Penicillium italicum by disrupting mitochondrial energy metabolism - Yafeng Li; Yonghua Zhang; Liangliang Gao; Jing Liu; Qiuli Ouyang; Jinxin Che; Nengguo Tao (Postharvest Biology and Technology, 2026)

CYP51B is involved in the prochloraz resistance of two newly isolated Penicillium italicum strains from citrus fruit - Tengjie Li; Yun Zhou; Jing Liu; Yue Chen; Jinxin Che; Nengguo Tao (Postharvest Biology and Technology, 2026)

Multi-proxy reconstruction of Holocene sedimentary evolution in the Yangtze Delta: Climatic forcing, sea-level oscillations, and diagenetic overprint - Zixuan Che; Chunzhu Chen; Lisi Wei; Wenwei Zhao; Quan Li; Yunpeng Yang; Hanfei Yang; Zhigang Wang; Xiaojian Zhang; Ximing Zhang; Shutong Yang; Huan Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Highly isolated interlayer Co-N4 fixed by heptazine promotes peroxymonosulfate activation to selectively generate singlet oxygen - Xiang Li; Bo Liu; Shi Zhou; Chunbo Liu; Guangbo Che; Wei Jiang (Journal of Hazardous Materials, 2026)

Engineering odor control in algal foods: Machine learning for quality enhancement - Yilan Sun; Qinhua Zhang; Hongkun Lin; Juehan Lu; Huiyue Zhang; Che Su; Shiguo Huang; Jie Pang; Xiaolin Li (Journal of Food Engineering, 2026)

Sustainable soil management in acidic paddy fields: liming and biochar application reduce greenhouse gas emissions while enhancing rice yields - Gong Wu; Xiaoyu Wang; Xing Wei; Mengyou Zhang; Jiangseng Chu; Mingjun Hou; Leili Lin; Yang Chen; Zhao Che; Xiaoxiao Li; Can Zhang; He Song (Journal of Environmental Management, 2026)

NO heterogeneous reduction during oxy-fuel combustion of semi-coke: The role of high-temperature rapid gasification - Pengqian Wang; Chenxi Zhang; Xingpeng Li; Jiaojiao Zhang; Yi Liu; Yongbo Du; Chang’an Wang; Defu Che; Bo Bai (Fuel, 2026)

Removal of tetracyclines and estrogens with simultaneous ammonia retention in swine wastewater by aerobic treatment under short sludge retention time - Yi Wu; Weizhe Sun; Linyan Yang; Kai Li; Chengdan Che; Ben Wang (Environmental Research, 2026)

FeSe2 graphite intercalation compounds derived from spent graphite with spatial confinement effect enable high-performance sodium storage - Jiahao Yang; Chong Xu; Zizheng Zhou; Guang Ma; Shuang Liu; Dongyuan Zhang; Gong Cheng; Junjie Fu; Sai Che; Yan Jia; Yongfeng Li (Chemical Engineering Journal, 2026)

Mo-doped NiCo-LDH@Ti3C2Tx-N MXene heterostructures for coin cells and 3D-printed wearable micro-supercapacitors - Jiayi Shen; Mai Li; Haotian Hu; Yifeng Cheng; Ayesha Irfan; Chenxi Li; Qinglin Deng; Limin Wu; Renchao Che (Chemical Engineering Journal, 2026)

Soft-chemical topotactic pathway to (001)-faceted hollandite K-Fe-Ti oxides with accelerated Li+ migration - Xing Wang; Ling Che; Zihao Li; Zhigao Chen; Xingang Kong; Kun Zhang; Keyu Xie (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Oxygen vacancy enriched alumina supported Ni nanocatalysts for highly selective acetylene hydrogenation - Hedan Yao; Yuanjun Che; Dong Huang; Yi Qin; Yuchen Niu; Wenhong Li; Liuyi Pan; Dong Li (Chemical Engineering Journal, 2026)

Experimental and numerical investigations of heavy gas leakage in long and narrow spaces - Yuanqing Ma; Angui Li; Tianqi Wang; Ying Zhang; Changqing Yang; Jigang Che; Yifan Wang; Dingmeng Wu (Building and Environment, 2026)

Comparative impact of surface reflection models on aerosol component retrieval - Shuhui Liu; Lei Li; Xindan Zhang; Cheng Chen; Haoling Zhang; Ke Gui; Yu Zheng; Jingrui Ma; Huizheng Che (Atmospheric Research, 2026)

Decoding adenomyosis pathogenesis using an assembloid model - Yiliang Xu; Tao Cheng; Jianzhang Wang; Zhiruo Qiu; Xiaohong Guan; Yayuan Yu; Jiacheng Shen; Fangfang Xu; Xiaohong Jiang; Dandan Bai; Mingzhu Wang; Shuyan Mei; et al. (Science China Life Sciences, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Novel antifungal talaroenamine L with unusual leptosphaeronyl moiety from marine-derived Talaromyces sp. HDN17-428 via HDACi elicitation - Komal Anjum; Luning Zhou; Khizar Hayyat; Xiaofei Huang; Jiaxiang Wang; Guojian Zhang; Tianjiao Zhu; Qian Che; Dehai Li (Natural Product Research, 2025)

Sub-metre surface water mapping using Sentinel-1/2 with integrated super-resolution and deep learning - Jie Song; Jinyan Tian; Lin Zhu; Bingfeng Zhou; Xinyuan Qu; Che Wang; Niu Luo; Zhenxin Zhang; Lin Guo; Mingliang Gao; Xiaojuan Li; Huili Gong (International Journal of Remote Sensing, 2025)

Quantifying the sources of REE in the deep Philippine Sea: Insights from numerical modeling and field observations - Hong Che; Yi Zhong; Wenkai Guan; Qian Liu; Panfeng Li; Xue Ding; Bangqi Hu (Progress in Oceanography, 2025)

Increased sensitivity of snow phenology to temperature in unstable snow regions since 1990 - Qunqun Li; Xufeng Wang; Wei Wei; Zongxing Li; Tao Che (Journal of Hydrology, 2025)

Reconstructed precipitation isotopes in China during the past six decades based on machine learning - Shengjie Wang; Yanqiong Xiao; Yuqing Qian; Hongyang Li; Cunwei Che; Xiaofan Zhu; Mingjun Zhang (Journal of Hydrology, 2025)

Anthraquinone sites engineering of covalent organic frameworks enables efficient and selective 1O2 generation via directed oxidation of peroxymonosulfate - Yuzheng Wu; Jinyi Tan; Zifan Li; Luwen Liang; Bing Chen; Xinwen Ou; Shan Yao; Guiquan Che; Youqun Wang; Bin Han (Journal of Hazardous Materials, 2025)

Identifying biomarkers for arsenic exposure-induced nonalcoholic fatty liver disease: An integrated proteomics, metabolomics, and machine learning approach - Yiqiong Sun; Fuping Li; Weizhen Hua; Zhenbin Che; Meiping Tian; Yan-Yang Lu; Qingyu Huang (Journal of Hazardous Materials, 2025)

Long-term substitution of chemical fertilizer with organic manure enhances the activity and autotrophic growth of ammonia-oxidizing archaea and comammox nitrospira in paddy soil - Chunyan Wu; Xu Tang; Che Tan; Tao Sun; Yu Zeng; Yinxiu Liu; Yingxia Liu; Yan Li; Yongchao Liang; Chang Yin (Journal of Environmental Management, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Hydrological connectivity associated with salinity mediates wetland vegetation pattern and productivity in estuary - Bo Pang; Chunguang Che; Changzhi Yang; Tian Xie; Baoshan Cui; Yeling Liu; Qing Wang; Yuming Lu; Yina Li; Fang Gao (Journal of Environmental Management, 2025)

Enhanced cobalt removal through coupled ultrasonic and oxygen potential regulation: A novel process study - XiaoQian Che; Jing Chen; WanTao Ning; Libo Zhang; ChuanYu Li; Jing Li; BaoXin Liu; JunChang Liu (Journal of Environmental Chemical Engineering, 2025)

Progress in the study of the emission characteristics of intermediate and semivolatile organic compounds from motor vehicles - Xianbao Shen; Hongwei Ni; TianTian Lv; Zhiliang Yao; Hongqian Che; Xuewei Hao; Bobo Wu; Xinyue Cao; Xin Li; Qi Zhou (Journal of Environmental Sciences, 2025)

Mechanism of anomalous “internal subsidence and peripheral uplift” in a salt mine goaf: A multi-source validated superposition of poroelastic uplift and mining-induced subsidence - Ahu Zhao; Yinping Li; Xilin Shi; Shefeng Hao; Zengguang Che; Kun Yang; Mingnan Xu; Hongling Ma (Geomechanics for Energy and the Environment, 2025)

Nontargeted metabolomics combining with intestinal microbiota revealed the potential mechanisms of DHA/EPA - acetylated astaxanthin esters in regulating the abnormal lipid metabolism - Xiaoran Li; Baolian Jing; Chunsen Xia; Xiyu Wang; Xing Qiao; Tiantian Zhang; Hongyan Li; Hongxia Che (Food Research International, 2025)

Dual mechanisms of Vitisin A in managing alcoholic liver disease: Inhibition of lipogenesis and complement activation - Yuanqin Zhu; Huilin Deng; Jia Liu; Xusheng Li; Xin Huang; Zhaodi Che; Weibin Bai; Rui Jiao (Food and Chemical Toxicology, 2025)

Efficient removal of Escherichia coli in pig farm wastewater and its associated tetA antibiotic-resistance genes by Bi nanosphere-loaded graphitic carbon nitride - Jingshuang Zhang; Gengyuan Zhang; Mingao Li; Yidan Zhang; Jinqiao Li; Li Wang; Guangbo Che; Qianyu Liu; Chunbo Liu (Chemical Engineering Journal, 2025)

Cell-supporting cytoskeletons and phagocytic acquisition of compatible solutes emerge as common strategies for high-salt adaptation in different ciliates - Fengchao Li; Wenying Zhang; Shuai Luo; Ning Ma; Jing Zhang; Weiwei Qin; Che Hu; Xinxin Gao; Yuan Xiao; Chuanqi Jiang; Xiaocui Chai; Qiukun Wang; et al. (Science China Life Sciences, 2025)

Natural and anthropogenic drivers of salinization in the Bohai Rim: Mechanisms and remediation through pine needle amendments - Baijun Shang; Feng Wang; Tong Li; Zhihong Xu; Bernhard Wehr; Yash P. Dang; Rongxiao Che; Lizhen Cui; Jintong Liu; Hui Gao; Shuhui Yu; Tonggang Fu (Journal of Soils and Sediments, 2025)

Genome-wide analysis of AHP genes in soybean and the role of GmAHP10 in improving salt stress tolerance - Lingfang Cao; Jinlong Cao; Li Wang; Jianjun Wang; Zhijun Che (Functional & Integrative Genomics, 2025)

Regional collaborative data harmonization: Building the next generation of global observations - Stephanie D. Jurburg; Clara Arboleda-Baena; An Xie; Rongxiao Che; Tida Ge; Yuyi Yang; Yanjiang Cai; Yongyu Zhang; Gang Li; Xin Sun (Soil Ecology Letters, 2025)

Geochemical Compositions and Transport Patterns of Surface Sediments from the Malacca Strait - Lina Ai; Shengfa Liu; Hui Zhang; Peng Cao; Xue Li; Wenjing Qi; Kaikai Wu; Che Abd Rahim Mohamed; Xuefa Shi (Journal of Ocean University of China, 2025)

Assessment of AOD Simulation by Assimilating Himawari and MODIS Products - Zhilin Wang; Yarong Li; Jianjun He; Wei Tian; Tie Dai; Hong Wang; Huizheng Che (Journal of Meteorological Research, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Evaluation of the working performance of different digging shovels based on the maize root-soil complex model - Hailong Che; Hua Zhou; Zhengzhong Li; Xian Wang; Xianliang Wang; Zhongcai Wei; Yanjun Li; Yinping Zhang (Biosystems Engineering, 2025)

Climate teleconnections among the Earth’s three poles - Anmin Duan; Xin Li; Wenting Hu; Tao Che; Jun Hu; Yuzhuo Peng; Chao Zhang; Die Hu; Yuheng Tang; Zhulei Pan; Qilu Wang; Guoxiong Wu (Science Bulletin, 2025)

Design and characterisation of the out-of-plane dielectric elastomer generator for wave energy harvesting - Xi Wang; Jinxin Wang; Tianyou Zhang; Jung-Che Chang; Siqian Li; Yao Zhang; Tianyi Zeng; Xin Dong (Ocean Engineering, 2025)

Outbreeding of isofemale lines as a candidate approach to improve the quality of thelytokous Wolbachia-infected line of the egg parasitoid, Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae - Hong-Yu Liang; Ying Shan; Qian-Jin Dong; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Invertebrate Pathology, 2025)

Preparation and characterization of glutamine/chito-oligosaccharide modified zein nanoparticles: Controlled release naringin and anti-diabetes - Yiyan Guo; Mingze Xu; Jiapeng Chen; Jingfeng Che; Wenqing Zhu; Yuxin Zheng; Wanting Huang; Wenjun Dai; Hong Chen; Limin Zhai; Li Zhang; Yan-Qing Guan (Food Chemistry, 2025)

The immunomodulatory effects of yeast glycoprotein in sea cucumber (Apostichopus japonicus) against skin ulceration syndrome induced by Vibrio alginolyticus - Wan Zhang; Jian Che; Xiaowen Sun; Bilal Murtaza; Tingfang Li; Xiaoyu Li; Lili Wang; Yongping Xu (Fish & Shellfish Immunology, 2025)

Dynamic relationships of antibiotic resistomes and greenhouse gas-functioning microbes across diverse habitats - Meiping Chen; Lu Song; Chen Ye; Hans-Peter Grossart; Yuyi Yang; Siyue Li; Hao Liao; Yu Gong; Rongxiao Che; Quanfa Zhang (Environmental Research, 2025)

Investigation of the impact of local tumor phenolic-chemistry for dual starvation and vaccination therapy - Jingsong Lu; Zhenhu Guo; Sumei Chen; Ying Li; Xin Xu; Jing Yu; Shenglei Che; Guifeng Zhang; Wensheng Xie; Yen Wei; Lingyun Zhao (Chemical Engineering Journal, 2025)

Synergistic ferroptosis-immunotherapy nanoassembly via PROTAC-mediated SLC7A11 degradation and trisulfide-driven glutathione depletion for enhanced antitumor efficacy - Zhenjie Wang; Yuehua Wang; Yilan Dai; Wenjia Zhang; Chunmei Luo; Siyao Che; Dixian Luo; Jiasi Zhang; Li Deng; Zhiqiang Yu (Chemical Engineering Journal, 2025)

Long-term variations in aerosol optical properties in Beijing: insights from diurnal and nocturnal continuous measurements - Shiya Peng; Yu Zheng; Lei Li; Ke Gui; Jibiao Zhu; Shuhui Liu; Haoling Zhang; Hujia Zhao; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2025)

Assessing Spatiotemporal Characteristics, Health Impacts and Related Economic Losses of PM2.5, PM10 and O3 in Beijing-Tianjin-Hebei Region from 2015 to 2020 - Ran Gao; Qin Li; Yanping Zhang; Fei Che; Xiaorui Zhang; Yijie Wang; Yijun Zhang; Xite Zheng; Quanmei Li; Fengyi Huang; Chuning Luo; Wanqi Liu; et al. (Environment, Development and Sustainability, 2025)

Single-cell transcriptome analysis highlights a critical role of ATG5 for endothelial cells in diabetic nephropathy - Yun Zhang; Lishuang Che; Hanyuan Gao; Quanzuan Zeng; Jiequn Zhang; Yanling Zheng; Yuangen Li; Xiaoqing Chen (Human Cell, 2025)

A lightweight method for apple disease segmentation using multimodal transformer and sensor fusion - Yihong Song; Manzhou Li; Zizhe Zhou; Jiahe Zhang; Xiangge Du; Min Dong; Qinhong Jiang; Che Li; Yuantao Hu; Qiulin Yu; Dongmei Wang; Hegan Dong; et al. (Computers and Electronics in Agriculture, 2025)

Urinary phthalate metabolites associate with blood levels of estrogen quinone-derived hemoglobin adducts in Taiwanese pregnant women - Shu-Li Wang; Dar-Ren Chen; Sheng-Yen Hsu; Chia-Wei Liu; Che Lin; Chien-Wen Sun; Pen-Hua Su; Ying-Chih Tseng; Po-Hsiung Lin (Toxicology Letters, 2025)

A new generation aerosol optical depth dataset based on AVHRR data over China from 1981 to 2000 - Yahui Che; Jie Guang; Yong Xue; Gerrit de Leeuw; Lu She; Linlu Mei; Xingwei He; Ling Sun; Zhengqiang Li (Remote Sensing of Environment, 2025)

Shortened thawing and freezing intervals in the northern hemisphere since 1990 from sites observations and remote sensing - Yanpeng Yang; Xufeng Wang; Zongxing Li; Tonghong Wang; Tao Che (Remote Sensing of Environment, 2025)

Evolution mechanism of thermo-mechanical properties and microstructure of foamed cement regulated by water-based drilling cuttings content - Lidi Huang; Jieran Che; Wei Jiang; Xingyu Li; Qing Li; Shijie Fan; Yandong Liu (Process Safety and Environmental Protection, 2025)

Biaxially stretched high temperature proton exchange membranes deriving from carbon black doped polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene - Xinna Gao; Niuniu Zhang; Chunyu Li; Wantong Zheng; Wenwen Ding; Quantong Che (Process Safety and Environmental Protection, 2025)

The expansin-like gene StEXLB1 plays a role in potato defence against bacterial wilt - Dan Liu; Jiaqi Wang; Yexing Feng; Meng Luo; Zhixiang Xing; Yunzhu Che; Chong Du; Biao Zhao; Tianshuai Qi; Xiaocan Zhao; Fumeng He; Xu Feng; et al. (Plant Science, 2025)

Mapping snow cover frequency at 30 m for studying seasonal variations and topographic controls on the Tibetan Plateau - Guigang Wang; Tao Che; Liyun Dai; Yanxing Hu; Jun Wu; Saiyao Meng; Chuilei Kong; Jing Wang; Dongdong Feng; Shijie Wang; Xuemei Li (Journal of Hydrology, 2025)

Synergistic control of sludge bulking and pollutant removal using acid-treated zeolite molecular sieves - Xiaoya Jiang; Lingyu Liu; Tongyu Che; Xiushan Zhuang; Fang Liu; Shiwen Li; Shengyuan Wang (Journal of Environmental Chemical Engineering, 2025)

Efficient removal of benzotriazole in a bioretention column by porous carbonized wood from urban stormwater - Lin Cong; Mingchen Gao; Meipeng Jian; Fuguo Qiu; Yongjian Che; Xiaoran Zhang; Ziyang Zhang; Chaohong Tan; Haiyan Li (Journal of Environmental Chemical Engineering, 2025)

Unveiling the roles of nitrogen species and concentration in switching Synechocystis growth and metabolites secretion in a photobioreactor - Qian Li; Yingxin Chen; Xinyi Huang; Jingxian Che; Xinyi Zhang; Yun Zhou (Journal of Environmental Chemical Engineering, 2025)

Antioxidant and anti-inflammatory properties of Xianju wheat paste: A traditional condiment with functional food potential - Jinsong Che; Yi Zhang; Shida Li; Xiujuan Li (Food Research International, 2025)

Environmental nano-particulates induced pre-implantation embryonic toxicity in pluripotent stem cell-derived blastoids - Gaojing Liu; Yayuan Li; Xiuyun Liu; Wei Wang; Xiao Wen; Yange Che; Qiu Tu; Bo Zhao (Environmental Pollution, 2025)

Advanced anion exchange membrane for electrodialysis application based on quaternized poly (phthalazinone ether sulfone) - Fanchen Sun; Qian Liu; Zijian Li; Xuefu Che; Lin Zhuo; Yiping He; Guanwen Huang; Kang Niu; Shouhai Zhang; Xigao Jian (Desalination, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Sulfur doping of CoFe-LDHs for pseudocapacitive storage - Xinrui Qiang; Bingzhe Jia; Lei Wang; Jiarui Li; Jiale Wang; Haibo Che; Yichi Liu; Zhiqiang Li; Xinming Wu; Xiaozhou Feng (Chemical Engineering Journal, 2025)

Factors influencing the relationships between hourly visibility and aerosol optical depth in China—implications for hourly aerosol optical depth retrievals using automatic visibility observations - Nanxuan Shang; Ke Gui; Tiantao Cheng; Hengheng Zhao; Xutao Zhang; Wenrui Yao; Yu Zheng; Lei Li; Yurun Liu; Hong Wang; Zhili Wang; Huizheng Che; et al. (Atmospheric Environment, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Analysis of crop leaf area index, leaf chlorophyll content, and canopy chlorophyll content based on deep learning and hyperspectral remote sensing - Mengdie Leng; Yang Liu; Bing Li; Yinchao Che; Haikuan Feng; Meiyan Shu; Xin Xu; Hongbo Qiao; Jibo Yue (International Journal of Remote Sensing, 2025)

Estimating carbon fluxes over North America using a physics-constrained deep learning model - Bin Fan; Hankui K. Zhang; Zhongbin B. Li; Jingfeng Xiao; Xianghong Che; Zhihua Liu; Gustau Camps-Valls; Jing M. Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Involvement of the PINK1/Parkin signaling pathway in 4-vinylcyclohexene diepoxide-induced ovary toxicity in rats - Yue Che; Xiaozhu Wang; Qian Li; Xiyi Peng; Zhen Liu; Wenhui Xu; Mei Jiang; Ting Wang; Jian Gao; Weiling Wang (Food and Chemical Toxicology, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

Corrigendum to “Modulating the density of Co3N/CFs active site by optimizing the micro-structure for overall water splitting electrocatalysis” [Chem. Eng. J. 515 (2025) 163505] - Qiusen Liu; Tingzheng Fu; Hongbiao Xiao; Ye Yu; Zhiqing Che; Yixing Zhang; Anran Chen; Mian Li; Tingting Liu (Chemical Engineering Journal, 2025)

Standard strategy for developing multicomponent nanopesticides: From gene function analysis to co-delivery nano-platform construction - Qinhong Jiang; Min Dong; Lin Che; Che Li; Xian Zhang; Meizhen Yin; Jie Shen; Shuo Yan (Chemical Engineering Journal, 2025)

Bi-layered cellulose-based aerogel with photothermal and photocatalytic dual functions for integrated solar-driven desalination and Cr(VI) reduction - Guodong Tian; Chao Duan; Shasha Che; Yan Li; Kang Yang; Jinyu Guo; Yuxin Zhou; Yijian Wen; Yonghao Ni (Chemical Engineering Journal, 2025)

Multi-biomimetic cellulose-based regenerated fibers from scalable wet spinning for ultrahigh-efficiency rate fog harvesting - Chao Duan; Yuanmei Liu; Jinyu Guo; Yan Li; Yijian Wen; Yiyang Che; Xiaoshuang Liu; Kang Yang; Yonghao Ni (Chemical Engineering Journal, 2025)

Bimetallic ion crosslinked hydrogels sequentially releasing immunomodulatory factors and osteogenic factors to promote bone integration of 3D printed titanium alloy prostheses - Xiao Sheng; Zhenjia Che; Chuncheng Shen; Jingtao Wu; Chenhao Qiu; Chenjie Tan; Junjie Mao; Bo Li; Hang Yu; Jianyou Li; Wei Liu; Chen Li; et al. (Chemical Engineering Journal, 2025)

High-density magnetic-carbon interfaces in NiCu@C heterojunction toward broadband electromagnetic wave absorption - Zhikai Yan; Mengqiu Huang; Longjun Rao; Wenbin You; Biao Zhao; Lei Wang; Limin Wu; Ruixuan Zhang; Wei Li; Renchao Che (Chemical Engineering Journal, 2025)

Integrated transcriptomics, metabolomics, and histopathology reveal molecular mechanisms of sublethal triclosan exposure in mosquitofish larvae (Gambusia affinis) - Jiaxiang Che; Zhong Li; Xuegeng Wang; Meisha Guo; Haiqin Wang; Liangliang Huang; Honghu Zeng; Xiaohong Song (Aquatic Toxicology, 2025)

Parameter optimization and numerical analysis of the double disc digging shovel for corn root-soil complex - Hailong Che; Hua Zhou; Yinping Zhang; Zhengzhong Li; Xian Wang; Jiaye Li; Jinli Chen; Hui Zhou (Computers and Electronics in Agriculture, 2025)

Evolutionary dynamics and codon bias analysis of canine circovirus: Insights into global spread and host adaptability - Gen Li; Rongqi Liu; Yongyi Chen; Huixian Liang; Yinyi Liang; Xin Li; Yankun Ke; Bowen Lin; Jianfeng Zhong; Xiaofeng Guo; Jun Che; Jun Luo (Molecular Phylogenetics and Evolution, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

Insight into separation of wheat starch and gluten affected by ultrasound-assisted xylanase treatment - Limin Li; Qingfa Wang; Ruibin Che; Xueling Zheng; Chong Liu (Food Chemistry, 2025)

Biopolymer-amended geosynthetic clay liners for landfills and contaminated sites: Gas and hydraulic performance - Ying-Zhen Li; Heng Zhuang; Ji-Ying Fan; Wei-Yi Xia; Jia-Lei Wan; Chi Che; Yan-Jun Du (Environmental Research, 2025)

Moderating effects of reduced morning and evening questionnaire scores on the association between urinary phthalate metabolites and inflammatory cytokines among Chinese young adults: A human biomonitoring study - Tingting Li; Shuman Tao; Tangjun Jiang; Wanyu Che; Liwei Zou; Yajuan Yang; Fangbiao Tao; Xiaoyan Wu (Environmental Toxicology and Pharmacology, 2025)

In situ synthesizable high-performance Ni-Fe5C2 composite catalysts for dry reforming of methane - Jiming Liu; Yaqian Li; Yuchen Che; Wenjuan Shi; Ding Wang; Ruotong Cui; Xiang Feng; Jinhong Zhang; Huie Liu; Yuanyu Tian (Chemical Engineering Journal, 2025)

Origin and Geological Significance of the Cambrian–Permian Mafic-Felsic Magmatic Rocks in the Longshenggeng Area of the East Kunlun Orogenic Belt - Hua Li; Hui-Min Su; Haikui Tong; Changhai Luo; Jianxin Zhang; Tao Wang; Wenjun Li; Chaoping Xue; Jiaxiang Dong; Yuying Che; Xiaolin Chen; Xiong Li (Journal of Earth Science, 2025)

Enhanced complexity of interkingdom co-occurrence networks in blueberry rhizosphere microbial communities under soil pH stress - Jilu Che; Yaqiong Wu; Hao Yang; Ying Chang; Wenlong Wu; Lianfei Lyu; Xiaomin Wang; Fuliang Cao; Weilin Li (Applied Soil Ecology, 2025)

Research on the three-body kelp harvesting ship based on floating raft aquaculture mode - Xian Wang; Yanan Wang; Zhengzhong Li; Hailong Che; Lanlan Zhu; Tongfei Sheng; Hua Zhou; Duanyang Geng (Aquacultural Engineering, 2025)

Multi-objective optimization of inlet and outlet in a circular culture fish tank using the GBDT-NSGAII algorithm and computational fluid dynamic - Shanhong Zhang; Guanghui Yu; Yu Guo; Yang Wang; Daoliang Li; Xiaoli Zhao; Dannie D. O'Brien; Jui-Che Chiang (Aquacultural Engineering, 2025)

Impacts of Low-Order Stream Connectivity Restoration Projects on Aquatic Habitat and Fish Diversity - Xinfeng Li; Xuan Che; Xiaolong Chen; Changfeng Tian; Jiahua Zhang (Fishes, 2025)
River barriers constitute a key factor that is degrading river connectivity and represent a critical research focus in riverine ecosystem conservation. Management authorities and river restoration agencies globally have increasingly employed barrier removal or modification for connectivity restoration projects in recent years, practices that are widely discussed and empirically supported in academia. However, existing research predominantly focuses on large dams in primary rivers, overlooking the more severe fragmentation caused by low-head barriers within low-order streams. This study targets the Yanjing River (total length: 70 km), a third-order tributary of the Yangtze River basin, implementing culvert modification and complete removal measures, respectively, for two river barriers distributed within its terminal 9 km reach. Using differential analysis, principal component analysis (PCA), cluster analysis, Mantel tests, and structural equation modeling (SEM), we systematically examined the mechanisms by which connectivity restoration projects influences aquatic habitat and fish diversity, the evolution of reach heterogeneity, and intrinsic relationships between aquatic environmental factors and diversity metrics. Results indicate that (1) the post-restoration aquatic habitat significantly improved with marked increases in fish diversity metrics, where hydrochemical factors and species diversity exhibited the highest sensitivity to connectivity changes; (2) following restoration, the initially barrier-fragmented river segments (upstream, middle, downstream) exhibited significantly decreased differences in aquatic habitat and fish diversity, demonstrating progressive homogenization across reaches; (3) hydrological factors exerted stronger positive effects on fish diversity than hydrochemical factors did, particularly enhancing species diversity, with a significant positive synergistic effect observed between species diversity and functional diversity. These studies demonstrate that “culvert modification and barrier removal” represent effective project measures for promoting connectivity restoration in low-order streams and eliciting positive ecological effects, though they may reduce the spatial heterogeneity of short-reach rivers in the short term. It is noteworthy that connectivity restoration projects should prioritize the appropriate improvement of hydrological factors such as flow velocity, water depth, and water surface width.

Gaining water bodies by climate change benefits water crisis mitigation in central Asia - Yanan Su; Shengqian Chen; Yijie Sui; Xin Li; Jinhao Xu; Xianghong Che; Tingting Xie; Jianhui Chen; Yongwei Sheng; Min Feng; Fahu Chen (Science Bulletin, 2025)

SEBS-amended in-situ mixed wall material for diesel-contaminated groundwater management - Zhe-Yuan Jiang; Xian-Lei Fu; Fei Jin; Chi Che; Zhong-Yuan Li; Guojun Cai; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Microwave-induced strength reduction and weakening mechanisms of basic rocks - Zhongjun Ma; Xiaobao Zhao; Han Li; Hanwen Liu; Yangwei Long; Yanlong Zheng; Ping Che (International Journal of Rock Mechanics and Mining Sciences, 2025)

A flexible intelligent sensor for patients with amyotrophic lateral sclerosis - Lei Duan; Zhi Li; Fan Jiang; Zong-Ju Chen; Wei-Song Zhang; Pei-Chen Zhao; Li-Chun Wang; Yan-Long Luo; Che Zhao; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Multi-physics modeling and full-cycle performance enhancement of Ca-based particle for calcium looping thermochemical energy storage - Jinbo Che; Xiaoyu Yang; Chao Song; Rui Wang; Zhanbin Liu; Yonggang Lei; Yinshi Li (Chemical Engineering Journal, 2025)

Modulating the density of Co3N/CFs active site by optimizing the micro-structure for overall water splitting electrocatalysis - Qiusen Liu; Tingzheng Fu; Hongbiao Xiao; Ye Yu; Zhiqing Che; Yixing Zhang; Anran Chen; Mian Li; Tingting Liu (Chemical Engineering Journal, 2025)

Deep Hypothermic Low Flow Results in Multiple Aspects of Neurological Deficits in Mice by eEF2 Hyperphosphorylation - Yumei Liao; Dongyang Che; Peng Liu; Xinyu Wang; Yanlin Zhang; Lingling Guo; Jinlin Hu; Tianyao Li; Mei Fong Lam; Nan Ma; Shiqing Zhang; Hua Lu; et al. (Molecular Neurobiology, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

Antiviral and cytotoxic indole diterpenoids from the antarctic sponge-derived fungus Aspergillus candidus HDN15-152 - Bingying Tang; Runfang Zhang; Falei Zhang; Tianjiao Zhu; Qian Che; Dehai Li; Guojian Zhang (Natural Product Research, 2025)

Improved surface water mapping using satellite remote sensing imagery based on optimization of the Otsu threshold and effective selection of remote-sensing water index - Lusheng Che; Shuangshuang Li; Xianfeng Liu (Journal of Hydrology, 2025)

Association of ambient ozone with time to pregnancy and the modifying effect of ambient temperature: a population-based cohort study - Bingxue Wu; Tao Wang; Yan Zhang; Yuyan Li; Cai Kong; Yishi Jiang; Xiangjing Song; Xing Chen; Zhengyuan Xie; Hanfeng Ye; Lin Feng; Zigao Zhao; et al. (Environmental Pollution, 2025)

Aquaporins-inspired MOF with CO2 recognition function in mixed matrix membrane for enhancing CO2/CH4 separation performance - Yong Zhang; Chao Liang; Qingbin Che; Zhaomin Li; Xueqin Li (Chemical Engineering Journal, 2025)

Synergy of single-atom iron and titanium-oxo cluster at oxygen vacancy in MIL-125-NH2 to achieve high-performance CO2-to-CH3OH photocatalysis - Yan Che; Changyan Zhu; Xin Liu; Mengying Li; Xingbing Liu; Hongzhu Xing (Chemical Engineering Journal, 2025)

Hourly estimation of black carbon in China based on sparse observation data and stacking model - Weijie Li; Yaqiang Wang; Zhaoliang Zeng; Ziwei Yi; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2025)

Improving short-term forecasting of surface dust concentration in Northern China: Integrating machine learning with multi-numerical models - Ziwei Yi; Zhaoliang Zeng; Yaqiang Wang; Weijie Li; Bihui Zhang; Hailin Gui; Bin Guo; Wencong Chen; Huizheng Che; Xiaoye Zhang (Atmospheric Pollution Research, 2025)

Effect of Straw Biochar on Availability of Phosphorus in Black Soil During Freeze-Thaw Period - Jiangnan Li; Xiaopei Qi; Fuxin Wang; Yuchen Che; Jingbo Qu; Yong Sun (Journal of Soil Science and Plant Nutrition, 2025)

Alginate-derived oligosaccharides (AOS) enhance the biomass of Phaeodactylum tricornutum and fucoxanthin yield - Xingkai Che; Dingning Fan; Ruirui Ding; Haixing Wu; Yongfu Li (Journal of Applied Phycology, 2025)

Effects of monochromatic LED light quality on photosynthetic capacity and pigment content in Dunaliella salina under low light intensity - Tianze Zhao; Yongfu Li; Xingkai Che; Haixing Wu; Yuchen Ye; Dingning Fan; Zhendong Li; Yingjie Zhao; Wei Ye (Journal of Applied Phycology, 2025)

Improving the Antifouling Properties of CTD During the Marine Field Tests: The Use of CAP@MMT Modified with Acid - Yachen Che; Lianxue Wei; Yaqi Diao; Wenjuan Jia; Hongzhi Li (Journal of Ocean University of China, 2025)

A multi-source data-driven innovative evaluation approach for assessing low-carbon city performance - Xiaoyun Du; Zhijie Li; Yingna Gao; Ying Che (Sustainable Cities and Society, 2025)

Spatiotemporal graph convolutional network using sparse monitoring data for accurate water-level reconstruction in urban drainage systems - Li He; Jun Nan; Lei Chen; Xuesong Ye; Shasha Ji; Zewei Chen; Yibo Zhang; Fangmin Wu; Bohan Liu; Zhencheng Ge; Yanhan Che (Journal of Hydrology, 2025)

Seasonality of precipitation isotopes associated with water vapor budget: A hierarchical clustering-based zoning in China - Haixiang Jie; Yudong Shi; Shengjie Wang; Shijun Lei; Yuqing Qian; Hongyang Li; Cunwei Che; Xiaofan Zhu; Mingjun Zhang (Atmospheric Research, 2025)

Risks of respiratory and circulatory system diseases induced by exposure to PM2.5 in high humidity and low solar radiation environments: disease types, genes, and functions - Xiaomeng Li; Liru Zhang; Zhengliang Zhang; Xuan Li; Jingli Qian; Jiawei Zhou; Hanxiong Che; Yan Han; Xin Qi; Fumo Yang; Yu Huang; Chao Peng; et al. (Environmental Geochemistry and Health, 2025)

Development and evaluation of an electrical impedance tomography (EIT) sensor for real-time monitoring of hemolysis dynamics - Piao Peng; Yue Fu; Bo Che; Xuan Li; Lei Liu; Jing Sun; Teng Luo; Linhong Deng (Analytica Chimica Acta, 2025)

Responses of water–carbon coupling to seasonal drought in different land use types in Northwest China - Xin Yuan; Liang Jiao; Ruhong Xue; Xichen Che; Jingjing Wu; Qian Li; Xuge Wang; Zhengdong Guo (Hydrological Sciences Journal, 2025)

Risk Assessment Method for Flooding Incident Emergency Operating Procedure Considering Mutual Dependence Between Human Error and Available Time - Kehui Li; Shengkui Zeng; Jianbin Guo; Haiyang Che (Journal of Marine Science and Engineering, 2025)
An emergency operating procedure (EOP) for flooding incidents is used to assist crews in preventing ships from capsizing. However, under a flooding scenario, failure to complete the EOP within a limited time may result in the risk of capsizing. Human performance is the major factor in the EOP execution process, which is influenced by available time. There is a mutual dependence between human error and available time: (a) shorter available time will increase time pressure and the human error probability (HEP); (b) human error will either be recovered, which may require more response time and result in shortened available time, or be uncorrected, which may worsen the system state and reduce the time limitation, thereby shortening the available time. This mutual dependence can affect EOP risk, which is not considered in current studies. This paper proposes a method based on a Dynamic Bayesian Network (DBN) to assess EOP risk considering this mutual dependence. To model the mutual dependence, a continuous SPAR-H method is proposed in the intra-slice network to determine the conditional probability distribution of human error for dependence (a), and a dynamic available time model is proposed in the inter-slice network to determine the conditional probability distribution of available time for dependence (b). The Ro-Ro flooding incident is used to illustrate the proposed method.

Synthesis of novel 18 β -glycyrrhetinic acid sulfonate derivatives displaying significant anti-oomycete activity against Phytophthora capsici - Yibo Liu; Yan Li; Yuee Tian; Yihao Guo; Ruxue Wei; Xiaobo Huang; Le Qian; Shengming Liu; Genqiang Chen; Zhiping Che (Natural Product Research, 2025)

Mapping rice lodging severity using dual-pol Sentinel-1 SAR data: polarimetric parameters, lodging sensitivity, and fuzzy classification modelling - Mo Wang; Qing Sun; Xianghong Che; Li Chen; Yunpeng Cui; Juan Liu; Jinming Wu; Ting Wang; Huan Li (International Journal of Remote Sensing, 2025)

Chitosan hydrogel incorporated with bone marrow mesenchymal stem cell-derived exosomal TIMP2 to inhibit angiogenesis in cholangiocarcinoma - Fei Song; Dan Xu; Jiayin Che; Ming Huang; Hongyang Li (Tissue and Cell, 2025)

Deciphering the microbiome, lipopolysaccharides, and metabolome interplay: Unveiling putrescine's mechanism for enhancing sperm quality in heat-stressed boars - Chenglong Yu; Hao Li; Lun Hua; Lianqiang Che; Bin Feng; Zhengfeng Fang; Shengyu Xu; Yong Zhuo; Jian Li; De Wu; Junjie Zhang; Yan Lin (Theriogenology, 2025)

Simulation study on damage behavior of a shallow-buried Foundation bridge under combined action of flood scouring and heavy vehicle load - Tong Wu; Gangping Fan; Chuandong Dou; Xing Li; Chunyang Dou; Jian Che; Tianzhuo Wang; Jincheng Rao (Ocean Engineering, 2025)

Phase transformation of calcium sulfate at mineral-solution interface: An overlooked pathway for selective enrichment of cadmium - Wenjing Li; Guiquan Che; Chunli Wang; Zhihao Zhang; Jing Zhang; Zhang Lin (Journal of Hazardous Materials, 2025)

Simulation investigation on separation characteristics of gas-liquid model products from in-situ pyrolysis of tar-rich coal - Tianlin Yuan; Chang’an Wang; Meijing Chen; Fu Yang; Yujie Hou; Li Ma; Zhonghui Duan; Defu Che (Journal of Environmental Chemical Engineering, 2025)

Two episodes of lunar basaltic volcanism in Mare Fecunditatis as revealed by Luna-16 soil samples - Svetlana Demidova; Alexander Nemchin; Renaud Merle; Yue Guan; James Head; Katherine Helen Joy; Clive R. Neal; Martin Whitehouse; Mikhail Ivanov; Xiao-Lei Wang; Xiaochao Che; Cyril Lorenz; et al. (Geochimica et Cosmochimica Acta, 2025)

Sexual dimorphism in zebrafish aggression and metabolism under acute ammonia stress - Fang Zhi Chua; Li-Yih Lin; Yung-Che Tseng; Ming-Yi Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Preparation of high-performance SiOx anode materials via dual interfacial reinforcement strategy - Ye Wang; Chong Xu; Junjie Fu; Sai Che; Guang Ma; Kaiyi Chen; Jiahao Yang; Shuang Liu; Gong Cheng; Dongyuan Zhang; Yunen Huang; Wenyue Gao; et al. (Chemical Engineering Journal, 2025)

S-scheme heterojunction of WO3/metal-covalent organic frameworks for artificial photosynthetic CO2 reduction - Liang Fang; Li-Wen Bai; Di Wu; Hong-Tu Che; Yanxia Jiang; Ya Wang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

A highly compressible and expandable cellulose sponge with arch-like lamellar structures for non-compressible hemorrhage - Bingjing Cai; Yawen Fan; Shuo Yang; Chaoqun Che; Xiaoyun Li; Xiaoying Wang (Carbohydrate Polymers, 2025)

Comparative studies on the ventilation performance and obstacle deflection effect of attached ventilation in underground generator halls - Jiaxing Li; Angui Li; Xiaofen Ren; Xin Zhang; Jinnan Guo; Jigang Che (Building and Environment, 2025)

Surface Wave Numerical Simulation and Characteristics Analysis Considering the Effect of Sea Ice in the Bohai Sea, China - Wenbo Li; Zhifeng Wang; Rui Li; Che Yue; Wei Zhang; Shengjian Chen (Pure and Applied Geophysics, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Effects of simulated microgravity on dental pulp stem cell stemness - Huailong Hou; Zhengjun Qiu; Jingyi Che; Yanping Li; Jingxuan Sun; Weiwei Zhang; Jinjie Ma; Shuang Zhang; Mengdi Li; Yumei Niu; Lina He (Journal of Molecular Histology, 2025)

DNA Barcode and Correct Scientific Name of Golden Pompano, an Important Marine Aquaculture Fish Species in China - Ang Li; Changting An; Huan Wang; Shuai Che; Shufang Liu; Zhimeng Zhuang (Fishes, 2025)
The golden pompano ranks at the top of production in current China’s marine fish aquaculture; however, there has been long-standing controversy regarding its valid scientific name. Multiple latin names were used simultaneously to refer to golden pompano, such as Trachinotus ovatus, T. blochii, T. mookalee and T. anak. Moreover, two distinct morphological species are regarded as deserving the scientific name T. ovatus. In this study, we employed DNA barcoding to determine which particular species the “golden pompano” represents and to explore the potential synonyms and cryptic species within T. ovatus and its closely related species. We analyzed the DNA barcodes of golden pompano samples from various aquaculture farms in China’s main production regions, as well as most species within the genus Trachinotus. The phylogenetic analyses revealed that all T. ovatus sequences clustered into two divergent clades with a large genetic distance, and the two clades were geographically separated, being from the Indo-west Pacific and the East Atlantic regions, respectively. Based on the type locality information and historical distribution records, we support the validity of the naming of Trachinotus ovatus from the Indo-west Pacific, and the so-called Trachinotus ovatus from the East Atlantic may represent a cryptic species. All the golden pompano samples were clustered into the Indo-west Pacific T. ovatus clade, with a considerably small intragroup genetic distance, which suggests that the golden pompano in China should be identified as the species Trachinotus ovatus. The golden pompano, T. blochii and T. mookalee were completely separated into distinct monophyletic clades in the phylogenetic trees, which indicated that they are different species. The T. anak clustered with the monophyletic clade of Indo-west Pacific T. ovatus and the genetic distance between them was at the intraspecific difference level. This implied that the T. anak might be the junior synonym of T. ovatus. The species delimitations based on the ABGD and bPTP methods are in agreement with the findings from phylogenetic analyses. The above results help to form a consistent viewpoint regarding the naming of the golden pompano and provide new understandings for the taxonomy of the genus Trachinotus.

Bridging the gap between hyperspectral imaging and crop breeding: soybean yield prediction and lodging classification with prototype contrastive learning - Guangyao Sun; Yong Zhang; Lei Wang; Longyu Zhou; Shuaipeng Fei; Shiteng Han; Shunfu Xiao; Yingpu Che; Long Yan; Yun Xu; Yinghui Li; Lijuan Qiu; et al. (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain” [Aquaculture, Volume 586, Part 2, 15 February 2025, 741875] - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

A correlation-guided cooperative coevolutionary method for feature selection via interaction learning-based space division - Yaqing Hou; Huiyue Sun; Gonglin Yuan; Yijing Li; Zifan Che; Hongwei Ge (Swarm and Evolutionary Computation, 2025)

Bioplastics and biodegradable plastics: A review of recent advances, feasibility and cleaner production - Shirui Huang; Qianhe Dong; Sichen Che; Ronghua Li; Kuok Ho Daniel Tang (Science of The Total Environment, 2025)

Comparative analysis of fecundity related traits and transcriptome in two isofemale lines of the egg parasitoid, Trichogramma dendrolimi (Matsumura) - Hong-Yu Liang; An-Ke Liu; Ning He; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Asia-Pacific Entomology, 2025)

Association between ambient temperature and couple fecundity: Insights from a large-scale cohort study in Yunnan, China - Bingxue Wu; Tao Wang; Yan Zhang; Yuyan Li; Xing Chen; Zhengyuan Xie; Cai Kong; Yuzhi Lan; Hanfeng Ye; Xiangjing Song; Zigao Zhao; Yan Che (International Journal of Hygiene and Environmental Health, 2025)

Various wind activity proxies unmixed from grain-size distributions of surface eolian sands at the desert scale in the Tengger Desert, Northwest China - Shipei Dong; Zhuolun Li; Qiujie Chen; Yingyibing Shen; Xuehua Che; Cheng Zhang; Yinzhou Huang (Geomorphology, 2025)

Impacts of live and artificial feed on histology, biochemical indicators, gene expression, and bacterial resistance in mandarin fish (Siniperca chuatsi) - Shunli Che; Jiawei Chen; Hai Zhang; Weizhen Xu; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2025)

The optimized nitrogen rate reduced ammonia emissions from rice paddies in the cold region of Northeast China - Shiting Bi; Pengfei Li; Jiarui Lv; Qiang Dong; Xiangyu Luo; Yeqi Che; Muhammad Rehman Naseer; Zhilei Liu; Cailian Yu; Xianlong Peng (European Journal of Agronomy, 2025)

Effects of nanopolystyrene and/or phoxim exposure on digestive function of Eriocheir sinensis - Mengting Huang; Yuan Ma; Qianru Fan; Shunli Che; Jun Zhang; Shuquan Ding; Shuren Zhu; Xilei Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

MIL-100(Fe)-derived Mg/Fe layered double hydroxides composite millimeter-scale aerogel beads for phosphate adsorption from real domestic wastewater - Yubo Pan; Ruijie Che; Keren Lu; Linrui Li; Mingxing Shi; Mingzhu Xia; Fenghe Wang; Fengyun Wang (Chemical Engineering Journal, 2025)

Effects of forest fire on successional trajectory of understory vegetation in boreal permafrost region in Northeast China - Xiaoying Li; Hongwei Wang; Huijun Jin; Ruixia He; Xiaoying Jin; Yan Li; Gangyi Zhou; Fuqiang Che (Cold Regions Science and Technology, 2025)

Long-term distribution and evolution trends of absorption aerosol optical depth with different chemical components in global and typical regions - Hujia Zhao; Ke Gui; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Xiaofang Jia; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

Olaparib research update: mechanism, structure and clinical trials - Hao Che; Li-Wei Wang; Xiang-Yang Ye; Xingrui He (Medicinal Chemistry Research, 2025)

Reforestation significantly enriches soil microbial carbon, nitrogen, and phosphorus cycling genes but simplifies their co-occurrence network - Dong Liu; Song Zhang; Weirong Zhuang; Kexin Li; Fang Wang; Ting Li; Danhong Chen; Qiuping Fan; Zejin Zhang; Muyesaier Tudi; Rongxiao Che (Applied Soil Ecology, 2025)

Seasonality and extreme flooding can override the effects of debris dam removal on riverine species: a case study of macroinvertebrates - Tsung-Tse Hsieh; Jia-Yi Li; Che-Chang Lin; Mei-Hwa Kuo; Ming-Chih Chiu (Aquatic Ecology, 2025)

Increased miRNA-375 causes oxidative damage but promotes apoptosis resistance and cell migration in the clam Ruditapes philippinarum - Ming Cong; Zhaoshun Li; Wenwen Tian; Yixian Yu; Yu Che; Jiasen Lv (Frontiers in Marine Science, 2025)
MicroRNA is an important regulatory factor at the post-transcriptional level. Previous miRNAomics analysis found that miRNA-375 was steadily upregulated in the clam Ruditapes philippinarum upon ammonia nitrogen exposure. However, we have no knowledge about its regulatory mechanism yet. In this study, the clams were challenged by the injection of miRNA-375 mimics/inhibitor in vivo . Then, a combined approach of qRT-PCR, enzyme assay, and ultrastructure observation was applied to investigate its regulatory effects on the related genes, cellular parameters, and histological structures, respectively. Results showed that increased expression of miRNA-375 interfered with the expression levels of both its target genes and ammonia toxicity-related genes, which would probably lead to oxidative stress, migration of damaged cells, apoptosis resistance, and increased possibility of tumor formation. In addition, miRNA-375 increased MDA content but decreased glutamate content and caused serious structure damage to the clam gills. Thus, increased miRNA-375 probably brings a disastrous fate to the clam R. philippinarum by inducing oxidative damage but promoting apoptosis resistance and cell migration. Overall, this study revealed for the first time the regulatory effects of miRNA-375 in the clams and gave valuable clues to understand the toxicological mechanisms of ammonia nitrogen on the marine bivalve.

Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Land degradation decreased crop productivity by altering soil quality index generated by network analysis - Ming Gao; Wei Hu; Xingyi Zhang; Meng Li; Yongsheng Yang; Renfeng Che (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

Uncovering the impacts of social comparative information on water saving behavior among urban residents: A field experiment in China - Juan Wang; Le Wen; Yongbo Li; Jing Liu; Shuai Che (Journal of Cleaner Production, 2025)

Ticks jump in a warmer world: Global distribution shifts of main pathogenic ticks are associated with future climate change - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Wenwen Chen; Lianjin Liu; Xiaofang Zhou; Chong Chen; Xian Li; Yiyang Su; Lingyu Che; Guishuang Li (Journal of Environmental Management, 2025)

Tandem synergetic effect in symbiotic Co catalyst for enhanced oxygen reduction - Jing Zhang; Meihuan Liu; Yuhao Zhang; Hui Su; Xiuxiu Zhang; Baojie Li; Jianglong Guo; Youcai Che; Weiren Cheng; Qinghua Liu (Chemical Engineering Journal, 2025)

Epidemiology of liver diseases: global disease burden and forecasted research trends - Jia Xiao; Fei Wang; Yuan Yuan; Jinhang Gao; Lu Xiao; Chao Yan; Feifei Guo; Jiajun Zhong; Zhaodi Che; Wei Li; Tian Lan; Frank Tacke; et al. (Science China Life Sciences, 2025)

The shifts of precipitation phases and their impacts - Xuemei Li; Tao Che; Yuanlong Tang; Huan’e Duan; Guigang Wang; Xu Zhang; Chuanming Yang; Jun Wu; Yue Zhang; Lanhai Li (Science China Earth Sciences, 2025)

Applicability of Different Indices for Delineating the Boundary of Arid Region: A Case Study in Northwestern China - Xue Peng; Xiang Li; Yingyibing Shen; Xuehua Che; Shipei Dong; Zhuolun Li (Journal of Earth Science, 2025)

Mitigating Vibrio-Induced Skin Ulceration in Sea Cucumbers Using Probiotic Strains - Wan Zhang; Jian Che; Xiaowen Sun; Bilal Murtaza; Chenghao Zhang; Xiaoyu Li; Lili Wang; Yongping Xu (Fishes, 2025)
Sea cucumbers are valuable in aquaculture, but their cultivation faces challenges from diseases such as skin ulceration syndrome caused by Vibrio alginolyticus (VA). This study aimed to isolate and identify probiotics capable of combating VA and improving sea cucumber’s growth performance. Pathogenic VA was identified, through 16S rDNA sequencing, confirming its high genetic similarity (>99%) to Vibrio alginolyticus. Two Bacillus strains, Bacillus licheniformis YB-1, and Bacillus megaterium YB-2, were isolated as potential probiotics, with identification supported by 16S rDNA phylogenetic analysis and deposition in microbial culture collections. They demonstrated strong antibacterial activity against VA in vitro without exhibiting antagonism when combined. Probiotic tolerance to environmental stressors was observed, while feeding trials revealed significant growth improvements in sea cucumbers, with the highest specific growth rates observed at 1 × 106 CFU/mL for both strains. Immersion challenge tests showed that sea cucumbers treated with probiotics exhibited reduced symptoms of rotten skin syndrome and higher survival rates. The optimal combination of YB-1 and YB-2, with viable bacteria concentrations of 5 × 107 CFU/mL each, achieved a 55% survival rate after a VA challenge, demonstrating their synergistic efficacy. These findings suggest that YB-1 and YB-2 offer promising probiotic solutions for enhancing sea cucumber health and resistance to VA infections in aquaculture.

Effects of bicarbonate on antioxidant, immune, osmolytic and metabolic capabilities of Scylla paramamosain - Chenxi Che; Yuntao Li; Kangxiang Qin; Ziwei Fan; Wenjun Li; Shan Gao; Peng Yang; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Thermal pressure ventilation analysis in a sloping high-temperature tunnel: A case study in China - Jigang Che; Angui Li; Yuanqing Ma; Jinnan Guo; Jiaxing Li; Changqing Yang; Lunfei Che (Tunnelling and Underground Space Technology, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Black soldier fly and microbiome collaborate to bioconvert the tofu whey water in an efficient and environment-friendly manner - Xiaowen Ji; Shaojie Zhou; Wenwen Chen; Bin Cao; Yumeng Sun; Qiyang Che; Yinglao Zhang; Jibin Zhang; Ting Ding; Jiaping Xu; Feng Peng; Maoye Li; et al. (Journal of Water Process Engineering, 2025)

Mechanisms of nano zero-valent iron in enhancing dibenzofuran degradation by a Rhodococcus sp.: Trade-offs between ATP production and protection against reactive oxygen species - Xu Wang; Yaning Che; Yonglan Xu; Yanan Wu; Hangzhou Xu; Li Li (Journal of Hazardous Materials, 2025)

Three-dimensional oriented Ca nanoporous carbon with N doping tuned via self-assembly to potentiate P adsorption: The vital role of the micro interfacial electronic environment - Yibo Zhang; Jun Nan; Fangmin Wu; Xuesong Ye; Zhencheng Ge; Li He; Yanhan Che; Han Deng; Yunhao Pan; Bohan Liu (Journal of Cleaner Production, 2025)

Wheat growth stage identification method based on multimodal data - Yong Li; Yinchao Che; Handan Zhang; Shiyu Zhang; Liang Zheng; Xinming Ma; Lei Xi; Shuping Xiong (European Journal of Agronomy, 2025)

Photo-motivated heterojunctions coupling built-in electric field stimulating sulfur redox kinetics for lithium-sulfur batteries - Haifeng Zhang; Fei Ma; Ting Meng; Junwei Li; Haifei Zhu; Zeyu Geng; Wenbo Zhao; Xiaohan Wang; Penghui Wu; Abdelnaby M. Elshahawy; Qianrui Gao; Quande Che (Chemical Engineering Journal, 2025)

Trifunctional surface engineering of Lithium-rich manganese-based oxides via Al3+/PO43− co-doping and oxygen vacancy regulation for High-performance lithium-ion batteries - Hongyun Zhang; Jinyang Dong; Gang Chen; Huiquan Che; Kang Yan; Xi Wang; Jinzhong Liu; Dewang Liu; Yun Lu; Ning Li; Yuefeng Su; Feng Wu; et al. (Chemical Engineering Journal, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Triple modifications of Li-rich manganese-based cathode materials using LiMnPO4 one-step method - Jianan Hao; Jinyang Dong; Yuefeng Su; Kang Yan; Jiayu Zhao; Huiquan Che; Yun Lu; Ning Li; Bin Zhang; Ping Zhang; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

Editing of the soluble starch synthase gene MeSSIII-1 enhanced the amylose and resistant starch contents in cassava - Xiaohua Lu; Yajie Wang; Xinghou Zhen; Yannian Che; Hui Yu; Yujian Ge; Xiangwen Wang; Ruimei Li; Mengting Geng; Bin Zhou; Jiao Liu; Jianchun Guo; et al. (Carbohydrate Polymers, 2025)

High lead-tolerant mutant Bacillus tropicus AT31-1 from rhizosphere soil of Pu-erh and its remediation mechanism - Qiang Li; Wenxia Yuan; Xiujuan Deng; Yaping Chen; Limei Li; Lijiao Chen; Raoqiong Che; Wei Huang; Yamin Wu; Chun Wang; Zejun Wang; Miao Zhou; et al. (Bioresource Technology, 2025)

Impacts of nanopolystyrene and/or phoxim exposure at environmentally relevant concentrations on the intestinal histopathology, intestinal microbiota, and metabolome in Eriocheir sinensis - Shuquan Ding; Shunli Che; Mengting Huang; Yuan Ma; Longteng Shen; Jianbin Feng; Xilei Li (Aquatic Toxicology, 2025)

A logistic-Lasso-regression-based seismic fragility analysis method for electrical equipment considering structural and seismic parameter uncertainty - Jiawei Cui; Ailan Che; Sheng Li; Yongfeng Cheng (Earthquake Engineering and Engineering Vibration, 2025)

Removal of Cr(VI) from water using microalgae-based modified biochar: Adsorption performance, mechanisms, and life cycle assessment - Shuo Shang; Wenlu Che; Yanpeng Li (Algal Research, 2025)

Selenium-enriched Lactobacillus plantarum alleviate of high alkalinity-induced microbiota-gut-blood systems affect by improving the gut microbiota - Xinchi Shang; Longwu Geng; Haijun Wei; Xinghua Che; Lu Xing; Meiqi Xing; Wei Xu; Jian Hong Li (Aquaculture, 2024)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Environmental changes and human impacts over the past 1200 years: Evidence from high-resolution pollen records from peat in the Yunnan-Guizhou Plateau, Southwest China - Shuming Li; Lisi Wei; Wenwei Zhao; Weihe Ren; Qinran Gu; Zixuan Che; Xianyong Cao; Huan Li; Xiaojian Zhang; Chunzhu Chen; Yan Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Comparison of environmental impacts from pyrolysis, gasification, and combustion of oily sludge - Hongdi Yu; Fawei Lin; Xuan Guo; Chujun Luan; Jiantao Li; Rundong Li; Lei Che; Wangyang Tian; Guanyi Chen (Journal of Hazardous Materials, 2024)

Reductive soil disinfestation influences microbial aging of low-density polyethylene and polyhydroxyalkanoate microplastics and microbial communities in plastispheres - Jiahe Miao; Yining Zhu; Wen Li; Ruijie Che; Xinyan Zong; Jining Li; Fenghe Wang; Yicheng Wu; Haiyan Fu (Journal of Environmental Management, 2024)

Estimating AVHRR snow cover fraction by coupling physical constraints into a deep learning framework - Qin Zhao; Xiaohua Hao; Tao Che; Donghang Shao; Wenzheng Ji; Siqiong Luo; Guanghui Huang; Tianwen Feng; Leilei Dong; Xingliang Sun; Hongyi Li; Jian Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Recognition of dispersed organic matter macerals using YOLOv5m model with convolutional block attention module - Yuanzhe Wu; Qingfeng Lu; Wenfeng Wang; Wenlong Wang; Jiaxin Li; Xinyi Xu; Kexin Che (Fuel, 2024)

Research on a novel method of air distribution to create a uniform indoor environment in a long and narrow building - Changqing Yang; Kun Zhang; Jiaxing Li; Tianqi Wang; Haiguo Yin; Chongqing Cai; Lunfei Che (Energy and Buildings, 2024)

Lung cell injury risks of PM2.5 exposure in the high humidity and low solar radiation environment of southwestern China - Qin Zhang; Xuan Li; Xiaomeng Li; Ronghua Zhang; Bi Ren; Hanxiong Che; Xin Qi; Jiawei Zhou; Jiancai Tang; Andre S.H. Prevot; Zhenzhong Liu; Li Jiang; et al. (Atmospheric Environment, 2024)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

The Multifaceted Roles of Hippo-YAP in Cardiovascular Diseases - Hao Wu; Yan-Nan Che; Qi Lan; Yi-Xiang He; Ping Liu; Ming-Tai Chen; Li Dong; Meng-Nan Liu (Cardiovascular Toxicology, 2024)

Establishment and Validation of Sandell-Kolthoff Method for Saliva Iodine Determination - Yue Su; Ming Li; Honglei Xie; Xin Hou; Meng Zhao; Jia Li; Haowen Pan; Zexu Zhang; Zongyu Yue; Wenjing Che; Lanchun Liu; Jiasen Cao; et al. (Biological Trace Element Research, 2024)

A BP-Neural-Network-Based PID Control Algorithm of Shipborne Stewart Platform for Wave Compensation - Daoxi Li; Shuqing Wang; Xiancang Song; Zepeng Zheng; Wei Tao; Jvpeng Che (Journal of Marine Science and Engineering, 2024)
In order to carry out offshore operations smoothly in severe sea conditions, a shipborne Stewart platform for wave compensation is required. Due to the random characteristics of waves, traditional control algorithms cannot accurately compensate for the motion caused by a wave. For the electric shipborne Stewart platform, this paper proposes a backpropagation (BP)-neural-network-based proportional–integral–derivative (PID) control algorithm where the PID parameters are adaptively adjusted by a BP neural network. The control algorithm can improve the robustness and wave compensation precision of the wave compensation system. First, a numerical system model of the shipborne Stewart platform was established according to the classical kinematic model and dynamic model. Then, the BP-PID control algorithm was designed based on the joint space control. In order to reduce the network’s sensitivity to local details and quickly find the global minimum, the gradient descent method with the momentum term is used in the neural network. At last, the availability and rationality of the new method were substantiated through a simulation comparison under various sea conditions. The simulation results indicate that the proposed control method achieves a higher compensation accuracy in three directions under various sea states, compared with traditional PID control algorithm. Under the irregular wave disturbance, the new control method can reduce the position deviation by about 6.56 times compared with a traditional PID control algorithm. The new control algorithm will play an active role in the control of the shipborne Stewart platform.

Standardization in global environmental antibiotic resistance genes (ARGs) surveillance - Xuemei Mao; Xiaole Yin; Yu Yang; You Che; Xiaoqing Xu; Yu Deng; Liguan Li; Tong Zhang (Critical Reviews in Environmental Science and Technology, 2024)

Metabolomics reveals the potential mechanism of La(III) promoting enrichment of Sodium hydrogen arsenate and Roxarsone in Solanum nigrum L. - Yining Zhu; Ruijie Che; Zhongtian Dong; Ting Guo; Xin He; Jining Li; Fenghe Wang (Science of The Total Environment, 2024)

Global genomic epidemiology and transmission dynamics of plasmid-borne tmexCD-toprJ-carrying Klebsiella pneumoniae in a one health context - Hao Guo; Lirong Li; Yingying Zhang; Yawen Zhang; Che Song; Yuye Wu; Juan Xu; Zhi Ruan; Fang He (Science of The Total Environment, 2024)

Analysis of the spatiotemporal changes in global tropospheric ozone concentrations from 1980 to 2020 - Bo Liang; Jianjun He; Lifeng Guo; Yarong Li; Lei Zhang; Huizheng Che; Sunling Gong; Xiaoye Zhang (Science of The Total Environment, 2024)

Effects of filter-feeding fish faeces on microbial driving mechanism of lake sediment carbon transformation - Yiming Li; Xuan Che; Hongyuan Chen; Zhanpeng Meng; Xinfeng Li; Xiaodong Wang; Lin Zhu; Yunlong Zhao (Science of The Total Environment, 2024)

Terrestrial locomotion stability of undulating fin amphibious robots: Separated elastic fin rays and asynchronous control - Deliang Yu; Tianyu Che; Huibo Zhang; Yezhuo Li; Dongyang Sun; Zhaotian Wang (Ocean Engineering, 2024)

Construction and characterization of different hemolysin gene deletion strains in Vibrio parahaemolyticus (ΔhlyA, ΔhlyIII) and evaluation of their virulence - Jinyuan Che; Shaojie Hu; Qitong Fang; Binghong Liu; Zhuochen Liu; Cunjie Hu; Lei Wang; Lekang Li; Baolong Bao (Journal of Invertebrate Pathology, 2024)

Effect of co-fermentation of non-Saccharomyces yeasts with Saccharomyces cerevisiae on the quality and flavor of blueberry wine - Xiaming Che; Bang Li; Jiali Zeng; Yanru Chen; Jingjing Liu; Wenwen Zeng; Wenqin Cai; Yin Wan; Guiming Fu (Food Research International, 2024)

Optimal agronomic measures combined with biochar increased rice yield through enhancing nitrogen use efficiency in soda saline-alkali fields - Shihao Miao; Xudong Wang; Yang Song; Yue Zhang; Xuebin Li; Weikang Che; Junlong Piao; Liming Xie; Feng Jin (European Journal of Agronomy, 2024)

Copper/iron bimetal phenolic networks boosted apoptosis/ferroptosis/cuproptosis combined tumor therapy through dual glutathione depletion - Fan Zhao; Hongyan Yu; Chen Wang; Junchen Xu; Hao Gao; Yao Ying; Wangchang Li; Juan Li; Jingwu Zheng; Liang Qiao; Shenglei Che; Jing Yu (Chemical Engineering Journal, 2024)

Chemical regulation of lignin spatial conformation for a multifunctional soft material with a novel energy dissipation mechanism - Yingying Su; Xiao Han; Guanda Che; Jinghui Zhou; Yao Li; Sheng Cheng; Cong Wang; Xu Fei (Chemical Engineering Journal, 2024)

Structural reconstruction of lignin by mild and efficient dissolution: A strategy for the fabrication of mechanically strong carbon fiber precursors - Ruimin Che; Hui Zhao; Xin Li; Deqiang Li; Haq Nawaz; Feng Xu (Chemical Engineering Journal, 2024)

Experimental investigation on product and temperature distribution in a continuous flow packed-bed reactor for dodecahydro-N-ethylcarbazole dehydrogenation - Jingwen Xue; Pengzhao Li; Pengfei Yu; Jinhao Yi; Tao Ma; Hu Liu; Defu Che (Chemical Engineering Journal, 2024)

3D cellulose scaffold with gradient pore structure controlled by hydrogen bond competition: Super-strength and multifunctional oil/water separation - Wenqiu Zheng; Xiaoyu Wang; Ruimin Che; Deqiang Li; Xianhai Zeng; Fangong Kong; Lupeng Shao; Xin Li; Feng Xu (Carbohydrate Polymers, 2024)

Self-flocculating Spirulina platensis CMB-02 to efficiently treat ammonia nitrogen of rare earth elements wastewater - Dandan Che; Yulin Lai; Ziqi Weng; Ming Li; Guanglu Huang; Mingmin Zheng; Mingzi Wang (Bioresource Technology, 2024)

Changes in precipitation phases based on the multi-discrimination method in the Tibetan Plateau - Xu Zhang; Xuemei Li; Tao Che; Chuanming Yang; Huane Duan; Jun Wu; Yang Liu (Atmospheric Research, 2024)

Nanopolystyrene and phoxim pollution: A threat to hepatopancreas toxicity in Chinese mitten crab (Eriocheir sinensis) - Mengting Huang; Yuan Ma; Shunli Che; Longteng Shen; Zhicheng Wan; Shiping Su; Shuquan Ding; Xilei Li (Aquatic Toxicology, 2024)

Genome-wide identification of Aux/IAA gene family members in grape and functional analysis of VaIAA3 in response to cold stress - Shixiong Lu; Min Li; Yongjuan Cheng; Huimin Gou; Lili Che; Guoping Liang; Juan Mao (Plant Cell Reports, 2024)

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

Sedimentation and transformation of heavy metals during the transport from the Yellow River estuary to the sea: Evidence from surface sediments of the Yellow River subaqueous delta - Caiping Hu; Ming Liu; Yiping Li; Jia Li; Xinying Che; Hongwei Wang (Marine Pollution Bulletin, 2024)

Transcriptomic analysis reveals nanoplastics-induced apoptosis, autophagy and immune response in Litopenaeus vannamei - Yiming Li; Yucong Ye; Xiaoyi Zhu; Xingguo Liu; Xinfeng Li; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Metabolites of blueberry roots at different developmental stages strongly shape microbial community structure and intra-kingdom interactions at the root-soil interface - Jilu Che; Yaqiong Wu; Hao Yang; Ying Chang; Wenlong Wu; Lianfei Lyu; Xiaomin Wang; Fuliang Cao; Weilin Li (Science of The Total Environment, 2024)

Efficient adsorption of short-chain perfluoroalkyl substances by pristine and Fe/Cu-loaded reed straw biochars - Na Liu; Yinhui Li; Minggu Zhang; Naiju Che; Xianliang Song; Yanli Liu; Chengliang Li (Science of The Total Environment, 2024)

Novel insights into the mechanism of dynamic changes in microstructure and physicochemical properties of corn straw pretreated by ball milling and feasibility analysis of anaerobic digestion - Youpei Qu; Xinying Miao; Shaopeng Chen; Nan Qin; Jiangnan Li; Yuchen Che; Lina Luo; Yong Sun (Science of The Total Environment, 2024)

Multi-targets detection via combination of multi-stimulus-response engineered bacteria and hydrogel-based separation platform - Huachao Che; Xike Tian; Yulun Nie; Yong Li; Liqiang Lu; Yuguang Hu (Journal of Hazardous Materials, 2024)

Migration of naphthalene in a biochar-amended bioretention facility based on HYDRUS-1D analysis - Meipeng Jian; Yongjian Che; Mingchen Gao; Xiaoran Zhang; Ziyang Zhang; Chaohong Tan; Haiyan Li (Journal of Environmental Management, 2024)

Riboflavin-induced microbial succession for enhanced tellurite reduction in wastewater treatment - Jiawei Jing; Bin Yu; Tingting Wang; Xinyu Guo; Pengfei Huang; Jiayue Che; Chuan Li; Yuanyuan Qu (Journal of Environmental Chemical Engineering, 2024)

Synergistic effect of holey graphene and CoSe2-NiSe2 heterostructure to enhance fast Na-ion transport - Chong Xu; Kaiyi Chen; Jiahao Yang; Guang Ma; Ye Wang; Zizheng Zhou; Zhixuan Wu; Sai Che; Zechen Li; Yuxin Tu; Zhihua Xiao; Daqiang Jiang; et al. (Chemical Engineering Journal, 2024)

CoSe2-Modified multidimensional porous carbon frameworks as high-Performance anode for fast-Charging sodium-Ion batteries - Chong Xu; Jiahao Yang; Kaiyi Chen; Guang Ma; Ye Wang; Zechen Li; Zizheng Zhou; Zhixuan Wu; Sai Che; Changsheng Ding; Yongfeng Li (Chemical Engineering Journal, 2024)

The adsorption and fixation of Cd and Pb by the microbial consortium weakened the toxic effect of heavy metal-contaminated soil on rice - Songhao Che; Jianing Wang; Yuanqin Zhou; Chengcai Yue; Xueying Zhou; Yufeng Xu; Shiqi Tian; Zhenning Cao; Xiaoshuang Wei; Siyuan Li; Xue Yang; Zhihai Wu; et al. (Chemical Engineering Journal, 2024)

Fabrication of carbon-coated iron-based porous heterogeneous Fenton catalyst and enhanced degradation performance towards ciprofloxacin - Yufan Mo; Chunxia Che; Wei Han; Feiran Chen; Jun Guan; Feng Zhang; Bo Yang; Xiangdong Ren; Huiyu Li; Saeed Ahmed; Yongjun Feng (Chemical Engineering Journal, 2024)

The role of ALDH1A1 in glioblastoma proliferation and invasion - Yu-Kai Huang; Tzu-Ming Wang; Chi-Yu Chen; Chia-Yang Li; Shu-Chi Wang; Khushboo Irshad; Yuan Pan; Kun-Che Chang (Chemico-Biological Interactions, 2024)

Tropical cyclone ensemble forecast framework based on spatiotemporal model - Tongfei Li; Kaihua Che; Jiadong Lu; Yifan Zeng; Wei Lv; Zhiyao Liang (Earth Science Informatics, 2024)

Quantification of irrigation water transport processes in ZiZiphus jujuba garden using water stable isotopes - Xiaofei Zhong; Mingjun Zhang; Cunwei Che; Zechen Liu; Beibei Li; Yuanyuan Zhang (Journal of Mountain Science, 2024)

Influence of film color, mulching ratio and soil–mulch contact degree on heat transfer in Northwest China - Yin Zhao; Zunqiu Xu; Xiaomin Mao; Sien Li; Xingchao Qi; Jiangang Che (Agricultural and Forest Meteorology, 2024)

Disulfidptosis: A new type of cell death - Fei Xiao; Hui-Li Li; Bei Yang; Hao Che; Fei Xu; Gang Li; Cheng-Hui Zhou; Sheng Wang (Apoptosis, 2024)
Disulfidptosis is a novel form of cell death that is distinguishable from established programmed cell death pathways such as apoptosis, pyroptosis, autophagy, ferroptosis, and oxeiptosis. This process is characterized by the rapid depletion of nicotinamide adenine dinucleotide phosphate (NADPH) in cells and high expression of solute carrier family 7 member 11 (SLC7A11) during glucose starvation, resulting in abnormal cystine accumulation, which subsequently induces andabnormal disulfide bond formation in actin cytoskeleton proteins, culminating in actin network collapse and disulfidptosis. This review aimed to summarize the underlying mechanisms, influencing factors, comparisons with traditional cell death pathways, associations with related diseases, application prospects, and future research directions related to disulfidptosis.

New cyclic dipeptide discovered from deep-sea derived Aspergillus sp. HDN20-1401 - Komal Anjum; Xiaofei Huang; Luning Zhou; Tianjiao Zhu; Qian Che; Guojian Zhang; Dehai Li (Natural Product Research, 2024)

Effects of sulfate on survival, osmoregulation and immune inflammation of mud crab(Scylla paramamosain) under low salt conditions - Yun Hu; Gao Gao; Kangxiang Qin; Xiaosong Jiang; Chenxi Che; Yuntao Li; Changkao Mu; Chunlin Wang; Huan Wang (Aquaculture, 2024)

A review on ‘source prevention, process control, end recovery’ trinity-comprehensive treatment technology for acid mine drainage - Yu Yang; Bo Li; Lulu Che; Menghua Li; Pu Liu; Tao Li; Ye Luo (Process Safety and Environmental Protection, 2024)

Impact of re-entrant jet and shedding cloud cavity on the distribution of cavitation erosion - Ning Qiu; Doubin Xun; Han Zhu; Pei Xu; Bangxiang Che; Minwei Li; Wenjie Zhou (Ocean Engineering, 2024)

Improve flotation efficiency of refractory tungsten ore and reduce carbon emission in flotation process: A case study of Sandaozhuang deposit in Henan, China - Wei Li; Fen Jiao; Xu Wang; Wenfang Che; Zhengquan Zhang; Baijun Xin; Min Xu; Wenqing Qin (Minerals Engineering, 2024)

Environmental impacts and decarbonization pathways of oily sludge pyrolysis based on life cycle assessment - Longtao Ji; Dungang Gu; Bin Cai; Lei Che; Lishan Xiao; Dominic C.Y. Foo; Nan Zhang; Yuhang Lou; Tingting Hu; Guanghui Li; Jiaqi Lu (Journal of Cleaner Production, 2024)

Optimization and analysis of a novel hydrogen liquefaction coupled system with dual path hydrogen refrigeration cycle and the closed nitrogen cycle pre-cooling - Shipeng Yu; Zhaoxi Wang; Guodong Qiu; Xunjian Che; Jie Chen; Qian Li; Weihua Cai (Journal of Cleaner Production, 2024)

Towards environmentally-friendly solutions for real textile-dyeing wastewater with energy recovery: Effluent recirculation and Rubia plant-derived purpurin electron mediator in microbial fuel cell - Sing-Mei Tan; Li-Ngee Ho; Yee-Shian Wong; Che Zulzikrami Azner Abidin; Soon-An Ong (Journal of Environmental Management, 2024)

Performance research and improvement of ultra-high-speed R290 rotary compressor - Hua Zhong; Bowen Lei; Li Zhang; La Da; Che Wang; Jianhua Wu (International Journal of Refrigeration, 2024)

Screening and rational identification of a novel angiotensin-converting enzyme C-domain inhibitory peptide from Fabaceae food peptide library - Tin-Yun Ho; Hsin-Yi Lo; Guan-Ling Lu; Chia-Yu Lin; Mei-Li Stevens; Chiao-Che Chen; Chien-Yun Hsiang (Food Chemistry, 2024)

A novel pH/ROS dual responsive engineering hydrogels based on poly(tannic acid)-assisted surface deposition of nano-enzymes with efficient antibacterial and antioxidant activity for diabetic wound healing - Hongyu Li; Yingping Wang; Xiance Che; Lanping Guo; Luqi Huang; Xia Li; Wenyuan Gao (Chemical Engineering Journal, 2024)

Impacts of cation modification on the carrier dynamics and chemical stability of SnO2-based buried interfaces in perovskite solar cells - Jidong Deng; Abduvely Mijit; Xubiao Wang; Yinhu Gao; Yuliang Che; Lu Lin; Xiaofeng Li; Minyi Huang; Li Yang; Jinbao Zhang (Chemical Engineering Journal, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Relative contributions of component-segregated aerosols to trends in aerosol optical depth over land (2007–2019): Insights from CAMS aerosol reanalysis - Hengheng Zhao; Ke Gui; Wenrui Yao; Nanxuan Shang; Xutao Zhang; Yuanxin Liang; Yurun Liu; Lei Li; Yu Zheng; Zhili Wang; Hong Wang; Junying Sun; et al. (Atmospheric Environment, 2024)

The relationship between resistance evolution and carbon metabolism in Staphylococcus xylosus under ceftiofur sodium stress - Qianwei Qu; Haixin Peng; Mo Chen; Xin Liu; Ruixiang Che; God’spower Bello-Onaghise; Zhiyun Zhang; Xueying Chen; Yanhua Li (Archives of Microbiology, 2024)

Genetic analysis of Discogobio (Cypriniformes: Cyprinidae) in the Central Yunnan Basin: Effects of geological events and conservation perspectives - Xing‐Jin Che; Yuan‐Wei Zhang; An‐Li Wu; Li‐Mei Zhang; Xiao‐Fu Pan; Mo Wang; Jun‐Xing Yang; Xiao‐Ai Wang (Zoologica Scripta, 2024)
Geological events can have a major effect on the genetic structure and differentiation of fish populations. The relative importance of key geological events on the distribution and genetic structure of endemic fish of the genus Discogobio in the Yunnan–Guizhou Plateau has not yet been evaluated. Studies of the phylogeography of Discogobio fishes could provide insights into spatial and temporal changes in their population size, dispersal history, and extent of geographical isolation, and the data acquired in such studies can be used to aid their conservation. Here, we used single‐nucleotide polymorphisms (SNP) to characterize the phylogeography of Discogobio fishes. Our analysis supports the endemicity of Discogobio . However, Discogobio samples from different regions contained multiple ancestral components, including admixed and diversified genetic components. This might stem from polymorphism of the ancestors themselves or the infiltration of genes caused by hybridization between Discogobio species. We estimated that the most recent common ancestor (MRCA) of Discogobio fish in the Central Yunnan Basin was approximately 4.63–3.83 million years ago (Ma). We also inferred that the evolution of Discogobio in the Central Yunnan Basin was closely related to the expansion and contraction of the lake basin around 2.59–0.13 Ma. We proposed measures that could be implemented to conserve remaining populations and their corresponding habitats to prevent further declines and preserve the biodiversity of this unique genus.

Monitoring nonlinear large gradient subsidence in mining areas through SBAS-InSAR with PUNet and Weibull model fusion - Yuanjian Wang; Ximin Cui; Chunqing Ge; Yuhang Che; Yuling Zhao; Peixian Li; Yue Jiang; Xiaoqing Han (Environmental Science and Pollution Research, 2024)

Metaphire guillelmi exhibited predominant capacity of arsenic efflux - Xiayun Zang; Mingyue He; Yuanzhou Xu; Ting Che; Fei Wang; Jingjing Xu; Huijuan Zhang; Feng Hu; Li Xu (Chemosphere, 2024)

Antisymmetric planar Hall effect in rutile oxide films induced by the Lorentz force - Yongwei Cui; Zhaoqing Li; Haoran Chen; Yunzhuo Wu; Yue Chen; Ke Pei; Tong Wu; Nian Xie; Renchao Che; Xuepeng Qiu; Yi Liu; Zhe Yuan; et al. (Science Bulletin, 2024)

Insecticide resistance and characteristics of mutations related to target site insensitivity of diamondback moths in Taiwan - Chia-Che Chang; Shu-Mei Dai; Chien-Yu Chen; Li-Hsin Huang; Yu-Hsien Chen; Ju-Chun Hsu (Pesticide Biochemistry and Physiology, 2024)

Accurate and precise in situ determination of beryllium contents in beryllium minerals using ablation spot size of 13 μm by LA–ICP–MS - Wen-Kai Jin; Xu-Dong Che; Ru-Cheng Wang; Huan Hu; Can Rao; Wen-Lan Zhang; Xiao-Feng Li (Journal of Geochemical Exploration, 2024)

Non-radical activation of persulfate with Bi2O3/BiO1.3I0.4 for efficient degradation of propranolol under visible light - Yuehua Deng; Qianqian Che; Yani Li; Jiating Luo; Xiang Gao; Yan He; Yiling Liu; Tong Liu; Xiaolong Zhao; Xiaobin Hu; Wei Zhao (Journal of Environmental Sciences, 2024)

Enhancing immobilized Chlorella vulgaris growth with novel buoyant barium alginate bubble beads - Yi Liu; Gaoshan Zhang; Yanpeng Li; Xuexue Wu; Shuo Shang; Wenlu Che (Bioresource Technology, 2024)

The genetic basis and process of inbreeding depression in an elite hybrid rice - Xiaodong Xu; Yawen Xu; Jian Che; Xu Han; Zhengji Wang; Xianmeng Wang; Qinghua Zhang; Xu Li; Qinglu Zhang; Jinghua Xiao; Xianghua Li; Qifa Zhang; et al. (Science China Life Sciences, 2024)

Beneficial ecological networks dominate the dynamic root endosphere microbiome during long-term symbiosis with host plants - Jilu Che; Yaqiong Wu; Hao Yang; Wenlong Wu; Lianfei Lyu; Xiaomin Wang; Weilin Li (Plant and Soil, 2024)

Circ_0090231 knockdown protects vascular smooth muscle cells from ox-LDL-induced proliferation, migration and invasion via miR-942-5p/PPM1B axis during atherosclerosis - Jian Yang; Xiangyan Li; Yuming Zhang; Pengfei Che; Wei Qin; Xuecui Wu; Yue Liu; Bing Hu (Molecular and Cellular Biochemistry, 2024)

Impact of freeze–thaw process on soil temperature and water after long-term grassland and bare land in Northeast China - Haiyu Li; Meng Li; Renfeng Che; Junchen Zhou (Journal of Soils and Sediments, 2024)

Snow cover duration delays spring green-up in the northern hemisphere the most for grasslands - Xufeng Wang; Zongxing Li; Jingfeng Xiao; Gaofeng Zhu; Junlei Tan; Yang Zhang; Yingchun Ge; Tao Che (Agricultural and Forest Meteorology, 2024)

Phylogeny and genetic diversity of Echinometra sea urchin in Taiwan - Mei-Fang Lin; Ming-Che Yang; Yi-Yuan Lin; Sheng-Chi Chung; Li-Lian Liu (Marine Biology Research, 2024)

Optimizing terrestrial locomotion of undulating-fin amphibious robots: Asynchronous control and phase-difference optimization - Deliang Yu; Tianyu Che; Huibo Zhang; Chao Li; Cong Wang; Zhaotian Wang (Ocean Engineering, 2024)

Biogenic volatile organic compounds dominated the near-surface ozone generation in Sichuan Basin, China, during fall and wintertime - Dasheng Huang; Qing Li; Yan Han; Shi-Yong Xia; Jiawei Zhou; Hanxiong Che; Keding Lu; Fumo Yang; Xin Long; Yang Chen (Journal of Environmental Sciences, 2024)

Micro-helical Ni3Fe chain encapsulated in ultralight MXene/C aerogel to realize multi-functionality: Radar stealth, thermal insulation, fire resistance, and mechanical properties - Sen Lin; Jing Lin; Zhiqiang Xiong; Xue He; Xin Li; Chongbo Liu; Chengying Wang; Xiaojun Zeng; Xuliang Nie; Renchao Che (Chemical Engineering Journal, 2024)

Permafrost thawing caused by the China-Russia Crude oil pipeline based on multi-type data and its impacts on geomorphological reshaping and water erosion - Kai Gao; Guoyu Li; Yapeng Cao; Chunqing Li; Dun Chen; Gang Wu; Qingsong Du; Fei Wang; Fedorov Alexander; Fuqiang Che; Zhenrong Zhang; Luyao Bai; et al. (CATENA, 2024)

Dietary lipid supplementation alleviated the impacts of polystyrene nanoplastic exposure in Litopenaeus vannamei - Yiming Li; Yucong Ye; Haojuan Yuan; Siwen Li; Na Rihan; Xingguo Liu; Yunlong Zhao; Xuan Che (Aquatic Toxicology, 2024)

Simultaneous Improvement of Water/Fertility Retention and Physical Properties of Dredged Sediment Using a Novel Composite Amendment - Peishu Huo; Xiaori Fu; Zheng Che; Jingbo Liang; Dexiao Li; Yulong Liu; Shuguang Lyu (Water, Air, & Soil Pollution, 2024)

Heating and Water Transport Behavior of Sandstones Under Microwave Irradiation - Qinhua Zhao; Yanlong Zheng; Jianchun Li; Ping Che; Xiaobao Zhao (Rock Mechanics and Rock Engineering, 2024)

Effect of plasma activated water Immersion on Broccoli Seed Germination and Nutritional Quality of Sprouts - Gongheng Che; Ting Jiang; Xiaodan Li; Junxia Xiao; Liang Liu; Jianteng Wei; Liping Guo (Journal of Plant Growth Regulation, 2024)

Correlation of gut microorganisms and non-volatile flavor substances provides new insights for breeding Scylla paramamosain - Gao Gao; Xing Li; Kangxiang Qin; Yun Hu; Xiaosong Jiang; Chenxi Che; Yuntao Li; Changkao Mu; Chunlin Wang; Huan Wang (Journal of Oceanology and Limnology, 2024)

Vibration Suppression of Two Adjacent Cables Using an Interconnected Tuned Mass Damper/Nonlinear Energy Sink - Che Yao; Dejian Li; Xiaojun Wei (Journal of Marine Science and Engineering, 2024)
Due to their high flexibility, low damping, and small mass, stay cables are prone to large-amplitude vibrations. Various mechanical measures, typically installed near the cable anchorage to the deck, have been developed to suppress cable vibration. These dampers, however, may not be effective for ultralong cables since the damper is close to the cable anchorage, the cable node. In this paper, a tuned mass damper (TMD)/nonlinear energy sink (NES) are considered for installation between two adjacent stay cables for vibration mitigation. Firstly, the static equilibrium equation of the stay cable–damper system is established, and the influence of the self-weight of the damper on cable shape is investigated. The governing equations describing the motion of the two adjacent cables with a damper are then established using the Hamilton principle, which are then solved by the method of separation of variables. For cases of swept-sine excitation and harmonic excitation, the optimal designs of TMD and NES are achieved with the purpose of suppressing the first- and third-mode-dominated vibrations, respectively. Both optimal TMD and NES may substantially suppress cable vibrations, with each having advantages under certain situations. Finally, the dynamic response characteristics of two adjacent cables with an optimal damper are analyzed. Interesting dynamic behaviors, such as energy input suppression, phase shift, cable frequency shift, and phase diagram boundary rotation, are identified, and their mechanisms are explained.

Characterizing the 3-D structure of each building in the conterminous United States - Yangzi Che; Xuecao Li; Xiaoping Liu; Xucai Zhang (Sustainable Cities and Society, 2024)

Deciphering the functional importance of comammox vs. canonical ammonia oxidisers in nitrification and N2O emissions in acidic agricultural soils - Che Tan; Chang Yin; Lei Zhang; Yu Zeng; Cécile Gubry-Rangin; Hao Chen; Zixiang Gao; Hongyun Peng; Tingqiang Li; Yongchao Liang (Soil Biology and Biochemistry, 2024)

Novel magnetic N-doped biochar derived from sugarcane bagasse and red mud for effective adsorption of tetracycline hydrochloride - Linye Zhang; Jun Xiao; Huixian Che; Deyuan Xiong; Yanling Zhou; Baiying Li; Yi Liu; Guangtao Wei (Journal of Environmental Chemical Engineering, 2024)

Linearly interpolating missing values in time series helps little for land cover classification using recurrent or attention networks - Xianghong Che; Hankui K. Zhang; Zhongbin B. Li; Yong Wang; Qing Sun; Dong Luo; Hao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Developing Ni/SAPO-11 deoxygenation catalysts using yttrium modified SAPO-11 prepared by rice husk ash - Zitong Li; Peng Lu; Caina Song; Yutong Che; Xiaosheng Wang; Zhiwei Lyu; Yuxiang Liu (Fuel, 2024)

Insight into the autochthonous bacterial strains as starter cultures for improving the flavor profiles of dry-cured duck: Changes in microbial diversity and metabolic profiles - Xiao-min Li; Lie-hua Che; Wen-di Zhang; Qian-li Huang; Cong Li; Bao-cai Xu (Food Chemistry, 2024)

Cholesterol plus dietary tannins play a key role in formation of urinary stone - Yu Xi; Luyao Chen; Xiangquan Zeng; Tianyi Jiang; Shuang Yang; Xiangxin Li; Yuxia Ma; Dongdong Cao; Huilian Che; Weibo Jiang (Food Bioscience, 2024)

Sensitivity analysis of the WRF simulated planetary boundary layer height to synoptic conditions over eastern China - Yarong Li; Jianjun He; Jiming Li; Hong-Li Ren; Hong Wang; Wangjun Luo; Sunling Gong; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2024)

Report on the 4th Board Meeting of the International Human Phenome Consortium - Mei Tian; Han Liu; Shiwen Peng; Zhong Yang; Weishuo Tao; Huiting Che; Xuanxuan Gao; Li Jin (Phenomics, 2024)

Effects of Rhizosphere Microorganisms Associated with Suaeda Salsa on the Growth and Salt Stress Resistance of Alfalfa - Jinxia Chen; Qian Zhang; Xihu Qie; Yajuan Che; Dantong Lv; Yuxuan Gao; Fuhong Miao; Shuo Li; Feng He; Juan Sun; Chao Yang (Journal of Soil Science and Plant Nutrition, 2024)

On the use of EST-SSR to analysis the genetic diversity of segetale rye from China - Yonghe Che; Yanping Yang; Lai Wei; Yunjie Yang; Xiaolei Wen; Juan Guo; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Cereal Research Communications, 2024)

Geochemistry and Zircon U-Pb and Hf Isotopes of Early Devonian Hardawu Granites in the Eastern Segment of the Ultrahigh-Pressure Metamorphic Belt, Northern Qaidam Basin - Hua Li; Ming Wang; Jiqing Li; Haikui Tong; Jiaxiang Dong; Minggang Tian; Xiaolin Chen; Leguang Li; Ting Xie; Xiong Li; Yuying Che (Journal of Earth Science, 2024)

Experimental study on sewage collection and related performance of square arc angle aquaculture tank - Zonglong Che; Yinxin Zhou; Chenxu Zhao; Xiaozhong Ren; Hangfei Liu; Wei Sun; Haibo Liu; Meng Li (Aquaculture International, 2024)

Internal logic and driving path of enterprise green innovation performance improvement under TOE framework: based on linkage effect analysis of fsQCA and NCA - Lin Li; Wenjing Che (Environment, Development and Sustainability, 2024)

Nutrients addition decreases soil fungal diversity and alters fungal guilds and co-occurrence networks in a semi-arid grassland in northern China - Hongling Yang; Li Cheng; Limuge Che; YongZhong Su; Yulin Li (Science of The Total Environment, 2024)

Experimental investigation and numerical modeling of effect of specimen size on microwave-induced fracturing of diorite - Zhongjun Ma; Yanlong Zheng; Fuxin Rui; Gaofeng Zhao; Jianchun Li; Ping Che (Minerals Engineering, 2024)

Enhanced extraction of heavy metals from gypsum-based hazardous waste by nanoscale sulfuric acid film at ambient conditions - Wenjing Li; Chunli Wang; Guiquan Che; Min Su; Zhihao Zhang; Weizhen Liu; Zhang Lin; Jing Zhang (Journal of Hazardous Materials, 2024)

A pilot restoration of Enhalus acoroides by transplanting dislodged rhizome fragments and its effect on the microbial diversity of submarine sediments - Hu Li; Jianguo Liu; Litao Zhang; Xingkai Che; Mengjie Zhang; Tie Zhang (Journal of Environmental Management, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Heterointerface engineering in porous microspheres for magnetic-dielectric balance to boost electromagnetic wave absorption - Longjun Rao; ZhuoLin Li; Yuetong Qian; Mengqiu Huang; Lei Wang; Yongsheng Liu; Jincang Zhang; Yuxiang Lai; Chongyun Liang; Renchao Che (Chemical Engineering Journal, 2024)

Multifunctional Spirulina-hybrid helical microswimmers: Imaging and photothermal efficacy enabled by intracellular gold deposition - Ziqiao Li; Yanan Che; Ming Chen; Jing Hu; Pan He; Xiang Sun; Xiaozhen Wu; Youliang Yao; Huili Zheng; Gang Liu; Xiaohui Yan (Chemical Engineering Journal, 2024)

A novel catalytic/sterilization PV-Trombe wall system: Analysis on PV electrical and air purification performance in winter - Lei Che; Niansi Li; Miaomiao Fan; Guoji Zhang; Guoyu Zhang; Bendong Yu (Building and Environment, 2024)

Three-dimensional structure and transport flux of springtime smoke aerosols over the Indochina Peninsula - Yurun Liu; Ke Gui; Quanliang Chen; Liangliang Feng; Hongke Cai; Xutao Zhang; Wenrui Yao; Hengheng Zhao; Nanxuan Shang; Lei Li; Yu Zheng; Huizheng Che (Atmospheric Research, 2024)

Characterization of Organosulfates (OSs) in typical urban areas in Eastern China: Source, Process, and Volatility - Yang Du; Hanxiong Che; Zier Bao; Yiliang Liu; Qing Li; Miao Hu; Jiawei Zhou; Shumin Zhang; Xiaojiang Yao; Quan Shi; Chunmao Chen; Yan Han; et al. (Atmospheric Research, 2024)

Correction to: Novel FOXP2 variant associated with speech and language dysfunction in a Chinese family and literature review - Fengyu Che; Chenhao Li; Liyu Zhang; Chenxi Qian; Lidangzhi Mo; Benchang Li; Haibin Wu; Lifang Wang; Ying Yang (Journal of Applied Genetics, 2024)

Novel FOXP2 variant associated with speech and language dysfunction in a Chinese family and literature review - Fengyu Che; Chenhao Li; Liyu Zhang; Chenxi Qian; Lidangzhi Mo; Benchang Li; Haibin Wu; Lifang Wang; Ying Yang (Journal of Applied Genetics, 2024)

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Molecular characterization of the integrative and conjugative elements harbouring multidrug resistance genes in Glaesserella parasuis - Yongliang Che; Renjie Wu; Hongjie Li; Longbai Wang; Xuemin Wu; Qiuyong Chen; Rujing Chen; Lunjiang Zhou (Veterinary Microbiology, 2024)

Exposure to polystyrene nanoplastics induces apoptosis, autophagy, histopathological damage, and intestinal microbiota dysbiosis of the Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Haojuan Yuan; Na Rihan; Mingming Han; Xingguo Liu; Tian Zhu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Adsorption and accumulation of N2 at the solid–liquid interface: The impact of hydration films - Bao Li; Dan Su; Daochang Che; Lei Zhang; Shengyu Liu; Boris Albijanic (Minerals Engineering, 2024)

Metabolomics revealed more deleterious toxicity induced by the combined exposure of ammonia and nitrite on Ruditapes philippinarum compared to single exposure - Ming Cong; Zhaoshun Li; Yu Che; Yuanmei Li; Wenwen Tian; Jiasen Lv; Xiyan Sun (Marine Environmental Research, 2024)

Spatiotemporal comprehensive evaluation of water quality based on enhanced variable fuzzy set theory: A case study of a landfill in karst area - Yu Yang; Bo Li; Chaoyi Li; Pu Liu; Tao Li; Ye Luo; Lei Yang; Lulu Che; Menghua Li (Journal of Cleaner Production, 2024)

New insight into oxygen vacancy and synergism in CuCeOx catalysts based on the toluene oxidation - Guangtao Hu; Zirui Zhang; Chang’an Wang; Guojie Li; Dandan Zhou; Jinshi Wang; Defu Che; Running Kang (Journal of Environmental Chemical Engineering, 2024)

An effective strategy for improving the freeze-drying survival rate of Lactobacillus curvatus and its potential protective mechanism - Xiao-min Li; Lie-hua Che; Ying Wu; Cong Li; Bao-cai Xu (Food Bioscience, 2024)

Adsorption and enrichment of low-concentration heavy metal complexes by retractable claws made of polyelectrolyte brushes - Guiquan Che; Zhihao Zhang; Wenjing Li; Min Su; Chunli Wang; Zhengping Hao; Jing Zhang (Chemical Engineering Journal, 2024)

A Ketogenic Diet may Improve Cognitive Function in Rats with Temporal Lobe Epilepsy by Regulating Endoplasmic Reticulum Stress and Synaptic Plasticity - Qi Qiao; Shuang Tian; Yuan Zhang; Liqin Che; Qing Li; Zhenzhen Qu; Weiping Wang (Molecular Neurobiology, 2024)

Surfeit Locus Protein 4 as a Novel Target for Therapeutic Intervention in Cerebral Ischemia–Reperfusion Injury - Wenjie Hu; Xiangyi Kong; Yu Cui; Hui Wang; Jingchen Gao; Xiyuran Wang; Shujun Chen; Xiaohua Li; Shifang Li; Fengyuan Che; Qi Wan (Molecular Neurobiology, 2024)

Soil microbial subcommunity assembly mechanisms are highly variable and intimately linked to their ecological and functional traits - Qiuping Fan; Kaifang Liu; Zelin Wang; Dong Liu; Ting Li; Haiyan Hou; Zejin Zhang; Danhong Chen; Song Zhang; Anlan Yu; Yongcui Deng; Xiaoyong Cui; et al. (Molecular Ecology, 2024)
Revealing the mechanisms underlying soil microbial community assembly is a fundamental objective in molecular ecology. However, despite increasing body of research on overall microbial community assembly mechanisms, our understanding of subcommunity assembly mechanisms for different prokaryotic and fungal taxa remains limited. Here, soils were collected from more than 100 sites across southwestern China. Based on amplicon high‐throughput sequencing and iCAMP analysis, we determined the subcommunity assembly mechanisms for various microbial taxa. The results showed that dispersal limitation and homogenous selection were the primary drivers of soil microbial community assembly in this region. However, the subcommunity assembly mechanisms of different soil microbial taxa were highly variable. For instance, the contribution of homogenous selection to Crenarchaeota subcommunity assembly was 70%, but it was only around 10% for the subcommunity assembly of Actinomycetes, Gemmatimonadetes and Planctomycetes. The assembly of subcommunities including microbial taxa with higher occurrence frequencies, average relative abundance and network degrees, as well as wider niches tended to be more influenced by homogenizing dispersal and drift, but less affected by heterogeneous selection and dispersal limitation. The subcommunity assembly mechanisms also varied substantially among different functional guilds. Notably, the subcommunity assembly of diazotrophs, nitrifiers, saprotrophs and some pathogens were predominantly controlled by homogenous selection, while that of denitrifiers and fungal pathogens were mainly affected by stochastic processes such as drift. These findings provide novel insights into understanding soil microbial diversity maintenance mechanisms, and the analysis pipeline holds significant value for future research.

Novel Multiplexed High Throughput Screening of Selective Inhibitors for Drug-Metabolizing Enzymes Using Human Hepatocytes - Jianhua Liu; Daria Vernikovskaya; Gary Bora; Anthony Carlo; Woodrow Burchett; Samantha Jordan; Lloyd Wei Tat Tang; Joy Yang; Ye Che; George Chang; Matthew D. Troutman; Li Di (The AAPS Journal, 2024)

A novel iron sulfide phase with remarkable hydroxyl radical generation capability for contaminants degradation - Chunli Wang; Wenjing Li; Zhihao Zhang; Dashi Lei; Guiquan Che; Chunli Gou; Jing Zhang; Zhengping Hao (Water Research, 2024)

Adsorption of phosphate onto agricultural waste biochars with ferrite/manganese modified-ball-milled treatment and its reuse in saline soil - Naiju Che; Jie Qu; Jiaqi Wang; Na Liu; Chengliang Li; Yanli Liu (Science of The Total Environment, 2024)

Characterization of risks and pathogenesis of respiratory diseases caused by rural atmospheric PM2.5 - Ronghua Zhang; Xiaomeng Li; Xuan Li; Qin Zhang; Jiancai Tang; Zhenzhong Liu; Guiqin Song; Li Jiang; Fumo Yang; Jiawei Zhou; Hanxiong Che; Yan Han; et al. (Science of The Total Environment, 2024)

Numerical research on the hydrodynamic effect on the leakage of two-phase refrigerant-oil mixture in the flank gaps of compressors - Che Wang; Hua Zhong; Shuai Zhang; Jiajin Li; Bowen Lei; Jianhua Wu (International Journal of Refrigeration, 2024)

Common vetch intercropping with reduced irrigation ensures potato production by optimizing microbial interactions - Ting Che; Xinyue Zhang; Mingyue He; Fei Wang; Na Li; Xiayun Zang; Zhuoliang Xiao; Yuanzhou Xu; Feng Hu; Yongfeng Ren; Huijuan Zhang; Li Xu; et al. (Field Crops Research, 2024)

Vegetable residues retention: An effective and environment friendly way to handle tomato wastes from greenhouse production - Xiaomei Sun; Sijin Chen; Huan Li; Jinxia Li; Guojun Han; Haobing Dong; Jiangwei Che; Qin Zhang (European Journal of Soil Biology, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

Quantitative study on the relationships between smog and online reviews from the perspective of risk perception - Qiang Li; Xiaona Guo; Veselin Krustev; Jianming Miao; Heli Lu; Jiangping Qiu; Shengquan Che (Environmental Impact Assessment Review, 2024)

Three-Dimensional Tetrathiafulvalene-Based covalent organic frameworks for efficient photocatalytic nitrogen fixation - Yunchao Ma; Liaofang Shang; Jingyang Li; Yuanyuan Wu; Guangbo Che; Chunbo Liu; Qianrong Fang (Chemical Engineering Journal, 2024)

Capturing aqueous uranyl ions into catalytic nanometric shells of liquid metal droplets for electrochemical reduction - Zhuanzhuan Zhai; Lifen Long; Xinpeng Che; Bailang Zhang; Ting Wang; Mingjie Li; Chaoxu Li (Chemical Engineering Journal, 2024)

Green manuring relocates microbiomes in driving the soil functionality of nitrogen cycling to obtain preferable grain yields in thirty years - Guopeng Zhou; Kunkun Fan; Songjuan Gao; Danna Chang; Guilong Li; Ting Liang; Hai Liang; Shun Li; Jiudong Zhang; Zongxian Che; Weidong Cao (Science China Life Sciences, 2024)

Post-transcriptional regulation of myogenic transcription factors during muscle development and pathogenesis - Shen-Liang Chen; Chuan-Che Wu; Ning Li; Tzu-Han Weng (Journal of Muscle Research and Cell Motility, 2024)

Characterization of CYP3A5 Selective Inhibitors for Reaction Phenotyping of Drug Candidates - Jie Chen; Lloyd Wei Tat Tang; Samantha Jordan; Makayla Harrison; Gabrielle M. Gualtieri; Ethan DaSilva; Danial Morris; Gary Bora; Ye Che; Li Di (The AAPS Journal, 2024)

ICEEMDAN/LOESS: An Improved Vibration-Signal Analysis Method for Marine Atomic Interferometric Gravimetry - Jinxiu Ma; An Li; Fangjun Qin; Wenbin Gong; Hao Che (Journal of Marine Science and Engineering, 2024)
The marine atomic interferometric gravimeter is a vital precision instrument for measuring marine geophysical information, which is widely used in mineral resources exploration, military applications, and missile launches. In practical measurements, vibration disturbance is an important factor that affects measurement accuracy. This paper proposes the combination of improved complete ensemble empirical mode decomposition with adaptive noise and locally weighted regression for vibration characterization of gravimeter vibration data. Firstly, the original signal is added into a pair of white noise for adaptive noise-complete ensemble empirical mode decomposition to obtain multiple intrinsic mode functions. The efficient IMF components and noise components are filtered out under the dual indicators of correlation coefficient and variance contribution ratio, and then the LOESS filtering method is used for noise reduction to obtain useful signal detail information; finally, the noise-containing components are reconstructed with the effective components after the noise-reduction process. The experimental results of both simulated and measured vibration signals show that the proposed method can effectively decompose the different high- and low-frequency bands contained in the vibration signal and remove the noise of the original signal.

Cerebral neurotoxicity of amino-modified polystyrene nanoplastics in mice and the protective effects of functional food Camellia pollen - Hangjia Bai; Yanliang Wu; Haini Li; Yining Zhu; Ruijie Che; Fenghe Wang; Chaofeng Zhang (Science of The Total Environment, 2024)

Columnar optical-radiative properties and components of aerosols in the Arctic summer from long-term AERONET measurements - Yuanxin Liang; Huizheng Che; Xindan Zhang; Lei Li; Ke Gui; Yu Zheng; Xutao Zhang; Hengheng Zhao; Peng Zhang; Xiaoye Zhang (Science of The Total Environment, 2024)

Polystyrene nanoplastics exposure alters muscle amino acid composition and nutritional quality of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Effects of short and long-term thermal exposure on microbial compositions in soils contaminated with mixed benzene and benzo[a]pyrene: A short communication - Mukhtiar Ali; Xin Song; Qing Wang; Zhuanxia Zhang; Meng Zhang; Min Ma; Jilu Che; Rui Li; Xing Chen; Zhiwen Tang; Biao Tang; Xiangfeng Huang (Science of The Total Environment, 2024)

A comprehensive review on the source, ingestion route, attachment and toxicity of microplastics/nanoplastics in human systems - Yining Zhu; Ruijie Che; Xinyan Zong; Jinhan Wang; Jining Li; Chaofeng Zhang; Fenghe Wang (Journal of Environmental Management, 2024)

Multi-sensor integrated mapping of global XCO2 from 2015 to 2021 with a local random forest model - Jiabin Chen; Ruohua Hu; Leyan Chen; Zihao Liao; Linlin Che; Tongwen Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Preparation and characteristic analysis of graphene based on coal macerals of different rank - Pengliang Ma; Yuegang Tang; Ruiqing Li; Qili Che; Peng Luo (Fuel, 2024)

Catalytic gasification of large particle-size biomass with loaded AAEMs under oxygen-steam atmosphere - Jiyun Ren; Kaixuan Yang; Yuhang Li; Yang Bai; Jiahao Jiang; Xiaole Huang; Lei Deng; Defu Che (Fuel, 2024)

The mechanism of photothermal catalytic reforming of biomass tar: An exploratory study based on density functional theory - Beibei Yan; Tianxiao Yu; Jian Li; Xiaopeng Jia; Zhiyu Li; Yuechi Che; Guanyi Chen; Juan Zhao (Fuel, 2024)

Evaluation of MERRA-2 and CAMS reanalysis for black carbon aerosol in China - Weijie Li; Yaqiang Wang; Ziwei Yi; Bin Guo; Wencong Chen; Huizheng Che; Xiaoye Zhang (Environmental Pollution, 2024)

N atoms regulate heterogeneous crystal phase engineering of mesoporous magnetic FexN nanofibers to promote electromagnetic wave dissipation of magnetic composite aerogel absorbers - Wanjia Li; Wangchang Li; Zengbao Ma; Yue Kang; Ting Zou; Yu Lei; Yao Ying; Wenbo Xiang; Jing Yu; Jingwu Zheng; Liang Qiao; Juan Li; et al. (Chemical Engineering Journal, 2024)

The impact of aerosol-cloud interaction on mesoscale numerical weather prediction when low-cloud and haze coexist in winter over major polluted regions of China - Wenjie Zhang; Hong Wang; Xiaoye Zhang; Yue Peng; Zhaodong Liu; Junting Zhong; Siting Li; Huizheng Che (Atmospheric Environment, 2024)

Using a Laboratory Column Experiment to Explore the Influence of an Antecedent Dry Period on the Nutrient Removal of a Bioretention Filter - Wei Zhang; Zimeng Zhuang; Juan Li; Huichao Sun; Wu Che (Water, Air, & Soil Pollution, 2024)

Dung-soil microbial community coalescence can exert dual effects on alpine grasslands through changing soil microbiomes - Dong Liu; Zelin Wang; Kaifang Liu; Song Zhang; Feiling Yang; Jie Li; Feng Liu; Da Bao; Rongxiao Che (Journal of Soils and Sediments, 2024)

Glycerol changes the growth and lipid profile of the marine microalga Isochrysis galbana via the regulation of photosynthetic and respiratory metabolic pathways - Feifei Yang; Wenhao Liu; Yongfu Li; Xingkai Che; Shuchen Liu (Journal of Applied Phycology, 2024)

Anthropogenic nitrogen pollution inferred by stable isotope records of crustose coralline algae - Aafaq Nazir; Chiao-Feng Lai; Shih-Wei Wang; Showe-Mei Lin; Hong-Chun Li; Ming-Tsung Chung; Pei-Ling Wang; Yung-Che Tseng; Jen-Chieh Shiao (Marine Pollution Bulletin, 2024)

Influences of hydrodynamics on microbial community assembly and organic carbon composition of resuspended sediments in shallow marginal seas - Yangli Che; Chaoran Lin; Shen Li; Jiao Liu; Longhai Zhu; Shilei Yu; Nan Wang; Haoshuai Li; Mutai Bao; Yang Zhou; Tonghao Si; Rui Bao (Water Research, 2024)

Analysis of the spatiotemporal changes in global land cover from 2001 to 2020 - Qiaoqiao Jing; Jianjun He; Yarong Li; Xianyu Yang; Yue Peng; Hong Wang; Fei Yu; Jie Wu; Sunling Gong; Huizheng Che; Xiaoye Zhang (Science of The Total Environment, 2024)

Polystyrene nanoplastics induce lipid metabolism disorder and alter fatty acid composition in the hepatopancreas of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Comprehensive energy, exergy, and economic analyses of a geothermal and flue gas-based dual-source power, hydrogen, and freshwater trigeneration system - Li Bian; Xiangqian Che; Arivalagan Pugazhendhi (Process Safety and Environmental Protection, 2024)

In situ preparation of biochar/Bi4O5Br2 composite for ibuprofen removal under the synergistic effect of adsorption and photocatalysis and the underlying mechanism - Huanxian Shi; Yumiao Zhang; Yueyue Wei; Chen Che; Zhanyang Xia; Guolong Li; Xiaofei Zhang; Yajun Shi; Zhishu Tang (Journal of Water Process Engineering, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Where are the critical points of water transfer impact on grain production from the middle route of the south-to-north water diversion project? - Lingling Zhang; Li Che; Zongzhi Wang (Journal of Cleaner Production, 2024)

Study on the water-carbon coupling coordination function on the eastern edge of the Qinghai-Tibet plateau - Xin Yuan; Liang Jiao; Xichen Che; Jingjing Wu; Xuli Zhu; Qian Li (Ecological Modelling, 2024)

Aerosol optical and radiative properties and their environmental effects in China: A review - Huizheng Che; Xiangao Xia; Hujia Zhao; Lei Li; Ke Gui; Yu Zheng; Jingjing Song; Bing Qi; Jun Zhu; Yucong Miao; Yaqiang Wang; Zhili Wang; et al. (Earth-Science Reviews, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

A Numerical Simulation Study and Effectiveness Evaluation on the Flow Field Effect of Trapezoidal Artificial Reefs in Different Layouts - Xiaolong Chen; Xuan Che; Yin Zhou; Changfeng Tian; Xinfeng Li (Journal of Marine Science and Engineering, 2023)
The combined release of artificial reefs in different quantities and arrangements leads to different flow field effects. This study designs a small trapezoidal artificial reef. To optimize the quantity and layout of these reefs, trapezoidal reefs in three different layouts were selected for analysis at five different velocity gradients (0.1, 0.5, 1.0, 1.5, and 2.0 m/s). The effects of disposal spacing and layout on the flow field effect of trapezoidal artificial reefs at different flow velocities were simulated using Ansys Fluent. According to the findings: after simulation, flow velocity could indirectly reflect the distribution of upwelling and back eddy, the scale and strength of upwelling increased as flow velocity increased, and the back eddy showed no obvious variation with flow velocity. In transverse combination mode, both the scale and strength of the upwelling and back eddy were maximized when the reef spacing was 1.0 L; in longitudinal combination mode, upwelling and back eddy reached maximum scale and strength when the disposal spacing of the reefs was 1.5 L of a single reef. In 2020, flow mapping and fishery surveys were carried out in the engineering pilot area. The results showed that the number and species of fish populations with 1.5 L spacing in the vertical combination method were significantly higher than those in other forms, and the structure of the fish reef was stable without any flipping or sliding phenomenon. This study can provide a theoretical reference for the design and the actual deployment of artificial reefs to improve the ecological restoration of the water.

Thermal bleaching in the northern South China Sea: impact of abnormal environment and climate on high-latitude coral reefs - Xin Wang; Yinqiang Li; Mingqing Lin; Zhiwei Che; Weihua Mo; Yanli Chen; Shaohua Mo; Wentao Niu; Haolang Zhou (Environmental Science and Pollution Research, 2023)

Migration and adsorption of naphthalene in road-deposited sediments from stormwater runoff: Impact of the particle size - Hongze Liu; Fuguo Qiu; Mingchen Gao; Yongjian Che; Chaohong Tan; Ziyang Zhang; Rui Yan; Haiyan Li; Meipeng Jian (Science of The Total Environment, 2023)

Uptake, transport and accumulation of micro- and nano-plastics in terrestrial plants and health risk associated with their transfer to food chain - A mini review - Yongqiang Liu; Yue Ben; Ruijie Che; Chunqing Peng; Jining Li; Fenghe Wang (Science of The Total Environment, 2023)

Quantitative proteomics reveals the neurotoxicity of trimethyltin chloride on mitochondria in the hippocampus of mice - Zhenzhong Liu; Li Wang; Yue Wang; Siya Wu; Caiting Peng; Yu Wang; Ming Huang; Li Che; Rongjing Sun; Xi Zhao; Zuo Du; Wenhu Liu (NeuroToxicology, 2023)

Oxidative stress responses of the scleractinian coral Acropora digitifera from the tropical Bidong Island, Malaysia - focus on protein thiol groups' detection - Muhammad Arif Samshuri; Che Din Mohd Safuan; Siti Nurtahirah Jaafar; Chui Pin Leaw; Li Keat Lee; Mathinee Yucharoen; Zainudin Bachok (Journal of Experimental Marine Biology and Ecology, 2023)

Decarbonization potential collaborated with source industries for China's iron and steel industry towards carbon neutrality - Jingchao Sun; Ziyang Qiu; Yuxing Yuan; Zichang Che; Lei Zhang; Tao Du; Hongming Na; Yingnan Li (Journal of Cleaner Production, 2023)

Relative contributions of ambient air and internal sources to multiple air pollutants in public transportation modes - Zhiyuan Li; Wenwei Che; Md Shakhaoat Hossain; Jimmy C.H. Fung; Alexis K.H. Lau (Environmental Pollution, 2023)

Degradation of perfluorooctanoic acid (PFOA) using multiphase fenton-like technology by reduced graphene oxide aerogel (rGAs) combined with BDD electrooxidation - Yinhui Li; Naiju Che; Na Liu; Chengliang Li (Chemical Engineering Journal, 2023)

Multisite evaluation of physics-informed deep learning for permafrost prediction in the Qinghai-Tibet Plateau - Yibo Liu; Youhua Ran; Xin Li; Tao Che; Tonghua Wu (Cold Regions Science and Technology, 2023)

From cellulose to tar: Analysis of tar formation pathway with distinguishing the primary and secondary reactions - Xiaopeng Jia; Yuechi Che; Jian Li; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Juan Zhao (Bioresource Technology, 2023)

Study on the Mechanism of Eerdun Wurile’s Effects on Post-operative Cognitive Dysfunction by the TLR4/NF-κB Pathway - Yun Qiao; Huiru Li; Yan Li; Enboer Su; Zhe Wang; Limuge Che; Yiri Du (Molecular Neurobiology, 2023)
The object of our work was to observe whether the Mongolian medicine Eerdun Wurile (EW) improve postoperative cognitive dysfunction (POCD) by affecting the TLR4/NF-κB. Mice (6–8-week-old male C57BL/6 J) were selected to establish an animal model of POCD by combining intracerebroventricular injection of lipopolysaccharide and nephrectomy; EW formulation and EW basic formulation were administered intra-gastrically for 7 consecutive days. The cognitive performance was assessed by Morris water maze test. H&E staining was examined to detect alterations in hippocampal tissue. Immunohistochemical staining was performed to evaluate MyD88, NF-κB, TLR4, iNOS, and IBA-1 expressions; Western blotting and RT-qPCR were performed to evaluate MyD88, NF-κB, and TLR4. The expressions of IL-6, IL-1β, and TNF-α were evaluated by ELISA. Intracerebroventricular injection of lipopolysaccharide combined with nephrectomy induced cognitive dysfunction in mice, stimulated TLR4/NF-κB and microglia, and promoted the secretion of murine TNF-α, IL-1β, and IL-6. EW formulation and EW basic formulation treatment are able to suppress the TLR4/NF-κB pathway activation and microglia, and the serum cytokine secretions related to proinflammation, and restore the cognitive performance. EW formulation and EW basic formulation can improve POCD in mice, and TLR4/NF-κB pathway seems to be one of the important mechanisms in EW’s improvement of POCD.

Relationship between night shift and sleep problems, risk of metabolic abnormalities of nurses: a 2 years follow-up retrospective analysis in the National Nurse Health Study (NNHS) - Heli Zhang; Jingpin Wang; Siwei Zhang; Sumei Tong; Jinping Hu; Ying Che; Lin Zhuo; Peng Wang; Rongmei Geng; Yujie Zhou; Panfeng Wang; Siyan Zhan; et al. (International Archives of Occupational and Environmental Health, 2023)
Background and purpose Efforts to improve nurses’ physical and mental health are critical to ensuring the safety and quality of the healthcare system. Long-term studies targeting the relevancy of nurses’ occupation characteristics with health conditions remain insufficient. This study aimed to examine the relationship between nurses’ night shift and sleep problems and metabolic abnormalities risk. Methods This study was a part of the National Nurse Health Study, an ambispective cohort study in China, in 2021. Based on an integration physical examination data system, this study carried out a retrospective analysis of 730 nurses from 2018 to 2020 and combined with a questionnaire survey in 2021. The STROBE guidelines were adopted for reporting. Results In the 23 (23.0, 24.0) months follow-up, higher night shift load was associated with more sleep problems such as shortened sleep duration, sleep disorders, poor sleep quality, and sleep deprivation. Moreover, night shift load was associated with chronic diseases risk factors, increasing body mass index and body fat, with more night shift density, increasing the occurrence of low levels of high-density lipoprotein cholesterol, high triglyceride, triglyceride/high-density lipoprotein cholesterol ratio, and serum uric acid. Conclusion The night shift load has become an occupational health concern, contributing to chronic diseases relevant metabolic risk factors and negative influence on sleep health. Focus on the strategies to improve the sleep quality of nurses undergoing night shift work, optimize work scheduling and ongoing monitor the relevant risk factors are essential to enhance the stability and well-being of the nursing workforce. Clinical Trials registration information: NCT04572347, on October 1, 2020. https://www.clinicaltrials.gov/ct2/show/NCT04572347

Experimental study on multi-scale damage and deterioration mechanism of carbonaceous slate under freeze-thaw cycles - Hanqing Lu; Weixing Bao; Yan Yin; Xun Sun; Huizhou Li; Zhenhua Pan; Bowen Che (Bulletin of Engineering Geology and the Environment, 2023)

Effects of extra-extreme precipitation variability on multi-year cumulative nitrous oxide emission in a semiarid grassland - Linfeng Li; Yanbin Hao; Weijin Wang; Joel A. Biederman; Zhenzhen Zheng; Yanfen Wang; Muyesaier Tudi; Ruyan Qian; Biao Zhang; Rongxiao Che; Xiaoning Song; Xiaoyong Cui; et al. (Agricultural and Forest Meteorology, 2023)

The microbial mechanisms by which long-term heavy metal contamination affects soil organic carbon levels - Zhineng Xiao; Changqun Duan; Shiyu Li; Ji Chen; Changhui Peng; Rongxiao Che; Chang'e Liu; Yin Huang; Runran Mei; Liangliang Xu; Pengfei Luo; Yadong Yu (Chemosphere, 2023)

Real-time observation of magnetization and magnon dynamics in a two-dimensional topological antiferromagnet MnBi2Te4 - F. Michael Bartram; Meng Li; Liangyang Liu; Zhiming Xu; Yongchao Wang; Mengqian Che; Hao Li; Yang Wu; Yong Xu; Jinsong Zhang; Shuo Yang; Luyi Yang (Science Bulletin, 2023)

Structural characteristics variations of dough incorporated with long-chain inulin modified by phosphorylation - Yingyu Zhao; Denglin Luo; Chonghui Yue; Libo Wang; Peiyan Li; Zhouya Bai; Jiaxin Che (Journal of Cereal Science, 2023)

Effect of bio-chemical changes due to conventional ageing or chemical soaking on the texture changes of common beans during cooking - Li Zhu; Asanji Jean Claude Che; Clare Kyomugasho; Dongyan Chen; Marc Hendrickx (Food Research International, 2023)

Transcriptomic analysis of the antioxidant responses and immunomodulatory effects of dietary melatonin in red swamp crayfish (Procambarus clarkii) - Yiming Li; Yucong Ye; Siwen Li; Jianbin Feng; Xingguo Liu; Xuan Che; Qichen Jiang; Xiaolong Chen (Fish & Shellfish Immunology, 2023)

Investigation on Pb2+ adsorption characteristics by AAEMs-rich biochar in aqueous solution: Performance and mechanism - Jiahao Jiang; Ruiyu Li; Kaixuan Yang; Yuhang Li; Lei Deng; Defu Che (Environmental Research, 2023)

In situ growth of polydopamine modified ZIF-L arrays on air-laid paper as flexible evaporator for efficient solar desalination - Long Cheng; Linzhi Zuo; Shitan Yan; Jiubing Shen; Chengping Li; Yiting Che; Liang Wang; Romanov Anton; Ting Bian (Desalination, 2023)

Sustainable utilization of anthraquinone-rich Rheum officinale as electron shuttle in microbial fuel cell: Strategy for stimulating monohydric phenols degradation and bioelectricity generation - Sing-Mei Tan; Li-Ngee Ho; Yee-Shian Wong; Che Zulzikrami Azner Abidin; Soon-An Ong (Chemical Engineering Journal, 2023)

Ultrafine particles in urban settings: A combined study of volatility and effective density revealed by VT-DMA-APM - Che-An Wu; Yu-Ting Chen; Li-Hao Young; Po-Kai Chang; Li-Ti Chou; Albert Y. Chen; Ta-Chih Hsiao (Atmospheric Environment, 2023)

Analysis and comparison of airflow-respirable dust control and innovative ventilation environment in drilling construction tunnels - Jinnan Guo; Angui Li; Ran Gao; Yicun Hou; Tianqi Wang; Jiaxing Li; Yifei Yin; Lunfei Che (Atmospheric Pollution Research, 2023)

tDCS Regulates ASBT-3-OxoLCA-PLOD2-PTEN Signaling Pathway to Confer Neuroprotection Following Rat Cerebral Ischemia-Reperfusion Injury - Xiangyi Kong; Xujin Yao; Jinyang Ren; Jingchen Gao; Yu Cui; Jiangdong Sun; Xiangyu Xu; Wenjie Hu; Hui Wang; Huanting Li; Oleg O. Glebov; Fengyuan Che; et al. (Molecular Neurobiology, 2023)

Study of screening, transport pathway, and vasodilation mechanisms on angiotensin-I converting enzyme inhibitory peptide from Ulva prolifera proteins - Zhiyong Li; Yuan He; Hongyan He; Caiwei Fu; Mengru Li; Aiming Lu; Dongren Zhang; Tuanjie Che; Songdong Shen (Acta Oceanologica Sinica, 2023)

Decision-theoretic rough set model and spatial analysis-based waste-to-energy incineration plant site selection: a case study in first-tier cities of China - Xuelan Zhang; Jiaheng Kang; Yue Che; Xiran Cao; Peize Li (Environmental Science and Pollution Research, 2023)

Elemental sulfur-driven autotrophic denitrification process for effective removal of nitrate in mariculture wastewater: Performance, kinetics and microbial community - Lu Wang; Jun Liu; Yongfu Li; Zhihao Liu; Long Zhang; Hong Che; Hongwu Cui; Ying Zhang (Chemosphere, 2023)

Real-world emission characteristics and inventory of volatile organic compounds originating from construction and agricultural machinery - Hongqian Che; Xianbao Shen; Zhiliang Yao; Bobo Wu; Runling Gou; Xuewei Hao; Xinyue Cao; Xin Li; Hanyu Zhang; Siwen Wang; Zhenyi Chen (Science of The Total Environment, 2023)

Quantifying the contribution of local drivers to observed weakening of spring dust storm frequency over northern China (1982–2017) - Ke Gui; Huizheng Che; Wenrui Yao; Yu Zheng; Lei Li; Linchang An; Hong Wang; Yaqiang Wang; Zhili Wang; Hong-Li Ren; Junying Sun; Jian Li; et al. (Science of The Total Environment, 2023)

A review of treatment technologies for acid mine drainage and sustainability assessment - Yu Yang; Bo Li; Tao Li; Pu Liu; Beibei Zhang; Lulu Che (Journal of Water Process Engineering, 2023)

An efficiency-driven approach for global ecological industrial parks - Shih-Fang Lo; Wen-Min Lu; Che-Wei Chang; Shiu-Wan Hung; Li-Ling Yang (Journal of Cleaner Production, 2023)

Petrology and mineralogy of the martian olivine gabbroic shergottite Northwest Africa 13581: Insights into the enriched martian mantle source - Yunhua Wu; Weibiao Hsu; Shiyong Liao; Zhiyong Xiao; Xiaochao Che; Lili Pan; Ye Li; Shaolin Li (Geochimica et Cosmochimica Acta, 2023)

Development of a recurrent spatiotemporal deep-learning method coupled with data fusion for correction of hourly ozone forecasts - Jie Li; Ji-cheng Jang; Yun Zhu; Che-Jen Lin; Shuxiao Wang; Jia Xing; Xinyi Dong; Jinying Li; Bin Zhao; Bingyao Zhang; Yingzhi Yuan (Environmental Pollution, 2023)

Strong variation of near-surface seismic anisotropy in Taiwan and its geological implications - Hsin-Yu Lee; Yuancheng Gung; Li-Wei Chen; Wen-Shan Chen; Ying-Nien Chen; Sheng-Jyun Cai; Hui-Chu Chen; Che-Wei Liao (Earth and Planetary Science Letters, 2023)

Photocatalysis-PMS oxidation system based on CQDs-doped carbon nitride nanosheets for degradation of residual drugs in water - Yongqiang Wang; Yibo Bai; Che Han; Zaimei Li; Xiaowen Lun; Conglu Zhang (Environmental Science and Pollution Research, 2023)

Dendrobium officinale polysaccharides improved reproductive oxidative stress injury in male mice treated with cyclophosphamide - Yi Mu; Bangwei Che; Kaifa Tang; Wenjun Zhang; Shenghan Xu; Wei Li; Jun He; Miao Liu; Peng Chen; Siwen Zhong; Guangyu Li (Environmental Science and Pollution Research, 2023)

High-quality images and data augmentation based on inverse projection transformation significantly improve the estimation accuracy of biomass and leaf area index - Yingpu Che; Qing Wang; Ziwen Xie; Shilin Li; Jinyu Zhu; Baoguo Li; Yuntao Ma (Computers and Electronics in Agriculture, 2023)

Evolutions of dissolved organic matter and disinfection by-products formation in source water during UV-LED (275 nm)/chlorine process - Xiating Zhao; Chuze Chen; Haoran Chen; Yaxin Guo; Xueqi Zhang; Mengting Li; Liu Cao; Yuting Wang; Tingting Gong; Lei Che; Guoying Yang; Qiming Xian (Water Research, 2023)

Polystyrene nanoplastics decrease nutrient accumulation, disturb sex hormones, and inhibit reproductive development in juvenile Macrobrachium nipponense - Yiming Li; Yucong Ye; Na Rihan; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

A portable and intelligent logic detector for simultaneous and in-situ detection of Al3+ and fluoride in groundwater - Huachao Che; Xike Tian; Jiahuan Wang; Chu Dai; Yulun Nie; Yong Li; Liqiang Lu (Journal of Hazardous Materials, 2023)

Techno-economic assessment and exergy analysis of iron and steel plant coupled MEA-CO2 capture process - Yuhang Yang; Tao Du; Yingnan Li; Qiang Yue; Heming Wang; Liying Liu; Shuai Che; Yisong Wang (Journal of Cleaner Production, 2023)

Reforestation substantially changed the soil antibiotic resistome and its relationships with metal resistance genes, mobile genetic elements, and pathogens - Song Zhang; Ting Li; Jinming Hu; Kexin Li; Dong Liu; Haixia Li; Fang Wang; Danhong Chen; Zejin Zhang; Qiuping Fan; Xiaoyong Cui; Rongxiao Che (Journal of Environmental Management, 2023)

A theoretical and applied convective heat transfer model for deep-buried underground tunnels with non-constant wall temperature - Jinnan Guo; Angui Li; Yuanqing Ma; Jigang Che; Jiaxing Li; Shaofeng Niu; Lianhua Deng; Duo Wang; Lunfei Che (Energy and Buildings, 2023)

Decomposition of meteorological and anthropogenic contributions to near-surface ozone trends in Northeast China (2013–2021) - Nanxuan Shang; Ke Gui; Hujia Zhao; Wenrui Yao; Hengheng Zhao; Xinglu Zhang; Xutao Zhang; Lei Li; Yu Zheng; Zhili Wang; Yaqiang Wang; Huizheng Che; et al. (Atmospheric Pollution Research, 2023)

Detection and quantitative analysis of tumor-associated tertiary lymphoid structures - Man Yang; Yurou Che; Kezhen Li; Zengyi Fang; Simin Li; Mei Wang; Yiyao Zhang; Zhu Xu; Liping Luo; Chuan Wu; Xin Lai; Weidong Wang (Journal of Zhejiang University-SCIENCE B, 2023)

Response of soil physicochemical properties, soil nutrients, enzyme activity and rice yield to rice straw returning in highly saline-alkali paddy soils - Weikang Che; Junlong Piao; Qian Gao; Xuebin Li; Xiang Li; Feng Jin (Journal of Soil Science and Plant Nutrition, 2023)

Characterization of SARS-COV-2 main protease inhibitory peptides from Ulva prolifera proteins - Zhiyong Li; Yehua Wang; Caiwei Fu; Dongren Zhang; Tuanjie Che; Songdong Shen (Journal of Oceanology and Limnology, 2023)

CEEMD-LASSO-ELM nonlinear combined model of air quality index prediction for four cities in China - Suling Zhu; Peiqi Wang; Ruyi Wang; Min Li; Jinxing Che; Xinlu Wang (Environmental and Ecological Statistics, 2023)

Electric-field control of reversible electronic and magnetic transitions in two-dimensional oxide monolayer magnets - Guopeng Wang; Tao Hu; Yimin Xiong; Xue Liu; Shengchun Shen; Jianlin Wang; Mengqian Che; Zhangzhang Cui; Yingying Zhang; Luyi Yang; Zhengcao Li; Yalin Lu; et al. (Science Bulletin, 2023)

Proteome changes in Neck-arm restraint and Achilles tendon suspensions during early post-mortem aging in cattle - Wentao Cai; Zezhao Wang; Kaixin Wen; Hongbo Li; Cong Qian; Leijie Che; Haijun Zhang; Yang Zhang; Junya Li; Haipeng Li (Livestock Science, 2023)

A late Neoproterozoic to early Paleozoic accretionary orogenic belt in the eastern Central Asian orogenic Belt: Evidence from the Irshi ophiolite mélange in the middle segment of the Great Xing’an Range - Jianfeng Liu; Jinyi Li; Shuo Zhao; Maohui Ge; Yawen Che (Journal of Asian Earth Sciences, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

Challenges and engineering application of landfill leachate concentrate treatment - Qian Li; Hanlin Cui; Yihao Li; Xin Song; Wenzong Liu; Yongxuan Wang; Haimeng Hou; Hongbo Zhang; You Li; Fan Wang; Jun Song; Hanfeng Ye; et al. (Environmental Research, 2023)

Investigation of heavy gas dispersion characteristics in a static environment: Spatial distribution and volume flux prediction - Yuanqing Ma; Angui Li; Jigang Che; Tianqi Wang; Changqing Yang; Lunfei Che; Jun Liu (Building and Environment, 2023)

Biomass burning and aqueous reactions drive the elevation of wintertime PM2.5 in the rural area of the Sichuan basin, China - Xinyi Zhang; Zhier Bao; Liuyi Zhang; Jiawei Zhou; Hanxiong Che; Qing Li; Mi Tian; Fumo Yang; Yang Chen (Atmospheric Environment, 2023)

Springtime reactive volatile organic compounds (VOCs) and impacts on ozone in urban areas of Yunnan-Guizhou plateau, China: A PTR-TOF-MS study - Qing Li; Yan Han; Dasheng Huang; Jiawei Zhou; Hanxiong Che; Liuyi Zhang; Keding Lu; Fumo Yang; Yang Chen (Atmospheric Environment, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

Hexavalent chromate bioreduction by a magnetotactic bacterium Magnetospirillum gryphiswaldense MSR-1 and the effect of magnetosome synthesis. - Siang Chen Wu; Wei-Che Hsiao; Ya-Chun Zhao; Li-Fen Wu (Chemosphere, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Analysis and optimization of energy loss reduction in a modified tee with deflectors via energy dissipation and vortex strength - Yifei Yin; Angui Li; Jiaxing Li; Dingmeng Wu; Tianqi Wang; Yuanqing Ma; Lunfei Che (Energy and Buildings, 2023)

Multifunctional electrocatalyst based on MoCoFe LDH nanoarrays for the coupling of high efficiency Electro-Fenton and water splitting process - Fengjiang Chen; Hongchen Liu; Fan Yang; Sai Che; Neng Chen; Chong Xu; Ni Wu; Yankun Sun; Chunhui Yu; Yongfeng Li (Chemical Engineering Journal, 2023)

Green waste and sewage sludge feeding ratio alters co-composting performance: Emphasis on the role of bacterial community during humification - Zejin Zhang; Changqun Duan; Yuxian Liu; Anning Li; Xi Hu; Jingkun Chen; Song Zhang; Xin Li; Rongxiao Che; Shiyu Li; Flemming Ekelund; Xiaoyong Cui (Bioresource Technology, 2023)

Combined effect of surface PM2.5 assimilation and aerosol-radiation interaction on winter severe haze prediction in central and eastern China - Yue Peng; Hong Wang; Xiaoye Zhang; Ping Wang; Siting Li; Zhaodong Liu; Wenjie Zhang; Huizheng Che (Atmospheric Pollution Research, 2023)

Light-driven uranyl-organic frameworks used as signal-enhanced photoelectrochemical sensors for monitoring anthrax - Guang Che; Weiting Yang; Cong Wang; Meiling Li; Xinyi Li; Yamin Fu; Qinhe Pan (Analytica Chimica Acta, 2023)

Tracing the future of epidemics: Coincident niche distribution of host animals and disease incidence revealed climate‐correlated risk shifts of main zoonotic diseases in China - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Yiyang Su; Lingyu Che; Meng Zhang; Yumeng Lu; Pufan Gao; Jingjing Yang; Ying Xue; Guishuang Li (Global Change Biology, 2023)
Climate has critical roles in the origin, pathogenesis and transmission of infectious zoonotic diseases. However, large‐scale epidemiologic trend and specific response pattern of zoonotic diseases under future climate scenarios are poorly understood. Here, we projected the distribution shifts of transmission risks of main zoonotic diseases under climate change in China. First, we shaped the global habitat distribution of main host animals for three representative zoonotic diseases (2, 6, and 12 hosts for dengue, hemorrhagic fever, and plague, respectively) with 253,049 occurrence records using maximum entropy (Maxent) modeling. Meanwhile, we predicted the risk distribution of the above three diseases with 197,098 disease incidence records from 2004 to 2017 in China using an integrated Maxent modeling approach. The comparative analysis showed that there exist highly coincident niche distributions between habitat distribution of hosts and risk distribution of diseases, indicating that the integrated Maxent modeling is accurate and effective for predicting the potential risk of zoonotic diseases. On this basis, we further projected the current and future transmission risks of 11 main zoonotic diseases under four representative concentration pathways (RCPs) (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) in 2050 and 2070 in China using the above integrated Maxent modeling with 1,001,416 disease incidence records. We found that Central China, Southeast China, and South China are concentrated regions with high transmission risks for main zoonotic diseases. More specifically, zoonotic diseases had diverse shift patterns of transmission risks including increase, decrease, and unstable. Further correlation analysis indicated that these patterns of shifts were highly correlated with global warming and precipitation increase. Our results revealed how specific zoonotic diseases respond in a changing climate, thereby calling for effective administration and prevention strategies. Furthermore, these results will shed light on guiding future epidemiologic prediction of emerging infectious diseases under global climate change.

Physiological response of red macroalgae Pyropia yezoensis (Bangiales, Rhodophyta) to light quality: a short-term adaptation - Xuefeng Zhong; Shuai Che; Congying Xie; Lan Wu; Xinyu Zhang; Lin Tian; Chan Liu; Hongbo Li; Guoying Du (Algae, 2023)
Light quality is a common environmental factor which influences the metabolism of biochemical substances in algae and leads to the response of algal growth and development. Pyropia yezoensis is a kind of economic macroalgae that naturally grows in the intertidal zone where the light environment changes dramatically. In the present study, P. yezoensis thalli were treated under white light (control) and monochromatic lights with primary colors (blue, green, and red) for 14 days to explore their physiological response to light quality. During the first 3 days of treatment, P. yezoensis grew faster under blue light than other light qualities. In the next 11 days, it showed better adaptation to green light, with higher growth rate and photosynthetic capacity (reflected by a higher rETRmax = 61.58 and Ek = 237.78). A higher non-photochemical quenching was observed in the treatment of red light than others for 14 days. Furthermore, the response of P. yezoensis to light quality also results in the difference of photosynthetic pigment contents. The monochromatic light could reduce the synthesis of all pigments, but the reduction degree was different, which may relate to the spectral absorption characteristics of pigments. It was speculated that P. yezoensis adapted to a specific or changing light environments by regulating the synthesis of pigments to achieve the best use of light energy in photosynthesis and premium growth and metabolism.

Mutagenicity of PM2.5 and Ethnic Susceptibility in Chengdu-Chongqing Economic Circle, China - Shumin Zhang; Qin Zhang; Xiaomeng Li; Ronghua Zhang; Hanxiong Che; Zhenzhong Liu; Dongmei Guo; Fumo Yang; Yang Chen (Science of The Total Environment, 2023)

Two genes related to apoptosis in the hepatopancreas of juvenile prawn, Macrobrachium nipponense: Molecular characterization and transcriptional response to nanoplastic exposure - Yiming Li; Xinglin Du; Wen Li; Qichen Jiang; Yucong Ye; Ying Yang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

A novel magnetic buoyant-bead flotation method for the removal of typical microalgae from harmful algal blooms - Yan Zhao; Xuexue Wu; Wenjuan Chang; Wenlu Che; Yi Liu; Yanpeng Li (Journal of Environmental Chemical Engineering, 2023)

Visualization study on the flow and migration characteristics of R290/PAG oil in a room air conditioner during startup and defrosting processes - Che Wang; Jianhua Wu; Bowen Lei; Yanjun Du; Jinbo Li (International Journal of Refrigeration, 2023)

Seasonal evolution of aerosol loading and its vertical distribution in northeastern China from long-term satellite observations and model reanalysis - Hujia Zhao; Ke Gui; Yanjun Ma; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Lei Zhang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2023)

Hydrogen Gas Enhanced Seed Germination by Increasing Trehalose Biosynthesis in Cucumber - Panpan Huang; Changxia Li; Pengpeng Che; Huwei Liu; Zongxi Zhao; Li Feng; Xinjuan Liu; Weibiao Liao (Journal of Plant Growth Regulation, 2023)

The degradation of subalpine meadows significantly changed the soil microbiome - Kaifang Liu; Ting Li; Xingwu Duan; Song Zhang; Meiping Chen; Haiyan Hou; Zelin Wang; Anlan Yu; Danhong Chen; Xiaoliang Zhang; Jinming Hu; Yifan Dong; et al. (Agriculture, Ecosystems & Environment, 2023)

Impact of commercial cooking on urban PM2.5 and O3 with online data-assisted emission inventory - Yingzhi Yuan; Yun Zhu; Che-Jen Lin; Shuxiao Wang; Yanghong Xie; Haixian Li; Jia Xing; Bin Zhao; Mengmeng Zhang; Zhiqiang You (Science of The Total Environment, 2023)

A double-edged sword: Reductive soil disinfestation changes the fates of trace metal elements in soil - Jiahe Miao; Jiarong Hao; Ruijie Che; Fenghe Wang; Jining Li; Lei Liu; Xinyu Li; Haoyu Wang (Science of The Total Environment, 2023)

Simultaneous profiling of dust aerosol mass concentration and optical properties with polarized high-spectral-resolution lidar - Da Xiao; Nanchao Wang; Sijie Chen; Lingyun Wu; Detlef Müller; Igor Veselovskii; Chengcai Li; Eduardo Landulfo; Venkataraman Sivakumar; Jing Li; Huizheng Che; Jing Fang; et al. (Science of The Total Environment, 2023)

Modeling of energy carrier in solar-driven calcium-looping for thermochemical energy storage: Heat-mass transfer, chemical reaction and stress response - Jinbo Che; Fengnian Wang; Chao Song; Rui Wang; Yinshi Li (Chemical Engineering Journal, 2023)

Identifying spatio-temporal climatic characteristics and events of the South-Asian aerosol pollution transport to the Tibetan Plateau - Haoyang Xu; Jianjun He; Jingxin Li; Hongli Ren; Lei Zhang; Sunling Gong; Hong Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2023)

Effects of Broflanilide on Oxidative Stress and Expression of Apoptotic Genes in Zebrafish (Danio rerio) Gill - Kai Wang; Wunan Che; Manman Duan; Chengju Wang; Xiuwei Li; Lu He (Bulletin of Environmental Contamination and Toxicology, 2023)

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

Description and evaluation of a newly developed emission inventory processing system (EMIPS) - Wencong Chen; Yaqiang Wang; Jiawei Li; Ziwei Yi; Zhenchi Zhao; Bin Guo; Huizheng Che; Xiaoye Zhang (Science of The Total Environment, 2023)

The mechanism of H2O in the superheated steam affecting the quality of in-situ pyrolysates of oil shale kerogen: Part B-favorable conversion of residues - Fumin Zhao; Bao Li; Daochang Che; Shengyu Liu (Fuel, 2023)

GrpE and ComD contribute to the adherence, biofilm formation, and pathogenicity of Streptococcus suis - Fei Yu; Chunliu Dong; Yuefeng Zhang; Ruixiang Che; Chunmei Xie; Yanyan Liu; Zhiyun Zhang; Lu Li; Xueying Chen; Xuehui Cai; Gang Wang; Yanhua Li (Archives of Microbiology, 2023)

Assessment of toxic mechanisms and mode of action to three different levels of species for 14 antibiotics based on interspecies correlation, excess toxicity, and QSAR - Jin J. Li; Ya X. Yue; Jie F. Jiang; Sheng J. Shi; Hui X. Wu; Yuan H. Zhao; Fei F. Che (Chemosphere, 2023)

Impact of plant community structure and its diversity on richness and abundance of arthropod aphidophagous natural enemy community - Jian-hong Wang; Bin-bin Ren; Jin-li Shao; Wei Li; Shao-cheng Che (Urban Forestry & Urban Greening, 2023)

Adsorption and desorption of heavy metals at water sediment interface based on bayesian model - Zheng Li; Xizhi Li; Shuhang Wang; Feifei Che; Yang Zhang; Pingjian Yang; Jinbo Zhang; Yanxiao Liu; Huaicheng Guo; Zhenghui Fu (Journal of Environmental Management, 2023)

Design of novel double-layer coated ammonium polyphosphate and its application in flame retardant thermoplastic polyurethanes - Mei Wan; Congling Shi; Xiaodong Qian; Yueping Qin; Jingyun Jing; Honglei Che; Fei Ren; Jian Li; Bin Yu; Keqing Zhou (Chemical Engineering Journal, 2023)

Evaluation of the antimicrobial mechanism of biogenic selenium nanoparticles against Pseudomonas fluorescens - Ying Xu; Ting Zhang; Jiarui Che; Jiajia Yi; Lina Wei; Hongliang Li (Biofouling, 2023)

Study on the management efficiency of lanthanum/iron co-modified attapulgite on sediment phosphorus load - Yihe Qu; Li Zhao; Zhenghai Jin; Haoran Yang; Chengqi Tu; Feifei Che; Mohammad Russel; Xinshan Song; Wei Huang (Chemosphere, 2023)

Soil sample sizes for DNA extraction substantially affect the examination of microbial diversity and co-occurrence patterns but not abundance - Ting Li; Song Zhang; Jinming Hu; Haiyan Hou; Kexin Li; Qiuping Fan; Fang Wang; Linfeng Li; Xiaoyong Cui; Dong Liu; Rongxiao Che (Soil Biology and Biochemistry, 2023)

Real-world emission characteristics of semivolatile/intermediate-volatility organic compounds originating from nonroad construction machinery in the working process - Xianbao Shen; Hongqian Che; Tiantian Lv; Bobo Wu; Xinyue Cao; Xin Li; Hanyu Zhang; Xuewei Hao; Qi Zhou; Zhiliang Yao (Science of The Total Environment, 2023)

Iron/manganese binary metal oxide-biochar nano-composites with high adsorption capacities of Cd2+: Preparation and adsorption mechanisms - Jie Qu; Naiju Che; Guoliang Niu; Longfei Liu; Chengliang Li; Yanli Liu (Journal of Water Process Engineering, 2023)

Ultra-trace detection and efficient adsorption removal of multiple water-soluble volatile organic compounds by fluorescent sensor array - Huachao Che; Shulin Yan; Ming Xiong; Yulun Nie; Xike Tian; Yong Li (Journal of Hazardous Materials, 2023)

Purification identification and function analysis of ACE inhibitory peptide from Ulva prolifera protein - Zhiyong Li; Yuan He; Hongyan He; Weizhe Zhou; Mengru Li; Aiming Lu; Tuanjie Che; Songdong Shen (Food Chemistry, 2023)

Melanin from Sepia pharaonis ink alleviates mucosal damage and reduces inflammation to prevent alcohol-induced gastric ulcers - Lin Liu; Kuan Lu; Jingwen Xie; Hongxia Che; Hongyan Li; Xie Wancui (Food Bioscience, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Application of peanut shell biochar increases rice yield in saline-alkali paddy fields by regulating leaf ion concentrations and photosynthesis rate - Junlong Piao; Weikang Che; Xiang Li; Xuebin Li; Chengbo Zhang; Qingshu Wang; Feng Jin; Shuang Hua (Plant and Soil, 2023)

Report on the 3rd Board Meeting of the International Human Phenome Consortium - Mei Tian; Han Liu; Shunling Chen; Zhong Yang; Weishuo Tao; Shiwen Peng; Huiting Che; Li Jin (Phenomics, 2023)

Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Peng-Wei Tseng; Hau-Wen Li; Chih Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana , are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.

Changes in aerosol loading before, during and after the COVID-19 pandemic outbreak in China: Effects of anthropogenic and natural aerosol - Yuanxin Liang; Ke Gui; Huizheng Che; Lei Li; Yu Zheng; Xutao Zhang; Xindan Zhang; Peng Zhang; Xiaoye Zhang (Science of The Total Environment, 2023)

The protective effect of Eleutheroside E against the mechanical barrier dysfunction triggered by lipopolysaccharide in IPEC-J2 cells - Huijuan Li; Rui Han; Feng Yong; Yueli Fan; Bao Zhao; Xiaocai Hu; Tianrui Zhang; Dongsheng Che (Research in Veterinary Science, 2023)

New method for morphological identification and simultaneous quantification of multiple tetracyclines by a white fluorescent probe - Huachao Che; Yulun Nie; Xike Tian; Yong Li (Journal of Hazardous Materials, 2023)

Modeling study on the roles of the deposition and transport of PM2.5 in air quality changes over central-eastern China - Lei Zhang; Jianjun He; Sunling Gong; Xiaomei Guo; Tianliang Zhao; Huizheng Che; Hong Wang; Chunhong Zhou; Jingyue Mo; Ke Gui; Yu Zheng; Lei Li; et al. (Journal of Environmental Sciences, 2023)

Seasonal cycles and long-term trends of arctic tropospheric aerosols based on CALIPSO lidar observations - Wenrui Yao; Ke Gui; Yu Zheng; Lei Li; Yaqiang Wang; Huizheng Che; Xiaoye Zhang (Environmental Research, 2023)

Effect of high light and desiccation on photosystem II in the seedlings and mature plants of tropical seagrass Enhalus acoroides during low tide - Xingkai Che; Hu Li; Litao Zhang; Jianguo Liu (Journal of Oceanology and Limnology, 2023)

Effects of Toxin-Antitoxin System HicAB on Biofilm Formation by Extraintestinal Pathogenic E. coli - Bo Hou; Chen-Yan Wang; Shao-Wen Li; Lun-Jiang Zhou; Yong-Liang Che; Qiu-Yong Chen (Current Microbiology, 2023)

Disclosing the mutual influence of photocatalytic fuel cell and photoelectro-Fenton process in the fabrication of a sustainable hybrid system for efficient Amaranth dye removal and simultaneous electricity production - Shen-Hui Thor; Li-Ngee Ho; Soon-An Ong; Che Zulzikrami Azner Abidin; Cheng-Yong Heah; Kea-Lee Yap (Environmental Science and Pollution Research, 2022)

The effect of growth stage and plant counting accuracy of maize inbred lines on LAI and biomass prediction - Yingpu Che; Qing Wang; Long Zhou; Xiqing Wang; Baoguo Li; Yuntao Ma (Precision Agriculture, 2022)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

Hesperidin partly ameliorates the decabromodiphenyl ether-induced reproductive toxicity in pubertal mice - Shiqi Li; Siyan Che; Sunni Chen; Zheng Ruan; Li Zhang (Environmental Science and Pollution Research, 2022)

Polyculture Affects the Growth, Antioxidant Status, Nutrient Content, and Flavor of Chinese Mitten Crabs (Eriocheir sinensis) and Largemouth Bass (Micropterus salmoides) - Silu Che; Shiheng Li; Quanjie Li; Yi Sun; Zhaowei Zheng; Zhijuan Nie; Zhonglin Tang; Peipei Wang; Jiancao Gao; Gangchun Xu (Fishes, 2022)
Chinese mitten crabs (Eriocheir sinensis) and largemouth bass (Micropterus salmoides) are popular with consumers in China. In recent years, the polyculture of these two species has received more attention, but little is known about how their interactions affect their commercially important traits. In this study, we set up an E. sinensis monoculture group (EM), a M. salmoides monoculture group (MM), and a polyculture group containing both species (EP) and compared the growth parameters, antioxidant statuses, nutritional compositions, and flavor qualities of crabs and fish between the different culture modes. Growth parameters in male crabs and largemouth bass were significantly higher in the EP group than in the EM and MM groups, respectively. Crabs in the EM and EP groups did not differ significantly in malondialdehyde content or glutathione peroxidase activity, regardless of the sampling time, which suggests that crabs in these groups had similar antioxidant and immunity capacities. Compared to the MM group, the activities of superoxide dismutase and catalase of largemouth bass in the EP group were higher, indicating the superior antioxidant capacity of fish in the polyculture mode. Alkaline phosphatase and acid phosphatase activities of both crabs and largemouth bass fluctuated with time in all groups, indicating their important roles in maintaining the health of these cultured species. The amino acid and fatty acid contents of edible tissues were similar between the EM and EP groups and the MM and EP groups, suggesting comparable flavor and quality of edible tissues in crabs and largemouth bass between culture modes. This study provides theoretical support for the polyculture of Chinese mitten crabs and largemouth bass.

UCRNet: Underwater color image restoration via a polarization-guided convolutional neural network - Haofeng Hu; Yizhao Huang; Xiaobo Li; Liubing Jiang; Li Che; Tiegen Liu; Jingsheng Zhai (Frontiers in Marine Science, 2022)
Underwater images always suffer from low contrast and color distortion due to the wavelength-dependent scattering and absorption effects caused by particles existing in turbid water, especially in high turbidity conditions. Based on the polarization properties of the backscattering light, polarimetric methods can estimate the intensity level of the backscattering and the transmittance of the media. Accordingly, they can separate the target signal from the undesired ones to achieve high-quality imaging. In addition, learning-based polarimetric methods are effective for gray-model image restoration, but the learning-based polarimetric technique for color image restoration has yet to be considered. In this paper, we propose a 3- dimensional convolutional neural network, which maintains the correlation of polarization information among different polarization channel images as well as embodies polarization constraints, for underwater color image restoration. The experimental results verify that the proposed solution improves the image quality (i.e., the image contrast, details, and color) and outperforms other existing methods, especially when the turbidity of scattering media is high. The proposed solution can be readily applied to practical applications and potentially realize the clear vision in other scattering media, including biomedical imaging and remote sensing.

Flame atomic absorption spectrometry combined with surface-modified magnetic mesoporous silica microspheres by polyethyleneimine for enrichment, isolation and determination of Cu 2+ in preserved eggs after high-temperature digestion - Zhengxiang Li; Tong Che; Minghong Yang; Xujia Hu (Food Additives & Contaminants: Part A, 2022)

Overexpression of transcriptional regulator and tailoring enzyme leads to the discovery of anti-inflammatory meroterpenoids from marine-derived fungus Alternaria alternata JJY-32 - Guowei Liu; Dan Liu; Zongyuan Li; Jieying Jiao; Xuewen Hou; Xiaomin Zhang; Qian Che; Tianjiao Zhu; Dehai Li; Guojian Zhang (Frontiers in Marine Science, 2022)
Four new ACTG-toxins like meroterpenoids tricycloalternarenes O-R were discovered from a marine-derived fungus Alternaria alternata JJY-32 by the overexpression of a LaeA-like global transcriptional regulator and a MpaB-like biosynthetic tailoring enzyme. Among those structures, tricycloalternarene O possesses a non-canonical cyclohexanone-pyran fused furan ring structure and tricycloalternarene R contains a truncated isoprenoid terminal. The structures were elucidated based on comprehensive 1D and 2D NMR data and assisted by ECD calculations. Tricycloalternarenes O-R showed potent anti-inflammatory activity in TLR4-transfected microphage cells (RAW264.7).

Identification and expression analysis of the grape pentatricopeptide repeat (PPR) gene family in abiotic stress - Lili Che; Shixiong Lu; Guoping Liang; Huimin Gou; Min Li; Baihong Chen; Juan Mao (Physiology and Molecular Biology of Plants, 2022)

Brain structural connectivity sub typing in unilateral temporal lobe epilepsy - Zhensheng Li; Che Jiang; Wei Xiang; Zijuan Qi; Quwen Gao; Kairun Peng; Jian Lin; Wei Wang; Weimin Wang; Bingmei Deng (Brain Imaging and Behavior, 2022)

Effects of ecological restoration on soil biogenic elements and their ecological stoichiometry in the Yellow River Delta, China - Dongxue Li; Yi’na Li; Yiliang Xie; Baoshan Cui; Zhonghua Ning; Shuyan Zhang; Zhenggang Bi; Shouqiang Fu; Chunguang Che (Frontiers in Marine Science, 2022)
Coastal wetlands serve as sources and sinks of carbon, nitrogen, phosphorus, and sulfur, and their ecological stoichiometry intuitively indicates the biogeochemical cycle process of the region. This study investigated the changing trend of the contents of soil organic carbon (i.e., SOC), total nitrogen (i.e., TN), total phosphorus (i.e., TP), and total sulfur (i.e., TS) and their ecological stoichiometric ratios in 2019-2021 in the Yellow River Delta (including north and south banks) under the Internationally Important Wetland Biodiversity Conservation Project by conducting field surveys and experiments. The results showed that SOC, TN, and TP showed the highest content in the North Unrestoration, while the TS content appeared highest in the North Restoration. In addition, ecological restoration improved the biogenic element stability in both banks and improved the stability of ecological stoichiometry on the north bank while decreasing the ecological stoichiometry stability on the south bank. Notably, the changing trend of soil C/S in the North Unrestoration exhibited a considerably different profile similarity from the North Restoration, which indicates that the ecological restoration changed the wetland ecosystem from the perspective of soil C/S. Furthermore, the high content of soil biogenic elements SOC and high ratio of soil ecological stoichiometry C/N and C/S in the Yellow River Delta induce that they are more sensitive to environmental change. Over the three years, the contributions of soil moisture content, soil salinity, and pH to soil biogenic element contents and their stoichiometric ratios were 32.20%, 49.30%, and 18.50% on the north bank, respectively, and 85.70%, 8.50%, and 5.80% on the south bank, respectively. This study implies that ecological restoration generally has a positive effect on the soil biogenic element contents and their ecological stoichiometry in the Yellow River Delta and provides a reference for delta restoration.

A transgene-free method for rapid and efficient generation of precisely edited pigs without monoclonal selection - Kui Xu; Xiuling Zhang; Zhiguo Liu; Jinxue Ruan; Changjiang Xu; Jingjing Che; Ziyao Fan; Yulian Mu; Kui Li (Science China Life Sciences, 2022)

A preliminary study on the volcanic intrusive complex type beryllium metallogenic belt from the southeast coast of China - Can Rao; Rucheng Wang; Fuyuan Wu; Xudong Che; Xiaofeng Li; Qi Wang; Zhiqi Zhang; Runqiu Wu (Science China Earth Sciences, 2022)

Recycling and remanufacturing technology analysis of permanent magnet synchronous motor - Zheng Li; Pengju Wang; Shuai Che; Shenhui Du; Ying Li; Hexu Sun (Clean Technologies and Environmental Policy, 2022)

Evansella halocellulosilytica sp. nov., an alkali-halotolerant and cellulose-dissolving bacterium isolated from bauxite residue - Guo-Hong Liu; Manik Prabhu Narsing Rao; Qian-Qian Chen; Jian-Mei Che; Huai Shi; Bo Liu; Wen-Jun Li (Extremophiles, 2022)

Transcriptome analysis reveals the effects of strigolactone on shoot regeneration of apple - Sumeera Asghar; Yao Xiong; Meng Che; Xingqiang Fan; Hui Li; Yi Wang; Xuefeng Xu; Wei Li; Zhenhai Han (Plant Cell Reports, 2022)

Characteristics and trends of grassland degradation research - Tong Li; Lizhen Cui; Michele Scotton; Junfu Dong; Zhihong Xu; Rongxiao Che; Li Tang; Shuohao Cai; Wenchao Wu; Davide Andreatta; Yanfen Wang; Xiufang Song; et al. (Journal of Soils and Sediments, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

The neural mechanisms underlying the modulation of attentional deployment on emotional stability - Shuang Li; Zhiyu Liu; Liping Che; Yue Gong; Sijia Liu; Xiuyan Guo (Experimental Brain Research, 2022)

Response of bacterial communities in saline-alkali soil to different pesticide stresses - Juan Che; Yan Lei Zhu; Yan Hong Li; Rui Zhang; Zhi Yong Ruan; Wei Zhang (Environmental Science and Pollution Research, 2022)

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Linear polyketides produced by co-culture of Penicillium crustosum and Penicillium fellutanum - Guihong Yu; Peng Sun; Reyilamu Aierken; Chunxiao Sun; Zhenzhen Zhang; Qian Che; Guojian Zhang; Tianjiao Zhu; Qianqun Gu; Mingyu Li; Dehai Li (Marine Life Science & Technology, 2022)

Distinct assembly mechanisms of microbial sub-communities with different rarity along the Nu River - Song Zhang; Kexin Li; Jinming Hu; Fang Wang; Danhong Chen; Zejin Zhang; Ting Li; Linfeng Li; Juan Tao; Dong Liu; Rongxiao Che (Journal of Soils and Sediments, 2022)

Effect of strontium on nutrient uptake, physiological parameters, and strontium localization in lettuce - Dong Yan; Kuke Ding; Yingxue He; Li Fan; Yongfei Che; Yingjun Zhao; Xiaoyan Jiang (Environmental Science and Pollution Research, 2022)

Neobacillus rhizophilus sp. nov. and Neobacillus citreus sp. nov., isolated from the citrus rhizosphere soil - Guo-Hong Liu; Manik Prabhu Narsing Rao; Qian-Qian Chen; Huai Shi; Jian-Mei Che; Bo Liu; Wen-Jun Li (Archives of Microbiology, 2022)

Correlation between crystallite structure and pore structure of coals at different ranks - Junqing Meng; Weining Che; Shichao Li (Arabian Journal of Geosciences, 2022)

Correction to: Lederbergia citri sp. nov., and Lederbergia citrisecundus sp. nov., isolated from citrus rhizosphere - Guo‑Hong Liu; Manik Prabhu Narsing Rao; Qian‑Qian Chen; Jian‑Mei Che; Huai Shi; Bo Liu; Wen‑Jun Li (Current Microbiology, 2022)

Pregnancy leads to changes in the brain functional network: a connectome analysis - Tongpeng Chu; Yuna Li; Kaili Che; Fanghui Dong; Heng Ma; Yinghong Shi; Peiyou Gong; Feng Zhao; Xicheng Song; Haizhu Xie; Ning Mao (Brain Imaging and Behavior, 2022)

Determination of threshold soil salinity with consideration of salinity stress alleviation by applying nitrogen in the arid region - Zheng Che; Jun Wang; Jiusheng Li (Irrigation Science, 2022)

Nocturnal Eyes in Slipper Lobsters (Decapoda Scyllaridae): Physiological and Ecological Implications of Habitat Depths for Visual Traits - Oki Hayasaka; Hao-Yi Chang; Li-Chun Li; Yung-Che Tseng; Yi Ta Shao (Frontiers in Marine Science, 2022)
The light characteristics of an ecosystem drive evolutionary adaptations in visual traits, enhancing the diversity and abundance of species living there. The visual systems of crustaceans are highly diverse and often correspond to the optical properties of their preferred environments. Although habitat depth is known to greatly influence visual specialization in marine crustaceans, it remains unclear whether depth drives visual adaptions in nocturnal species. Slipper lobsters (Scyllaridae) are nocturnal benthic marine crustaceans distributed throughout a wide range of depths. In order to understand the visual adaptive capabilities of slipper lobsters inhabiting different depths, we characterized the eye structures of a shallow-water species ( Parribacus japonicas ), an intermediate-depth species ( Scyllarides squammosus ) and a deep-water species ( Ibacus novemdentatus ). Moreover, we measured by electroretinogram (ERG) the spectral sensitivities and temporal resolutions for each species using the following light stimuli: UV (λ max 386 nm), blue (λ max 462 nm), green (λ max 518 nm), yellow (λ max 590 nm), and red (λ max 632 nm). Our histological experiments show that all three species possess a typical superposition compound eye with square facets, and their ERG measurements revealed a single sensitivity peak for each species. Notably, peak spectral sensitivity corresponded to habitat depth, with the estimated peak for I. novemdentatus (493.0 ± 9.8 nm) being similar to that of S. squammosus (517.4 ± 2.1 nm), but lower than that of P. japonicus (537.5 ± 9.9 nm). Additionally, the absolute sensitivities at respective peak wavelengths for I. novemdentatus and P. japonicus were higher than that of S. squammosus . No differences were observed among the three species for maximum critical flicker fusion frequency (CFF max ) across light stimuli. However, P. japonicus had lower CFF max values than the other two species. These data suggest that all three nocturnal slipper lobsters are likely monochromatic and well adapted to dim light environments. Significantly, the deep-water slipper lobster displayed higher spectral sensitivities at shorter wavelengths than the shallow water species, but temporal resolution was not compromised.

Discrepancy in photosynthetic responses of the red alga Pyropia yezoensis to dehydration stresses under exposure to desiccation, high salinity, and high mannitol concentration - Guoying Du; Xiaojiao Li; Junhao Wang; Shuai Che; Xuefeng Zhong; Yunxiang Mao (Marine Life Science & Technology, 2022)
Macroalgae that inhabit intertidal zones are exposed to the air for several hours during low tide and must endure desiccation and high variations in temperature, light intensity, and salinity. Pyropia yezoensis (Rhodophyta, Bangiales), a typical intertidal red macroalga that is commercially cultivated in the northwestern Pacific Ocean, was investigated under different dehydration stresses of desiccation, high salinity, and high mannitol concentration. Using chlorophyll fluorescence imaging, photosynthetic activities of P . yezoensis thalli were analyzed using six parameters derived from quenching curves and rapid light curves. A distinct discrepancy was revealed in photosynthetic responses to different dehydration stresses. Dehydration caused by exposure to air resulted in rapid decreases in photosynthetic activities, which were always lower than two other stresses at the same water loss (WL) level. High salinity only reduced photosynthesis significantly at its maximum WL of 40% but maintained a relatively stable maximum quantum yield of photosystem II (PSII) (F v /F m ). High mannitol concentration induced maximum WL of 20% for a longer time (60 min) than the other two treatments and caused no adverse influences on the six parameters at different WL except for a significant decrease in non-photochemical quenching (NPQ) at 20% WL. Illustrated by chlorophyll fluorescence images, severe spatial heterogeneities were induced by desiccation with lower values in the upper parts than the middle or basal parts of the thalli. The NPQ and rETR max (maximum relative electron transport rate) demonstrated clear distinctions for evaluating photosynthetic responses, indicating their sensitivity and applicability. The findings of this study indicated that the natural dehydration of exposure to air results in stronger and more heterogeneous effects than those of high salinity or high mannitol concentration.

Structural diversity and biological activity of natural p-terphenyls - Guoliang Zhou; Tianjiao Zhu; Qian Che; Guojian Zhang; Dehai Li (Marine Life Science & Technology, 2022)

Lederbergia citri sp. nov., and Lederbergia citrisecundus sp. nov., isolated from citrus rhizosphere - Guo-Hong Liu; Manik Prabhu Narsing Rao; Qian-Qian Chen; Jian-Mei Che; Huai Shi; Bo Liu; Wen-Jun Li (Current Microbiology, 2022)

Microbacterium sulfonylureivorans sp. nov., isolated from sulfonylurea herbicides degrading consortium - Qingyun Ma; Delong Kong; Qi Zhang; Miaomiao Li; Xiaoyan Han; Juan Che; Yiqing Zhou; Wei Zhang; Xu Jiang; Zhiyong Ruan (Archives of Microbiology, 2022)

Characteristics and failure mechanism of landslides along highways triggered by 2021 Ms6.4 Yangbi earthquake - Hanxu Zhou; Ailan Che; Guo Li (Landslides, 2022)

Experimental investigation and discrete element method simulation on mechanical properties and failure mechanism of polymer-stabilized sand - Wenyue Che; Jin Liu; Hongyang Li; Chengzong He; Yuxia Bai; Zezhuo Song; Ying Wang; Wei Qian; Zhihao Chen (Bulletin of Engineering Geology and the Environment, 2022)

Relationship between L-lactate dehydrogenase and multidrug resistance in Staphylococcus xylosus - Zhongwei Yuan; Jinpeng Wang; Ruixiang Che; Bello-Onaghise God’spower; Yonghui Zhou; Chunliu Dong; Lu Li; Mingri Chen; Nsabimana Eliphaz; Xin Liu; Yanhua Li (Archives of Microbiology, 2022)

Estimating concentrations for particle and gases in a mechanically ventilated building in Hong Kong: multivariate method and machine learning - Wenwei Che; Alison T. Y. Li; Alexis K. H. Lau (Air Quality, Atmosphere & Health, 2022)

Synergistic Therapy of Doxorubicin with Cationic Anticancer Peptide L-K6 Reverses Multidrug Resistance in MCF-7/ADR Cancer Cells In Vitro via P-glycoprotein Inhibition - Che Wang; Lili Huang; Ruojin Li; Ying Wang; Xiaoxue Wu; Dejing Shang (International Journal of Peptide Research and Therapeutics, 2021)

Retraction Note: Coastal meteorological characteristics based on big data and financial tax optimization of urban enterprises - Zhou Li; Che Ping (Arabian Journal of Geosciences, 2021)

Identification of Neuronal Polarity by Node-Based Machine Learning - Chen-Zhi Su; Kuan-Ting Chou; Hsuan-Pei Huang; Chiau-Jou Li; Ching-Che Charng; Chung-Chuan Lo; Daw-Wei Wang (Neuroinformatics, 2021)
Identifying the direction of signal flows in neural networks is important for understanding the intricate information dynamics of a living brain. Using a dataset of 213 projection neurons distributed in more than 15 neuropils of a Drosophila brain, we develop a powerful machine learning algorithm: node-based polarity identifier of neurons (NPIN). The proposed model is trained only by information specific to nodes, the branch points on the skeleton, and includes both Soma Features (which contain spatial information from a given node to a soma) and Local Features (which contain morphological information of a given node). After including the spatial correlations between nodal polarities, our NPIN provided extremely high accuracy (>96.0%) for the classification of neuronal polarity, even for complex neurons with more than two dendrite/axon clusters. Finally, we further apply NPIN to classify the neuronal polarity of neurons in other species (Blowfly and Moth), which have much less neuronal data available. Our results demonstrate the potential of NPIN as a powerful tool to identify the neuronal polarity of insects and to map out the signal flows in the brain’s neural networks if more training data become available in the future.

The severe toxicity of CuO nanoparticles to the photosynthesis of the prokaryotic algae Arthrospira sp - Xingkai Che; Ruirui Ding; Qiang Zhang; Yujie Li; Qi Sun; Yuting Li; Zishan Zhang; Wei Wang; Huiyuan Gao (Environmental Science and Pollution Research, 2021)

Effects of Biochar Application on Soil Organic Carbon in Degraded Saline-sodic Wetlands of Songnen Plain, Northeast China - Qianjin Che; Min Li; Zhongsheng Zhang (Chinese Geographical Science, 2021)

Resolving Transboundary Water Conflicts: Dynamic Evolutionary Analysis Using an Improved GMCR Model - Mengjie Yang; Kai Yang; Yue Che; Shiqiang Lu; Fengyun Sun; Ying Chen; Mengting Li (Water Resources Management, 2021)

LncRNA AFAP1-AS1 promotes M1 polarization of macrophages and osteogenic differentiation of valve interstitial cells - Welai He; Hong Che; Chaolong Jin; Yanli Li; Feng Li; Ruyuan Zhou (Journal of Physiology and Biochemistry, 2021)

Double-network cross-linked aerogel with rigid and super-elastic conversion: simple formation, unique properties, and strong sorption of organic contaminants - Longfei Liu; Yanli Liu; Miaomiao Tan; Naiju Che; Chengliang Li (Environmental Science and Pollution Research, 2021)

Linking hydraulic geometry, land use, and stream water quality in the Taihu Basin, China - Yaoyi Liu; Hongju Zhang; Peng Zeng; Yukun Wang; Gen Li; Fengyun Sun; Yue Che (Environmental Monitoring and Assessment, 2021)

Comparison of the Digestion and Absorption Characteristics of Docosahexaenoic Acid-Acylated Astaxanthin Monoester and Diester in Mice - Ye Li; Jie Yu; Jie Xu; Hongxia Che; Yuming Wang; Changhu Xue; Qingrong Huang; Tiantian Zhang (Journal of Ocean University of China, 2021)

RETRACTED ARTICLE: Coastal meteorological characteristics based on big data and financial tax optimization of urban enterprises - Zhou Li; Che Ping (Arabian Journal of Geosciences, 2021)

Exploring the Deeper Crustal Structure Beneath the Tatun Volcanic Area, Taiwan - Chien-Min Su; Wei-Jhe Wu; Strong Wen; Yi-Heng Li; Yen-Che Liao; Wen-Yen Chang; Chau-Huei Chen (Pure and Applied Geophysics, 2021)

Correction to: Involvement of P2Y12 receptor of stellate ganglion in diabetic cardiovascular autonomic neuropathy - Jingjing Guo; Xuan Sheng; Yu Dan; Yurong Xu; Yuanruohan Zhang; Huihong Ji; Jiayue Wang; Zixi Xu; Hongyu Che; Guodong Li; Shangdong Liang; Guilin Li (Purinergic Signalling, 2021)

Unraveling Physiological and Metabolomic Responses Involved in Phlox subulata L. Tolerance to Drought Stress - Yan Xiong; Yanting Qu; Hui Han; Fei Chen; Li Li; Huanwei Tang; Daidi Che; Xing Zhang (Plant Molecular Biology Reporter, 2021)

Neobacillus sedimentimangrovi sp. nov., a Thermophilic Bacterium Isolated from Mangrove Sediment - Rong Tang; Qi Zhang; Manik Prabhu Narsing Rao; Guo-Hong Liu; Jian-Mei Che; Min Lei; Bo Liu; Wen-Jun Li; Shun-Gui Zhou (Current Microbiology, 2021)

Changes in the Microbiome of the Inner Surface of Clear Aligners After Different Usage Periods - Dong Yan; Yi Liu; Xiaoxia Che; Sicong Mi; Yao Jiao; Lijia Guo; Song Li (Current Microbiology, 2021)

Mapping the permafrost stability on the Tibetan Plateau for 2005–2015 - Youhua Ran; Xin Li; Guodong Cheng; Zhuotong Nan; Jinxing Che; Yu Sheng; Qingbai Wu; Huijun Jin; Dongliang Luo; Zhiguang Tang; Xiaobo Wu (Science China Earth Sciences, 2021)

Dorsolateral Striatal proBDNF Improves Reversal Learning by Enhancing Coordination of Neural Activity in Rats - Wei Sun; Hongxia Che; Jia Li; Dongxin Tang; Xiaoyun Liu; Wenhui Liu; Lei An (Molecular Neurobiology, 2020)

Unraveling influence of metal species on norfloxacin removal by mesoporous metallic silicon adsorbent - Guiquan Che; Qiuyun Zhang; Lin Lin; Weirui Chen; Xukai Li; Laisheng Li (Environmental Science and Pollution Research, 2020)

First report of leaf blight on Cattleya × hybrid caused by Neoscytalidium dimidiatum in Taiwan - Che-Wei Chang; Chi-Yu Chen; Chih-Li Wang; Wen-Hsin Chung (Journal of Plant Pathology, 2020)

Reclassification of Brevibacterium frigoritolerans DSM 8801T as Bacillus frigoritolerans comb. nov. Based on Genome Analysis - Guo-Hong Liu; Bo Liu; Jie-Ping Wang; Jian-Mei Che; Peng-Fei Li (Current Microbiology, 2020)

Increased litter input significantly changed the total and active microbial communities in degraded grassland soils - Rongxiao Che; Dong Liu; Jinling Qin; Fang Wang; Weijin Wang; Zhihong Xu; Linfeng Li; Jinming Hu; Iman Tahmasbian; Xiaoyong Cui (Journal of Soils and Sediments, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Large paleo-rockslide induced by buckling failure at Jiasian in Southern Taiwan - Che-Ming Yang; Keng-Hao Kang; Shun-Hsing Yang; Kuo-Wei Li; Hui-Jung Wang; Yin-Tsan Lee; Kuei-Kun Lin; Yii-Wen Pan; Jyh-Jong Liao (Landslides, 2020)

Effects of network topologies on stochastic resonance in feedforward neural network - Jia Zhao; Yingmei Qin; Yanqiu Che; Huangyanqiu Ran; Jingwen Li (Cognitive Neurodynamics, 2020)

Research Progress on Estimation of the Atmospheric Boundary Layer Height - Hongsheng Zhang; Xiaoye Zhang; Qianhui Li; Xuhui Cai; Shaojia Fan; Yu Song; Fei Hu; Huizheng Che; Jiannong Quan; Ling Kang; Tong Zhu (Journal of Meteorological Research, 2020)

GWAS reveals two novel loci for photosynthesis-related traits in soybean - Li Wang; Yuming Yang; Shuyu Zhang; Zhijun Che; Wenjie Yuan; Deyue Yu (Molecular Genetics and Genomics, 2020)

The cognitive and neural mechanisms underlying norm-enforcement behaviors under social observation - Hui Ouyang; Fenfen Sun; Liping Che; Weidong Zhang; Xuemei Cheng; Li Zheng (Experimental Brain Research, 2020)

Deformation behaviors of dip slopes considering the scale effect and their geological properties - Wen-Chao Huang; Kun-Che Li; Jheng-Yu Hsieh; Meng-Chia Weng; Wen-Yi Hung (Bulletin of Engineering Geology and the Environment, 2020)

Synthesis and plant growth regulatory activities of 2′,3′-PhABA and iso-2′,3′-PhABA esters - Chuan Wan; Jiaqi Li; Fenghai Zhao; Dongyan Yang; Chuanliang Che; Shanshan Ding; Yimin Hu; Yumei Xiao; Zhaohai Qin (Molecular Diversity, 2020)

Terrestrial N 2 O emissions and related functional genes under climate change: A global meta‐analysis - Linfeng Li; Zhenzhen Zheng; Weijin Wang; Joel A. Biederman; Xingliang Xu; Qinwei Ran; Ruyan Qian; Cong Xu; Biao Zhang; Fang Wang; Shutong Zhou; Lizhen Cui; et al. (Global Change Biology, 2020)
Nitrous oxide (N 2 O) emissions from soil contribute to global warming and are in turn substantially affected by climate change. However, climate change impacts on N 2 O production across terrestrial ecosystems remain poorly understood. Here, we synthesized 46 published studies of N 2 O fluxes and relevant soil functional genes (SFGs, that is, archaeal amoA , bacterial amoA , nosZ , narG , nirK and nirS ) to assess their responses to increased temperature, increased or decreased precipitation amounts, and prolonged drought (no change in total precipitation but increase in precipitation intervals) in terrestrial ecosystem (i.e. grasslands, forests, shrublands, tundra and croplands). Across the data set, temperature increased N 2 O emissions by 33%. However, the effects were highly variable across biomes, with strongest temperature responses in shrublands, variable responses in forests and negative responses in tundra. The warming methods employed also influenced the effects of temperature on N 2 O emissions (most effectively induced by open‐top chambers). Whole‐day or whole‐year warming treatment significantly enhanced N 2 O emissions, but daytime, nighttime or short‐season warming did not have significant effects. Regardless of biome, treatment method and season, increased precipitation promoted N 2 O emission by an average of 55%, while decreased precipitation suppressed N 2 O emission by 31%, predominantly driven by changes in soil moisture. The effect size of precipitation changes on nirS and nosZ showed a U‐shape relationship with soil moisture; further insight into biotic mechanisms underlying N 2 O emission response to climate change remain limited by data availability, underlying a need for studies that report SFG. Our findings indicate that climate change substantially affects N 2 O emission and highlights the urgent need to incorporate this strong feedback into most climate models for convincing projection of future climate change.

Interaction Between Planetary Boundary Layer and PM2.5 Pollution in Megacities in China: a Review - Yucong Miao; Jing Li; Shiguang Miao; Huizheng Che; Yaqiang Wang; Xiaoye Zhang; Rong Zhu; Shuhua Liu (Current Pollution Reports, 2019)
Purpose of Review During the past decades, the number and size of megacities have been growing dramatically in China. Most of Chinese megacities are suffering from heavy PM 2.5 pollution. In the pollution formation, the planetary boundary layer (PBL) plays an important role. This review is aimed at presenting the current state of understanding of the PBL-PM 2.5 interaction in megacities, as well as to identify the main gaps in current knowledge and further research needs. Recent Findings The PBL is critical to the formation of urban PM 2.5 pollution at multiple temporal scales, ranging from diurnal change to seasonal variation. For the essential PBL structure/process in pollution, the coastal megacities have different concerns from the mountainous or land-locked megacities. In the coastal cities, the recirculation induced by sea-land breeze can accumulate pollutants, whereas in the valley/basin, the blocking effects of terrains can lead to stagnant conditions and thermal inversion. Within a megacity, although the urbanization-induced land use change can cause thermodynamic perturbations and facilitate the development of PBL, the increases in emissions outweigh this impact, resulting in a net increase of aerosol concentration. Moreover, the aerosol radiative effects can modify the PBL by heating the upper layers and reducing the surface heat flux, suppressing the PBL and exacerbating the pollution. Summary This review presented the PBL-PM 2.5 interaction in 13 Chinese megacities with various geographic conditions and elucidated the critical influencing processes. To further understand the complicated interactions, long-term observations of meteorology and aerosol properties with multi-layers in the PBL need to be implemented.

Genome-based reclassification of Bacillus plakortidis Borchert et al. 2007 and Bacillus lehensis Ghosh et al. 2007 as a later heterotypic synonym of Bacillus oshimensis Yumoto et al. 2005; Bacillus rhizosphaerae Madhaiyan et al. 2011 as a later heterotypic synonym of Bacillus clausii Nielsen et al. 1995 - Guo-Hong Liu; Manik Prabhu Narsing Rao; Zhou-Yan Dong; Jie-Ping Wang; Jian-Mei Che; Qian-Qian Chen; Cetin Sengonca; Bo Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Validation of an operational forecasting system of sea dike risk in the southern Zhejiang, South China - Tao Li; Fangdong Wang; Jingming Hou; Zhumei Che; Jianxi Dong (Journal of Oceanology and Limnology, 2019)

Surface wave simulation during winter with sea ice in the Bohai Sea - Che Yue; Jingkai Li; Changlong Guan; Xihu Lian; Kejian Wu (Journal of Oceanology and Limnology, 2019)

α -Pyrone derivatives with cyto-protective activity from two Takla Makan desert soil derived actinomycete Nocardiopsis strains recovered in seawater based medium - Tingting Zhao; Yimin Chang; Tianjiao Zhu; Jing Li; Qianqun Gu; Dehai Li; Qian Che; Guojian Zhang (Natural Product Research, 2019)

An improvement of the retrieval of temperature and relative humidity profiles from a combination of active and passive remote sensing - Yunfei Che; Shuqing Ma; Fenghua Xing; Siteng Li; Yaru Dai (Meteorology and Atmospheric Physics, 2019)

Seminal Plasma Exosomes: Promising Biomarkers for Identification of Male and Pseudo-Males in Cynoglossus semilaevis - Bo Zhang; Na Zhao; Lei Jia; Kang Peng; Jinyuan Che; Kunming Li; Xiaoxu He; Jinsheng Sun; Baolong Bao (Marine Biotechnology, 2019)

Variation in MERRA-2 aerosol optical depth over the Yangtze River Delta from 1980 to 2016 - Enwei Sun; Huizheng Che; Xiaofeng Xu; Zhenzhu Wang; Chunsong Lu; Ke Gui; Hujia Zhao; Yu Zheng; Yaqiang Wang; Hong Wang; Tianze Sun; Yuanxin Liang; et al. (Theoretical and Applied Climatology, 2019)

The joint impact of smoking plus alcohol drinking on treatment of pulmonary tuberculosis - Y. Ma; N.-Y. Che; Y.-H. Liu; W. Shu; J. Du; S.-H. Xie; Liang Li (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Role of Exogenous Glutathione in Alleviating Abiotic Stress in Maize (Zea mays L.) - Laming Pei; Ronghui Che; Linlin He; Xingxing Gao; Weijun Li; Hui Li (Journal of Plant Growth Regulation, 2019)

Antibacterial and anticorrosive properties of CuZnO@RGO waterborne polyurethane coating in circulating cooling water - Guofei Jiang; Xufei Li; Yangli Che; Yan Lv; Fang Liu; Yongqiang Wang; Chaocheng Zhao; Xiaojuan Wang (Environmental Science and Pollution Research, 2019)

Geological significance of the former Xiong’er Volcanic Belt on the southwestern margin of the North China Craton - Guanxu Chen; Jinhai Luo; Huan Xu; Jia You; Yifei Li; Zichen Che (Frontiers of Earth Science, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Involvement of P2Y12 receptor of stellate ganglion in diabetic cardiovascular autonomic neuropathy - Jingjing Guo; Xuan Sheng; Yu Dan; Yurong Xu; Yuanruohan Zhang; Huihong Ji; Jiayue Wang; Zixi Xu; Hongyu Che; Guodong Li; Shangdong Liang; Guilin Li (Purinergic Signalling, 2018)

The Effect of Hydrolysis with Neutrase on Molecular Weight, Functional Properties, and Antioxidant Activities of Alaska Pollock Protein Isolate - Chuyi Liu; Xiaoming Ma; Shuai Che; Changwei Wang; Bafang Li (Journal of Ocean University of China, 2018)

Energy-Based Brittleness Index and Acoustic Emission Characteristics of Anisotropic Coal Under Triaxial Stress Condition - Jun Zhang; Chi Ai; Yu-wei Li; Ming-guang Che; Rui Gao; Jia Zeng (Rock Mechanics and Rock Engineering, 2018)

Endothelium-independent vasodilator effect of isocorynoxeine in vitro isolated from the hook of Uncaria rhynchophylla (Miquel) - Ting Li; Ke Xu; Delu Che; Zhuangzhuang Huang; Nabila Jahan; Sicen Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Natural variation ofCsSTOP1in tea plant (Camellia sinensis) related to aluminum tolerance - Hua Zhao; Wei Huang; Yange Zhang; Ziwei Zhang; Yong Li; Che Tang; Jie Huang; Dejiang Ni (Plant and Soil, 2018)

Rainfall and inflow effects on soil erosion for hillslopes dominated by sheet erosion or rill erosion in the Chinese Mollisol region - Hai-ou Shen; Lei-lei Wen; Yun-feng He; Wei Hu; Hong-li Li; Xiao-cui Che; Xin Li (Journal of Mountain Science, 2018)

Acetaminophen Poisoning May Increase Coronary Artery Disease Risk: A Nationwide Cohort Study - Yu-Ting Chung; Che-Yi Chou; Wen-Chen Tsai; Wei-Kung Chen; Cheng-Li Lin; Wei-Sheng Chung (Cardiovascular Toxicology, 2018)

The Contribution of Opal-Associated Phosphorus to Bioavailable Phosphorus in Surface and Core Sediments in the East China Sea - Huanxin Li; Huijun He; Shifeng Yang; Yanli Liu; Hong Che; Mujian Li; Jing Zhang (Journal of Ocean University of China, 2018)

Weekday AOD smaller than weekend AOD in eastern China on the basis of the MODIS AOD product - Jingjing Song; Xiangao Xia; Xiaoling Zhang; Huizheng Che; Xiaojing Li (Theoretical and Applied Climatology, 2018)

TGF-β-induced NKILA inhibits ESCC cell migration and invasion through NF-κB/MMP14 signaling - Zhiliang Lu; Zhaoli Chen; Yuan Li; Jingnan Wang; Zhirong Zhang; Yun Che; Jianbing Huang; Shouguo Sun; Shuangshuang Mao; Yuanyuan Lei; Yibo Gao; Jie He (Journal of Molecular Medicine, 2018)

Comparison of Two Air Pollution Episodes over Northeast China in Winter 2016/17 Using Ground-Based Lidar - Yanjun Ma; Hujia Zhao; Yunsheng Dong; Huizheng Che; Xiaoxiao Li; Ye Hong; Xiaolan Li; Hongbin Yang; Yuche Liu; Yangfeng Wang; Ningwei Liu; Cuiyan Sun (Journal of Meteorological Research, 2018)

Suppression of Disheveled–Axin Domain Containing 1 (DIXDC1) by MicroRNA-186 Inhibits the Proliferation and Invasion of Retinoblastoma Cells - Xuanyi Che; Yuanjie Qian; Di Li (Journal of Molecular Neuroscience, 2018)

Aerosol optical properties and radiative impacts in the Pearl River Delta region of China during the dry season - Boru Mai; Xuejiao Deng; Zhanqing Li; Jianjun Liu; Xiang’ao Xia; Huizheng Che; Xia Liu; Fei Li; Yu Zou; Maureen Cribb (Advances in Atmospheric Sciences, 2018)

Mitochondrial genome sequences uncover evolutionary relationships of two Sargassum subgenera, Bactrophycus and Sargassum - Feng Liu; Xiaodong Li; Zhiwei Che (Journal of Applied Phycology, 2017)

Optical and radiative properties of aerosols during a severe haze episode over the North China Plain in December 2016 - Yu Zheng; Huizheng Che; Leiku Yang; Jing Chen; Yaqiang Wang; Xiangao Xia; Hujia Zhao; Hong Wang; Deying Wang; Ke Gui; Linchang An; Tianze Sun; et al. (Journal of Meteorological Research, 2017)

Effects of different fertilizers on growth and nutrient uptake of Lolium multiflorum grown in Cd-contaminated soils - Mohan Liu; Yang Li; Yeye Che; Shaojun Deng; Yan Xiao (Environmental Science and Pollution Research, 2017)

Relative contributions of boundary-layer meteorological factors to the explosive growth of PM2.5 during the red-alert heavy pollution episodes in Beijing in December 2016 - Junting Zhong; Xiaoye Zhang; Yaqiang Wang; Junying Sun; Yangmei Zhang; Jizhi Wang; Kaiyan Tan; Xiaojing Shen; Haochi Che; Lu Zhang; Zhouxiang Zhang; Xuefei Qi; et al. (Journal of Meteorological Research, 2017)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

The Activities of Adhesion and Biofilm Formation by Candida tropicalis Clinical Isolates Display Significant Correlation with Its Multilocus Sequence Typing - Shuan Bao Yu; Wen Ge Li; Xiao Shu Liu; Jie Che; Jin Xing Lu; Yuan Wu (Mycopathologia, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

Simulating and mapping the risk of surge floods in multiple typhoon scenarios: a case study of Yuhuan County, Zhejiang Province, China - Mengya Li; Wei Wu; Jun Wang; Zhumei Che; Yali Xie (Stochastic Environmental Research and Risk Assessment, 2017)

Comparative Efficacy and Safety of Nine Anti-Platelet Therapies for Patients with Ischemic Stroke or Transient Ischemic Attack: a Mixed Treatment Comparisons - Hua-Pin Huang; Wan-Hui Lin; Sheng-Gen Chen; Li-Zhen Chen; Min-Yi Chen; Chun-Hui Che (Molecular Neurobiology, 2017)

Effect of Reducing Nitric Oxide in Rumex K-1 Leaves on the Photoprotection of Photosystem II Under High Temperature with Strong Light - Xingkai Che; Zishan Zhang; Liqiao Jin; Meijun Liu; Yuting Li; Huiyuan Gao; Shijie Zhao (Journal of Plant Growth Regulation, 2016)

The bioconcentration ability of heavy metal research for 50 kinds of rice under the same test conditions - Wen-Juan Xie; Lei Che; Guang-Yu Zhou; Li-Na Yang; Min-Yu Hu (Environmental Monitoring and Assessment, 2016)

Overexpression of IrlVHA-c, A Vacuolar-Type H+-ATPase c Subunit Gene from Iris lactea, Enhances Salt Tolerance in Tobacco - Jingang Wang; Aimin Zhou; Yang Li; Shanshan Li; Xiaohui Zhang; Daidi Che (Plant Molecular Biology Reporter, 2016)

Genetic diversity of gliadin in Secale cereale subsp. segetale from Xinjiang, China - Yonghe Che; Ming Dai; Yanping Yang; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Genetic Resources and Crop Evolution, 2016)

In-flight Excavation of a Loess Slope in a Centrifuge Model Test - Zhongjie Fan; P. H. S. W. Kulatilake; Jianbing Peng; Wenyue Che; Yazhe Li; Zhenjiang Meng (Geotechnical and Geological Engineering, 2016)

Richness and bioactivity of culturable soil fungi from the Fildes Peninsula, Antarctica - Zhuang Ding; Liyuan Li; Qian Che; Dehai Li; Qianqun Gu; Tianjiao Zhu (Extremophiles, 2016)

Serum Uric Acid Levels and Diabetic Peripheral Neuropathy in Type 2 Diabetes: a Systematic Review and Meta-analysis - Shuai Yu; Ying Chen; Xu Hou; Donghua Xu; Kui Che; Changgui Li; Shengli Yan; Yangang Wang; Bin Wang (Molecular Neurobiology, 2016)

Mono(2-ethylhexyl)phthalate accumulation disturbs energy metabolism of fat cells - Huai-chih Chiang; Ya-Ting Kuo; Chih-Che Shen; Yi-Hua Lin; Shu-Li Wang; Tsui-Chun Tsou (Archives of Toxicology, 2016)

Double-Edged Roles of Nitric Oxide Signaling on APP Processing and Amyloid-β Production In Vitro: Preliminary Evidence from Sodium Nitroprusside - Zheng-Xu Cai; Hui-Shu Guo; Che Wang; Min Wei; Cheng Cheng; Zhao-Fei Yang; Yin-Wang Chen; Wei-Dong Le; Song Li (Neurotoxicity Research, 2016)

An automatic approach for urban land-cover classification from Landsat-8 OLI data - Erzhu Li; Peijun Du; Alim Samat; Junshi Xia; Meiqin Che (International Journal of Remote Sensing, 2015)

Targeted Delivery of Superoxide Dismutase by Chemical Modification with Quaternary Ammonium Chitosan and Pharmacokinetic Analysis - Jinfeng Liu; Kebo Wang; Jie Li; Chengchuan Che; Ge Yang; Kejian Wang (Journal of Pharmaceutical Innovation, 2015)

Translational Intracerebral Hemorrhage: a Need for Transparent Descriptions of Fresh Tissue Sampling and Preclinical Model Quality - Che-Feng Chang; Li Cai; Jian Wang (Translational Stroke Research, 2015)

Evaluation of the Toxicity, AChE Activity and DNA Damage Caused by Imidacloprid on Earthworms, Eisenia fetida - Kai Wang; Suzhen Qi; Xiyan Mu; Tingting Chai; Yang Yang; Dandan Wang; Dongzhi Li; Wunan Che; Chengju Wang (Bulletin of Environmental Contamination and Toxicology, 2015)

Modeling and Analysis of the Viscoelastic Response of the Ankle Ligament Complex in Inversion Ankle Sprain - Che-Yu Lin; Yio-Wha Shau; Chung-Li Wang; Jiunn-Horng Kang (Annals of Biomedical Engineering, 2015)

A QTL with major effect on reducing leaf rust severity on the short arm of chromosome 1A of wheat detected across different genetic backgrounds and diverse environments - Ziyi Du; Mingzhe Che; Guohui Li; Jiang Chen; Wei Quan; Yan Guo; Zhen Wang; Junda Ren; Huyan Zhang; Zhongjun Zhang (Theoretical and Applied Genetics, 2015)

Development of a test strip for rapid detection of lactoperoxidase in raw milk - Hong-xia Che; Bo Tian; Li-na Bai; Li-ming Cheng; Li-li Liu; Xiao-na Zhang; Zhan-mei Jiang; Xiao-xi Xu (Journal of Zhejiang University-SCIENCE B, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Chronic hepatitis C virus infection triggers spontaneous differential expression of biosignatures associated with T cell exhaustion and apoptosis signaling in peripheral blood mononucleocytes - Muttiah Barathan; Kaliappan Gopal; Rosmawati Mohamed; Rada Ellegård; Alireza Saeidi; Jamuna Vadivelu; Abdul W. Ansari; Hussin A. Rothan; M. Ravishankar Ram; Keivan Zandi; Li Y. Chang; Ramachandran Vignesh; et al. (Apoptosis, 2015)

Microbial community and functional diversity associated with different aggregate fractions of a paddy soil fertilized with organic manure and/or NPK fertilizer for 20 years - Xiaofen Chen; Zhongpei Li; Ming Liu; Chunyu Jiang; Yuping Che (Journal of Soils and Sediments, 2015)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Residential Preferences for River Network Improvement: An Exploration of Choice Experiments in Zhujiajiao, Shanghai, China - Yue Che; Wen Li; Zhaoyi Shang; Chen Liu; Kai Yang (Environmental Management, 2014)

A new model for fish ion regulation: identification of ionocytes in freshwater- and seawater-acclimated medaka (Oryzias latipes) - Hao-Hsuan Hsu; Li-Yih Lin; Yung-Che Tseng; Jiun-Lin Horng; Pung-Pung Hwang (Cell and Tissue Research, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Functional TRPV and TRPM channels in human preadipocytes - Hui Che; Jianbo Yue; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2014)

Elevated expression of vascular endothelial growth factor (VEGF) 120 in parthenogenetic porcine placentas - Yang Han; Hongsheng Ouyang; Dongsheng Che; Xianju Chen; Yongye Huang; I. A. Elfaki elhag; Daxin Pang; Zhanjun Li (Biotechnology Letters, 2014)

A study on rational slopeland classification for land conservation in Taiwan: a case of Jhuoshuei River before Typhoon Morakot - Chao-Wen Wang; Che-Wei Shen; Li-Ling Lin (Paddy and Water Environment, 2014)

VPA inhibits renal cancer cell migration by targeting HDAC2 and down-regulating HIF-1α - Feng-qiang Yang; Min Liu; Feng-ping Yang; Jianping Che; Wei Li; Wei Zhai; Guang-chun Wang; Jun-hua Zheng; Xi Li (Molecular Biology Reports, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

A cellular response protein induced during HSV-1 infection inhibits viral replication by interacting with ATF5 - LianQiu Wu; XueMei Zhang; YanChun Che; Ying Zhang; SongQing Tang; Yun Liao; RuiXiong Na; XiangLin Xiong; LongDing Liu; QiHan Li (Science China Life Sciences, 2013)

Microbial Diversity and Succession in the Chinese Luzhou-Flavor Liquor Fermenting Cover Lees as Evaluated by SSU rRNA Profiles - Ke Li; Qing Zhang; Xiao-Ting Zhong; Bi-Hong Jia; Chun-Hong Yuan; Sen Liu; Zhen-Ming Che; Wen-Liang Xiang (Indian Journal of Microbiology, 2013)

Mapping of QTL conferring resistance to sharp eyespot (Rhizoctonia cerealis) in bread wheat at the adult plant growth stage - Jiang Chen; Guo Hui Li; Zi Yi Du; Wei Quan; Hu Yan Zhang; Ming Zhe Che; Zhen Wang; Zhong Jun Zhang (Theoretical and Applied Genetics, 2013)

Actinopolyspora dayingensis sp. nov., a novel halophilic actinomycete isolated from a hypersaline lake - Tong-Wei Guan; Hui-Ping Zhao; Zhen-Ming Che; Xiao-Ping Zhang; Li-Li Zhang (Antonie van Leeuwenhoek, 2013)

Purification, molecular cloning, and antimicrobial activity of peptides from the skin secretion of the black-spotted frog, Rana nigromaculata - Ang Li; Yong Zhang; Che Wang; Geng Wu; Zhenchun Wang (World Journal of Microbiology and Biotechnology, 2013)

Functional transient receptor potential canonical type 1 channels in human atrial myocytes - Yan-Hui Zhang; Hui-Jun Wu; Hui Che; Hai-Ying Sun; Lik-Cheung Cheng; Xin Li; Wing-Kuk Au; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2013)

Cloning, expression and characterization of squalene synthase from Inonotus obliquus - Fangliang Zheng; Nan Liu; Yuchen Che; Li Zhang; Lijie Shao; Junfeng Zhu; Jian Zhao; Haixin Ai; Alan K. Chang; Hongsheng Liu (Genes & Genomics, 2013)

Photosynthetic carbon fixation by tropical coral reef phytoplankton assemblages: a UVR perspective - Gang Li; Zhiwei Che; Kunshan Gao (Algae, 2013)

Identification and quantitative detection of Legionella spp. in various aquatic environments by real-time PCR assay - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Yi-Chou Chiu; Cheng-Yu She; Shu-Min Shen; Yu-Li Huang; Wen-Chien Huang (Environmental Science and Pollution Research, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Differential Legionella spp. survival between intracellular and extracellular forms in thermal spring environments - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Shih-Yung Hsu; Jen-Te Huang; Jorn-Hon Liu; Yu-Li Huang (Environmental Science and Pollution Research, 2013)

Inhibition of matrix metalloproteinase-9 expression by docosahexaenoic acid mediated by heme oxygenase 1 in 12-O-tetradecanoylphorbol-13-acetate-induced MCF-7 human breast cancer cells - Haw-Wen Chen; Che-Yi Chao; Li-Lin Lin; Chia-Yang Lu; Kai-Li Liu; Chong-Kuei Lii; Chien-Chun Li (Archives of Toxicology, 2013)

Microbial succession in the traditional Chinese Luzhou-flavor liquor fermentation process as evaluated by SSU rRNA profiles - Wenliang Xiang; Ke Li; Seng Liu; Yage Xing; Mingyuan Li; Zhenming Che (World Journal of Microbiology and Biotechnology, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

BjHO-1 is involved in the detoxification of heavy metal in India mustard (Brassica juncea) - Hua Li; Ming Jiang; Li Ling Che; Li Nie; Zhi Min Yang (BioMetals, 2012)

Triterpenoid saponins from Ilex mamillata C.Y. Wu ex C.J. Tseng - Che Yan-Yun; Zhang Liang; Li Ning; Zeng Ke-Wu; Tu Peng-Fei (Natural Product Research, 2012)

Simulation of direct radiative forcing of aerosols and their effects on East Asian climate using an interactive AGCM-aerosol coupled system - Hua Zhang; Zhili Wang; Zaizhi Wang; Qianxia Liu; Sunling Gong; Xiaoye Zhang; Zhongping Shen; Peng Lu; Xiaodong Wei; Huizheng Che; Laurent Li (Climate Dynamics, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Isolation and performance evaluation of halotolerant phosphate solubilizing bacteria from the rhizospheric soils of historic Dagong Brine Well in China - Wen-liang Xiang; Hua-zhong Liang; Sen Liu; Fan Luo; Jie Tang; Ming-yuan Li; Zhen-ming Che (World Journal of Microbiology and Biotechnology, 2011)

Changes of Iron Stores and Duodenal Transepithelial Iron Transfer During Regular Exercise in Rats - Li-Long Che; De-Sheng Xiao; Hua-Xi Xu; Liwei Lu (Biological Trace Element Research, 2011)

Soil organic C, nutrients, microbial biomass, and grain yield of rice (Oryza sativa L.) after 18 years of fertilizer application to an infertile paddy soil - Meirong Lv; Zhongpei Li; Yuping Che; F. X. Han; Ming Liu (Biology and Fertility of Soils, 2011)

A disease associated with phytoplasma in Parthenium hysterophorus - Zhengnan Li; Lei Zhang; Haiyan Che; Hongguang Liu; Ming Chi; Daquan Luo; Yan Li; Wang Chen; Yunfeng Wu (Phytoparasitica, 2011)

Modulatory Effects of Lactobacillus salivarius on Intestinal Mucosal Immunity of Piglets - Jinhua Zhang; Jun Deng; Zhisheng Wang; Chuanyan Che; Yun-feng Li; Qian Yang (Current Microbiology, 2011)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Assessment of the modulating effects of fructo-oligosaccharides on fecal microbiota using human flora–associated piglets - Jian Shen; Baorang Zhang; Hua Wei; Chuanyan Che; Dezhong Ding; Xiuguo Hua; Peter Bucheli; Linghua Wang; Yixue Li; Xiaoyan Pang; Liping Zhao (Archives of Microbiology, 2010)

Monitoring haze episodes over the Yellow Sea by combining multisensor measurements - Jianping Guo; Xiaoye Zhang; Chunxiang Cao; Huizheng Che; Hongli Liu; Pawan Gupta; Hao Zhang; Min Xu; Xiaowen Li (International Journal of Remote Sensing, 2010)

Prospective variants screening of connexin genes in children with hearing impairment: genotype/phenotype correlation - Jiann-Jou Yang; Wen-Hung Wang; Yen-Chun Lin; Hsu-Huei Weng; Jen-Tsung Yang; Chung-Feng Hwang; Che-Min Wu; Shuan-Yow Li (Human Genetics, 2010)

Eukaryotic expression and purification of anti-epilepsy peptide of Buthus martensii Karsch and its protein interactions - Zongren Wang; Wen Wang; Zhongjun Shao; Bifeng Gao; Junchang Li; Jing Ma; Jinghua Li; Honglei Che; Wei Zhang (Molecular and Cellular Biochemistry, 2009)

Haze trends over the capital cities of 31 provinces in China, 1981–2005 - Huizheng Che; Xiaoye Zhang; Yang Li; Zijiang Zhou; John J. Qu; Xianjun Hao (Theoretical and Applied Climatology, 2009)

Oxidative Damage of the Extracts of Condensate, Particulate and Semivolatile Organic Compounds from Gasoline Engine Exhausts on Testicles of Rats - Wangjun Che; Hong Qiu; Guiming Liu; Yun Ran; Hao Zhang; Li Zhang; Weihua Wen (Bulletin of Environmental Contamination and Toxicology, 2009)

Prediction of the heterosis of Laminaria hybrids with the genetic distance between their parental gametophyte clones - Xiaojie Li; Guanpin Yang; Yuanyuan Shi; Yizhou Cong; Shi Che; Shancun Qu; Zhiling Li (Journal of Applied Phycology, 2008)

A study of NO trafficking from dinitrosyl–iron complexes to the recombinant E. coli transcriptional factor SoxR - Feng-Chun Lo; Chang-Li Chen; Chien-Ming Lee; Ming-Che Tsai; Tsai-Te Lu; Wen-Feng Liaw; Steve S.-F. Yu (JBIC Journal of Biological Inorganic Chemistry, 2008)

On the use of SSR markers for the genetic characterization of the Agropyron cristatum (L.) Gaertn. in Northern China - Y. H. Che; H. J. Li; Y. P. Yang; X. M. Yang; X. Q. Li; L. H. Li (Genetic Resources and Crop Evolution, 2008)

Genetic diversity of prolamines in Agropyron mongolicum Keng indigenous to northern China - Y. H. Che; L. H. Li (Genetic Resources and Crop Evolution, 2007)

Analysis of sky conditions using 40 year records of solar radiation data in China - H. Z. Che; G. Y. Shi; X. Y. Zhang; J. Q. Zhao; Y. Li (Theoretical and Applied Climatology, 2007)

Vibrational analysis of mandible trauma: experimental and numerical approaches - Shu-Li Lin; Sheng-Yang Lee; Long-Yi Lee; Wen-Ta Chiu; Che-Tong Lin; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2006)

Comparison of EC and BC and evaluation of dust aerosol contribution to light absorption in Xi'an, China - Li Yang; Zhang Xiaoye; Gong Sunling; Che Huizheng; Wang Dan; Qu Wenjun; Un Junying (Environmental Monitoring and Assessment, 2006)

Nitric oxide and iron metabolism in exercised rat with L-arginine supplementation - De-Sheng Xiao; Lu Jiang; Li-Long Che; Liwei Lu (Molecular and Cellular Biochemistry, 2003)

Study on the aerosol transmission of Hantaan virus - Che Fengxiang; Lu Jianchun; Meng Lingyin; Li Jingsong; Li Junbao; Tong Yongyi; Zhang Chaolong; Zhang Songle; Hu Qingxuan; Lui Mingxia (Aerobiologia, 1998)

Population study of atmospheric bacteria at the Fengtai district of Beijing on two representative days - Tong Yongyi; Che Fengxiang; Xu Xiuzhi; Chen Mieleng; Ye Binyan; Jiang Li (Aerobiologia, 1993)

Particle diameter of the airborne microorganisms over Beijing and Tianjin area - Che Fengxiang; Hu Qingxuan; Meng Lingying; Li Junbao (Aerobiologia, 1992)